Metabolic redirection and capacity expansion in heterotroph-reinforced microalgae-methanotroph systems under high ammonia stress - Yong-Ze Lu; Jia-Sen Yang; Xin-Ya Tan; Yi-Ru Wang; Hong-Yin Sha; Hao-Yu Wang; Shao-Jie Zong; Guang-Can Zhu (Bioresource Technology, 2027)

Transfer learning and multi-branch intermediate fusion deep neural network for wheat nitrogen concentration monitoring using multi-scale multi-modal remote sensing information - Xiangxiang Su; Huihan Wang; Mi Yang; Dongmei Yu; Jieyu Li; Weiqiang Wang; Ying Nian; Xinwei Li; Ze Zhang (Computers and Electronics in Agriculture, 2026)

Antifungal activity and mechanism of 2-Fluoroadenine against Botrytis cinerea in postharvest tomato fruit - Liu Yang; Yan-Ze Wang; Ya-Ya Lei; Hui-Wen Wang; Yu-Chen Sun; Shao-Yong Zhang; Zhi-Jun Zhang; Xiong-Fei Luo; Ying-Qian Liu (Postharvest Biology and Technology, 2026)

DEM investigation of soil arching effect induced by vertical unloading under high geostress - Xing-Tao Lin; Ze-Yu Zhao; Dong Su; Xiangsheng Chen (Computers and Geotechnics, 2026)

Mechanistic and functional integration of sirtuin deacylases: from substrate specificity to biological outcomes - Jian-long Zhang; Zi-Yu Dou; Yong-yue Fan; De-guan Sun; Xiong-jie Fan; Ze Yu; Guo-Cai Yang (Glycoconjugate Journal, 2026)

Early plant community changes in degraded alpine grasslands associated with restoration-induced shifts in soil and microbial communities on the Qinghai–Tibet Plateau - Xinxin Wang; Quan Cao; Chunping Zhang; Wenting Liu; Xiaoxia Yang; Yuzhen Liu; Yang Yu; Caicai Sun; Haitao An; Kongtao Wei; Ze Zhou; Quanmin Dong (Agriculture, Ecosystems & Environment, 2026)

Divergent formation pathways of soil particulate and mineral-associated organic carbon across soil depths under conservation tillage - Hong-Xuan Duan; Yu-Gang Tian; Cheng-Ze Yang; Qing Luo; Yang Liu; Zhi-Yan Hou; Rattan Lal; Yash Pal Dang; Zhi Dong; Xin Zhao; Hai-Lin Zhang (Applied Soil Ecology, 2026)

Qianlong Shutong Formula alleviates benign prostatic hyperplasia associated with the regulation of inflammation, fibrosis and the Hippo-YAP/TAZ pathway - Ze-chao Zhang; Xue-jin Ye; Chang-jie Shang; Zhi-feng Wei; Yu Chen; Shu-ping Huang; Min Zhu; Bo-tao Tang; Tai-sheng Liang (Tissue and Cell, 2026)

Internal texture of debris-flow slurries revealed by multi-resolution CT scanning - Xiao Su; Ze-Min Xu; Yu Jiang; Yi-Xi Wen (Sedimentary Geology, 2026)

Revealing the biocontrol potential of endophytic bacteria isolated from wild soybean seeds against soybean gray leaf spot - Xiaoqing Yi; Mengyu Sun; Sixiang Wang; Qing Qu; Yue Zhao; Yuzhu Dong; Xuemei Li; Lanlan Wang; Chenxi Wang; Ruowen Mei; Cuimei Yu; Ze Wang; et al. (Physiological and Molecular Plant Pathology, 2026)

Effects of Hericium erinaceus powder incorporation on gluten interactions, water-state distribution, starch digestibility and quality characteristics of wheat noodles - Yu-Ling Yang; Chao Yang; Long Yang; Zhang-Jie Bi; Chang-Qing Dong; Xue-Bin Yin; Ze-Xuan Gong; Zhi-Peng Liu; Ke Bian (Food Research International, 2026)

Polymer-specific oxidative biotransformation of polyethylene and polypropylene microplastics by the stored-grain pest Tribolium castaneum - Sakhawat Shah; Jin-Ru Zhao; Ze-Yu Liu; Yi-Jia Chen; Jie Tang; Karam Khamis Elgizawy; Qiu-Ying Huang; Elvis Genbo Xu; Feng-Lian Yang (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Hierarchical transcription factor interaction network: RsrF mediates dual-layer regulation of plant-polysaccharide-degrading enzyme biosynthesis in fungus - Mei-Ling Pang; Wen-Tong Li; Ze-Yu Deng; Di Tian; Yan-Hao Zhao; Dian-Qi Wu; Xue-Mei Luo; Jia-Xun Feng; Shuai Zhao (Bioresource Technology, 2026)

Identification, characterization, and projection of meteorological and hydrological compound dry-wet events in Southeast China: A coupled VIC-CMIP6 framework for the Minjiang River Basin - Ze-Jia Li; Zi-Mei Yang; Zhen-Yu Zhang; Ying Chen; Xing-Wei Chen; Lu Gao; Hai-Jun Deng; Mei-Bing Liu (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Systematic review of naturally occurring benzylisoquinoline alkaloids (2015–2024): phytochemistry, bioactivity and structure-activity relationship - Jing Liu; Tao Liu; Mu-Yan Liu; Hui-Hui Li; Xiao-Yu Zhao; Hui Zhang; Yan Ge; Ze-Dong Nan (Phytochemistry, 2026)

The unintentional adverse effect of Fe3 + on trimethoprim adsorption at environmentally relevant concentration by extracellular polymeric substances - You Ma; Tian-Yu Li; Zi-Yi Fan; Han Meng; Guo-Xiang Wang; Fang Fang; Yu-Dong Chen; Run-Ze Xu; Wen-Ming Xie (Journal of Environmental Chemical Engineering, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

SNX8 interacts with THOC7 to negatively regulate IFN 1 response via the TBK1-IRF3 signaling axis in teleost fish - Miao-miao Li; Chu-xin Wu; Ji-huan Hu; Ting-ting Yu; Ze-yin Jiang; Hong-ying Zhang; Xun-hang Li; Cheng-yu Hu (Fish & Shellfish Immunology, 2026)

PFDA exposure promotes myocardial aging and fibrosis via hyperactivation of the MTORC1 signaling axis - Xiao Guang Chen; Ze Yu Liao; Yi Zhang; Ran Li (Food and Chemical Toxicology, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

Morphological engineering and valence state strategy enable stable nitrate-to-ammonia electroconversion at copper surface in the wide pH range - Yue-Han Qin; Xiao-Hui Wang; Ze-Nong Zhang; Shi-Bin Yin; Cong-Cong Han; Xuan Ai; Shu-Ni Li; Xin Wang; Yu Chen (Chemical Engineering Journal, 2026)

Indium selenide framework constructed from supertetrahedral clusters for efficient adsorption of Cs+ and Sr2+ - Fei-Fei Wang; Yu-Hang Li; Ze-Jia Shen; Ze-Yu Wang; Lin Cheng; Shuaihua Wang; Kai-Yao Wang (Chemical Engineering Journal, 2026)

Overcoming bacterial fouling: Self-cleaning CNTs-PEI/Cu-ZnIn2S4 membranes for sustained water disinfection - Yuan Gao; Jiaqi Sun; Pei-Lin Gao; Qi Zhao; Xinyi Yu; Yujie Song; Jun Hu; Dan Wang; Zhi-Gang Shen; Ze-Hai Xu; Hua Sheng; Zhong-Ting Hu (Chemical Engineering Journal, 2026)

High-performance biaxially oriented polylactic acid films enabled by long-chain branching: microstructural evolution and property tuning - Yu-Hang Zhang; Xing-Liang Li; Zheng-Ming Li; Ze-Yong Zhao; Xiu-Li Wang; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Rubberized Engineered/Strain-Hardening Geopolymer Composites (EGC/SHGC) with low fiber content to enhance strength and ductility efficiencies - Ze-Ming Yang; Zhi-Liang Zhang; Xi Jiang; Yu Xiang; Ling-Yu Xu; Bo-Tao Huang (Journal of Cleaner Production, 2026)

Single-cell multi-omics dissects transcript isoform and immune repertoire dynamics in human immunosenescence - Yuhui Zheng; Ze-Hui Ren; Yafei Yang; Wenteng Liu; Fupeng Li; Yajun Zuo; Tao Zeng; Xue Wang; Xiumei Lin; Xinyue Zhu; Baibing Guan; Wenwen Zhou; et al. (Science China Life Sciences, 2026)

BVDV hijacks the IDO1-dependent tryptophan–kynurenine axis to promote viral replication by limiting interferon–STAT1 antiviral signaling - Tian-yi Liu; Shan-shan Liu; Pei-long LI; Yong Zhou; Yu-xin Song; Wei-jia YAO; Ze-chen Zhang; Chong Zhao; Jiao LI; Lan-bo Tian; Nan LI; Yu Liu; et al. (Veterinary Microbiology, 2026)

Semi-Analytical Solution to 3D Tunneling Face Stability Considering Excess Pore Pressure - Yang Cheng; Zi-Xuan Cui; Ze-Hang Qian; Zhen-Yu Yin; Wan-Huan Zhou (Transportation Geotechnics, 2026)

Comprehensive assessment of soil health in typical pear orchards in Northwest China - Hongyu Yu; Zhibing Zheng; Bingyue Yu; Xin Wang; Ze Yuan; Kuan Xu; Chen Fu; Tianchi Jiang; Jiapan Lian; Pengfei Liu; Binggan Lou; Wolde tefera; et al. (Soil and Tillage Research, 2026)

Targeted isolation of previously undescribed fortunefuroic acid-type triterpenoids from Keteleeria pubescens using 1H NMR/LC-PDA-MS and assessment of ACL Inhibition - Chun-Jing Chi; Ze-Yu Zhao; Yi Zang; Cong Li; Jia Li; Dong Huang; Peng Sun; Juan Xiong; Yeun-Mun Choo; Jin-Feng Hu (Phytochemistry, 2026)

Synthesis of acid-resistant phenanthroline-skeleton polymers applicable to the PUREX process and exploration of their U(VI) adsorption mechanism - Ze-Yang Wang; Wei-Jia Wang; Xin-Long Chen; Xu-Xin Li; Feng Zhang; Ze-Yu Ren; Ze-Yi Yan (Journal of Hazardous Materials, 2026)

Synergistic engineering of oxygen vacancies and AuCu interface on ZnO for enhanced photocatalytic biomass valorization - Hao-Yu Chen; Wu-Dan Yang; Jie-Yang Dong; Ling-Bao Wu; Dan-Dan She; Ze-Kuan Zhang; Tian-Jun Gong; Qi Zhang; Yao Fu (Chemical Engineering Journal, 2026)

Hydrogen-bond disruption and interface adsorption-guided (002) deposition by DOL for highly reversible Zn anodes - Wenzhu Cao; Xue Dong; Xinyu Xie; Ting Zou; Ze Yang; Chenchen Wei; Yaran Shi; Ying Yu (Chemical Engineering Journal, 2026)

Size-dependent drought responses shape stand resilience of even-aged larch plantations in semi-humid northwest China - Jiamei Li; Pengtao Yu; Hongyan Liu; Xiaocha Wei; Bingbing Liu; Yanfang Wan; Zidong Li; Ze Zhang; Jinghua Qi (Agricultural and Forest Meteorology, 2026)

High-stability active thermal control for nanosatellite payload under multi-timescale disturbances via temperature response decomposition and energy-adaptive error fusion - Qi-Yuan Liu; Yun-Ze Li; Yan-Ao-Ming Xi; Kai-Feng Chang; Ya-Hui Chen; Ran Wei; Yu-Peng Zhou; Xin Zhao (Advances in Space Research, 2026)

Research on Multi-Scale Feature Extraction and Mineral Content Inversion in Elemental Logging Based on an Integrated RF-CNN-XGBoost Model - You-hai Sun; Zhong-jian Li; Yong-qiang Zhao; Ze-bin Gong; Yang Zhang; Shou-qing Zhang; Dan Yu (Applied Geophysics, 2026)

Investigation of In-Situ Shear Failure Mechanism of Rock and Acoustic Emission Characteristics Using Discrete Element Method - Long Chen; Jian-jun Huang; Ze Yang; Shun-chuan Wu; Shang-rong Wu; Yu-song Zhao (Applied Geophysics, 2026)

Silurian to Devonian A-type granitic magmatism in the East Kunlun orogenic belt: magma origin and geodynamic evolution - Bin Liu; Meng-Yu Zhang; Zheng Zhai; Nan Wu; Shi-Ze Li; Yang Sun (International Geology Review, 2026)

Model test study on instability of tunnel face affected by existing double circular tunnels - Xing-Tao Lin; Qi-Jia Wu; Hao Xiong; Dong Su; Ze-Yu Zhao; Xiangsheng Chen (Tunnelling and Underground Space Technology, 2026)

A future cornerstone for the cold archives in the artificial intelligence era: multidimensional optical data storage - Zi-Ting Liu; Shi-Jie Song; Xin Zhang; Guo-Hong Liu; Ke-Mi Xu; Qi-Dai Chen; Yu-Hao Lei; Zhen-Ze Li; Lei Wang (Science Bulletin, 2026)

8-epi-11-oxotanzawaic acid A, an undescribed tanzawaic acid analog from the marine fungus Penicillium citreonigrum - Ze-Qing Li; Rong Chao; Si-Yu Fang; Tian-Hua Zhong; Yuan Wang (Phytochemistry Letters, 2026)

GNPS-guided discovery of antifungal brominated metabolites from Chaetomium elatum FH-3 via NaBr-regulation and biotransformation - Jing-jing Su; Yin-han Teng; Bai-xue Yin; Hai-fang Wang; Yu-ze Li; Wei Wang; Xiao-mei Song; Dong-dong Zhang; Hao Fan (Phytochemistry Letters, 2026)

Green synthesis of a histidine-copper biomimetic enzyme for sustainable degradation of sulfamethoxazole in aquaculture wastewater - Yini Zhao; Long Cheng; Tao Yu; Long Gu; Xiangyi Zhang; Hangfei Gao; Zhicen Liu; Ze Fan; Ting Yan; Dongli Qin; Xinyue Zhao; Haijiao Xie; et al. (Journal of Environmental Chemical Engineering, 2026)

Antibacterial activity and mechanism of mangosteen extract garcinone D against Bacillus cereus - Ya-Ya Lei; Guan-Qiu Zhou; Yu-Chen Sun; Jin-Cheng Ma; Fu-Li Liu; Bao-Qi Zhang; Wen Zhang; Li-jing Zhang; Yan-Ze Wang; Ying-Qian Liu (International Journal of Food Microbiology, 2026)

A systematic evaluation of key ingredient functionality on thermal and textural properties of plant-based cheese analogues - Huey Yu Lee; Eldwin Ze Hao Ooi; Shi Cheng Tong; Camille Keisha Mahendra; Eng-Seng Chan; Yee-Ying Lee (Food Chemistry, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Seismic behavior and restoring force model of prefabricated T-shaped thin concrete-encased steel column with closed stirrups - Xiao-Wu Liu; Xue-Chun Liu; Xuesen Chen; Bing-Ze Li; Yu-Fei Yang (Engineering Structures, 2026)

Three-dimensional thermohaline reconstruction using deep learning from PIES observations and its application in mapping Kuroshio intrusion in the Luzon Strait - Hua Zheng; Chuanzheng Zhang; Zhao-Jun Liu; Ze-Nan Zhu; Kun Zhang; Xiao-Hua Zhu; Feng Nan; Fei Yu (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Phase-change-gated nanocapsules synchronize fungicide release and plant transport for wheat crown-rot control - Xiquan Ding; Yu Fang; Zheng Zhang; Dongyin Yi; Ze Lv; Yang Gao; Xinyu Guo; Yucheng Gu; Hongyan Zhang; Xuemin Wu; Rui Zhao; Yong Xu (Chemical Engineering Journal, 2026)

Low enthalpy 3D evaporators coupled with auxiliary thermal management for rapid solar evaporation - Ze-Ming Huang; Hong-Yu Chu; Ye-Tong Liu; Xiang-Jing Mo; Jing Li; Chong-Chen Wang; Peng Wang; Xiao-Hong Yi (Chemical Engineering Journal, 2026)

Combinatorial optimization strategy with three-tier constraints of multi-split air conditioners considering thermal comfort, energy cost, and low-carbon: A numerical investigation - Yan-Ao-Ming Xi; Hai-Hao Jiang; Zhen-Yu Li; Yun-Ze Li; Kai-Feng Chang; Ya-Hui Chen; Jia-Lu Xu; Xiao-Ya Si (Building and Environment, 2026)

A novel passive external surface heat flow balance strategy for high-temperature-stability nano CubeSat thermal design: concepts, models and thermal control effect evaluations - Yan-Ao-Ming Xi; Yun-Ze Li; Qi-Yuan Liu; Kai-Feng Chang; Xin Zhao; Yu-Peng Zhou; Ran Wei (Advances in Space Research, 2026)

Neuro-symbolic framework for multi-USV coordination: COLREGs-compliant and energy-efficient smart navigation - Shuai Huang; Yi-Feng Chen; Mao-Yuan Sun; Jia-Ning Gao; Yu-Han Zhou; Jing-Wen Zeng; Cheng-Chen Wang; Ya-Ze Han; Yang Xiong (Frontiers in Marine Science, 2026)
Introduction Coordinating multiple unmanned surface vehicles (USVs) in coastal waters requires simultaneous consideration of COLREGs compliance, real-time response, energy efficiency, fault tolerance, and semantic scene understanding. Existing approaches typically address only part of this problem and provide limited support for integrated fleet-level coordination. Methods This paper proposes NSC-Marine, a neuro-symbolic framework that conceptually addresses these coupled constraints. It combines multimodal causal perception, LLM-based rule reasoning, energy-aware motion planning, and distributed fault reconfiguration within a dual-rate control architecture. To improve deployment safety, semantic reasoning is used to generate structured constraints, while low-level motion execution remains under deterministic planning and control. Results The framework is evaluated strictly within a physics-based simulation environment with approximately 70% overall fidelity, involving 1,000 trials of 20–100 USVs under Beaufort Scale 3–5 conditions. Under these simulated conditions, NSC-Marine achieves 88.7% ± 2.3% COLREGs compliance, 82.3% mission success under compound faults, and 13.6% energy reduction relative to the RLCA baseline, while maintaining a 320 ms critical-path latency. Discussion These metrics reflect an idealized simulation baseline and must not be generalized to physical deployment readiness. Real-world performance remains unvalidated, and staged hardware-in-the-loop testing and field trials are required to characterize the system’s actual behavior under physical disturbances.

Ginsenosides mitigate multi-organ aging: mechanistic insights from a preclinical systematic review and meta-analysis - Ao Li; Hua-Ze Wu; Die-Yi Chen; Yu-Xin Gao; Xiao-Qiang Xiang; Qing-Hui He; Hong-Yan Ma; Dan Tang (Critical Reviews in Food Science and Nutrition, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

NPY-Y2R driven neuroimmune signaling as a potential therapeutic target for trigeminal neuralgia: clinical and experimental evidence - Zi-Le He; Chao Xu; Qi-Fan Yang; Cong-Zhou Han; Ting Wu; Yu-Qing Xu; Yun-Ze Liu; Liang-Yu Ni; Si-Qi Jia; Tang-Yu Zhang; Yun Wang; Yi Feng (Science Bulletin, 2026)

A novel integrated degree of cyclostationarity indicator for gear micro-pitting monitoring of offshore wind turbines under marine non-Gaussian impulsive noise - Tianlin Yu; Hanbin Zhou; Zilin Zhang; Tingyu Qian; Qiji Ze; Qing Ni; Jun Luo; Ke Feng (Ocean Engineering, 2026)

Electron‑flow‑driven synergistic mineralization of naphthalene by an S‑N‑doped biochar‑bridged engineered consortium - Fuliang Bai; Chao Yang; Ze Yu; Zeya Wu; MingXia Sun (Journal of Hazardous Materials, 2026)

Deciphering the microbial and physicochemical pathways of biochar-based fertilizer in driving resource-use efficiency: A comparative study of two contrasting acidic soils - Yulin Chen; Ze Yu; Song Peng; Taowen Pan; Lansheng Deng; Kunzheng Cai (Journal of Environmental Management, 2026)

Dietary succinic acid supplementation enhances the growth performance and immunity of abalone Haliotis discus hannai - Ze Zhang; Zhenhua Wu; Xiaojun Yu; Tingting Fang; Ziqian Han; Yongqing Liu; Yang Liu; Kangsen Mai; Wenbing Zhang (Fish & Shellfish Immunology, 2026)

Axial compression behavior of corroded steel angles: Experiment, parametric analysis and design method - Jing-Zhou Zhang; Ze-Zhen Zheng; Ping Tan; Zhi-Wei Yu; Wei Bao (Engineering Structures, 2026)

Creation of intermuscular bone-free genetic mutants in grass carp and multiomics reveals molecular regulatory basis - Jun-Qi Liu; Chun-Hong Nie; Zheng-Yin Wang; Yue Yu; Dong-Yang Zhang; Jian Wang; Xue-Qiao Qian; Shi-Ming Wan; Ze-Xia Gao (Science China Life Sciences, 2026)

Research on initial external solution curing technology to enhance durability of cement mortars and chemical deposit infilling mechanism - Jinbo Yang; Yu Zhang; Ze Zhang (Innovative Infrastructure Solutions, 2026)

Deciphering RNA modification dynamics during spermatogenesis and sperm maturation - Zheng Cao; Zongyu Yu; Xin Wang; Dongqi Jiang; Yafei Yuan; Ze Shu; Yiting Yang; Yunfang Zhang (Science China Life Sciences, 2026)

High-efficiency micropropagation of Rhodiola species with concurrent bioactive compound validation - Cheng-cai Zhang; Xiang-tao Chen; Hong-yang Wang; Wei-wu Chen; Jiumi Ciwang; Xiao-yu Dai; Ya-fei Zhang; Qi Li; Sheng Wang; Ze-kun Zhang (In Vitro Cellular & Developmental Biology - Plant, 2026)

Influence of Fracture Geometry Parameters on the Mechanical Properties and Spatiotemporal Crack Evolution in Granite: Insights from Integrated AE and DIC Monitoring - Xiangyu Wang; Lei Zhang; Defu Zhu; Chunwang Zhang; Ze Wang; Zhenting Lv; Chengke Yang; Yu Zhang (Rock Mechanics and Rock Engineering, 2026)

Phytochemical and biological studies on rare and endangered plants endemic to China. Part XLIX. Terpenoids and phenylpropanoid-substituted flavan-3-ols from the leaves of Camellia petelotii (golden-flower tea) and their bioactivities - Ze-Yu Zhao; Can Wang; Zhe-Lu Jiang; Jiang Wan; Juan Xiong; Yi Zang; Yeun-Mun Choo; Jia Li; Jin-Feng Hu (Phytochemistry, 2026)

Beyond performance-cost trade-off: Engineered Geopolymer Composites (EGC) incorporating ultra-high-volume coal gangue wastes - Zhi-Liang Zhang; Ze-Ming Yang; Ling-Yu Xu; Jian-Cong Lao; Hui Zhang; Yu-Jie Huang; Linghua Shen; Dan-Dan Shi; Bo-Tao Huang (Journal of Cleaner Production, 2026)

Biochar aging-driven cadmium release in paddy soils: Mechanistic insights into adsorption capacity loss and biochar feedstock-specific risks - Ze-ning Yu; Xiao-qing Zhang; Fei-mei Chen; Rong-liang Qiu; Kuan Zhou; Xin-xian Long (Journal of Environmental Sciences, 2026)

Finite-strain modelling of PVD-assisted consolidation in clayey soils using a novel elastic–viscoplastic model with destructuration based on the equivalent time concept - Peng-Lin Li; Zhen-Yu Yin; Ze-Jian Chen; Jian-Hua Yin (Geotextiles and Geomembranes, 2026)

Unraveling flavor evolution in beef: the impact of aging methods and duration on precursors and volatile compounds - Silu Ze; Qianqian Liu; Xiangku Ye; Rongxin Wen; Chengfeng Sun; Qianqian Yu (Food Chemistry, 2026)

Synthesis of Cu-embedded carbon composites via in situ CNTs growth for efficient liquid iodine capture - Xin-Tong Jiang; Yu Liu; Yi Xin; Ze-Peng Li; Xiao-Yu Zhu; Xiao-Sa Zhang; Wen-Ze Li; Jian Luan (Environmental Research, 2026)

Reshaping global energy security: Implications of embodied energy transfers in global supply chains - Yannan Zhou; Ying Lu; Yu Yang; Yan Cheng; Ze He; Yuxin Wang; Yuli Shan (Energy Policy, 2026)

DeepLrn-Source: Deep learning powered landslide source identification - Lu-Yu Ju; Ze-Ning Zhao; Shi-Hao Xiao; Yuan-En Pang; Jian He; Yun-Hong Lv; Ruo-Chen Jiang; Xin He; Li-Min Zhang (Engineering Geology, 2026)

Benzotriazole ultraviolet stabilizers impair trophoblast function at nanomolar concentrations via GPER signaling: implications for placental health - Ze-Pei Zhao; Shi-Ye Zhu; Ying-Huang Hu; Yu-Ke Wan; Shang-Jun Xu; Jie-Zhi Ma; Deng-Ni Lai; An-Wei Chen; Yuan Yang; Lin Luo; Lin-Ying Cao (Chemico-Biological Interactions, 2026)

Salinity decrease leads to recovery of filamentous bacterial bulking in moderately halophilic aerobic granules: Unraveling the role of fungi - Ze-You Lu; You-Wei Cui; Ya-Nan Mi; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Jia-Ying Li (Bioresource Technology, 2026)

Chemical constituents from the roots of Rubus crataegifolius Bunge and their chemotaxonomic significance - Wei Liu; Yu-Li Zhang; Piao Yan; Ze Wu; Meng-Wei Gao; Shuo Tian; Ren-Bo An; Li-Li Jin (Biochemical Systematics and Ecology, 2026)

Pain-Affective Disorder Comorbidity in the Temporomandibular Disorders: From Mechanistic Insights to Clinical Management - Zhaoyichun Zhang; Shibin Yu; Shengxi Wu; Zuolin Jin; Ze Fan; Jing Huang (Neuroscience Bulletin, 2026)

Multiscale oceanic response to Typhoon Noru (2022) in the South China Sea: modulation by submesoscale processes - Dongmei Shen; Guoqing Han; Peiyu Liang; Jinyu Cai; Juncheng Xie; Peng Bai; Ze Meng; Yu Liu (Frontiers in Marine Science, 2026)
A comprehensive understanding of the upper-ocean response to typhoons is critical for improving typhoon intensity prediction. Although background mesoscale environments modulate the upper ocean, how submesoscale dynamics specifically drive the three-dimensional reshaping of the post-typhoon wake remains unclear. Our study employs a one-way nested model configuration (9 km parent grid and 3 km child grid) to examine the multiscale oceanic response to Typhoon Noru (2022) within the frontogenetic Vietnam Offshore Current region of the South China Sea. Mixed-layer heat budget analysis revealed that wind-driven vertical mixing primarily governed the forced-stage cooling magnitude, regardless of model resolution. However, the thermal evolution within the post-typhoon cold wake exhibited a pronounced contrast between the two resolutions. Spatial scale decomposition confirmed that the enhanced fine-scale thermal variability was primarily driven by submesoscale flows advecting background temperature gradients. Furthermore, the high-resolution simulation successfully resolved coherent ageostrophic secondary circulations along these submesoscale fronts. These localized overturning motions produced a persistent positive vertical buoyancy flux that slumped horizontal density fronts, thereby driving rapid restratification. These fine-scale vertical exchanges effectively transported warm surface water downward, governing the thermal restructuring within the post-typhoon cold wake. The findings highlight the importance of resolving submesoscale dynamics and provide a critical dynamical basis for improving sub-grid parameterizations of vertical transport in coupled prediction models.

Involvement of cytochrome P450 gene CYP333B119v2 in the resistance of Cydia pomonella to lambda-cyhalothrin - Yu-Ze Li; Chao Hu; Yu-Xi Liu; Yun-Tong Lv; Xue-Qing Yang (Pesticide Biochemistry and Physiology, 2026)

Tracking high-field-strength-element enrichment pathways in alkaline granites: Insights from potassium and barium isotopes - Hao-Cheng Yu; Zheng-Yu Long; A.E. Williams-Jones; Ralf Halama; Frédéric Moynier; Shan-Shan Li; Ming-Qian Wu; Hao-Ran Duan; Jia-Dong Ma; Nan Ju; Ze-Zhou Wang; Kun-Feng Qiu (Geochimica et Cosmochimica Acta, 2026)

Forage-driven rumen microbiome-metabolome axis shapes meat quality in Tibetan sheep: Unveiling the regulatory potential of CAZymes and plant-derived bioactive metabolites - Kongtao Wei; Chunping Zhang; Ze Zhou; Xue Zhang; Xin Liu; Yang Yu; Zhengshe Zhang; Quan Cao; Quanmin Dong (Food Research International, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

Acute triclosan exposure induces multidimensional toxicity in zebrafish larvae: Disruption of development, behavior, immune function, and cell death mechanisms - Xiao-Yu Wang; Yong Tao; Shi-Lin Du; Hong Wu; Hong-Yi Liang; Ya-Hui Zhang; Ting-Ting Ding; Ze-Jun Wang (Aquatic Toxicology, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

A mixed-fluid genetic model for the baiceng fluorite deposit, SW China: Deciphering the magmatic thermal driver and basinal fluid sources - Xi-Wen Zhang; Zhong-guo Jin; Ming-hong Zheng; Jun Chen; Ze-liang Yu; Long Luo; Yong-hu Su; Lin Ye; Yan-wen Tang; Min-shan Gun (Earth Science Informatics, 2026)

Nitrogen inhibitors enhance ecosystem multifunctionality through microbial networks in alpine grasslands of the Tibetan Plateau - Fang-Kun Yang; Peng-Yang Wang; Ze-Yang Liu; Fu-Ying Niu; Cheng-Yi Xie; Yi-Ming Gao; Yan-Mei Ma; Yu-Xing Wang; Jia-Cheng Guo; Wen-Ying Wang (Applied Soil Ecology, 2026)

Efficient Blank Filling Method for Electrical Imaging Based on the HR-FFC Algorithm - Jun-lei Su; Xu Dong; Ze-yi Jia; Yu Zeng; Xue-ying Shi; Jin-ku Dai (Applied Geophysics, 2026)

The emerging role of high-throughput proteomics in advancing precision medicine - Jia You; Yue-Ting Deng; Luo Chen; Lin-Bo Wang; Yu Guo; Ze-Yu Li; Jian-Feng Feng; Jin-Tai Yu; Wei Cheng (Science Bulletin, 2026)

Autoregressive dual latent space VAE for fault detection in multi-rate industrial processes - Yu Sun; Yuqing Chang; Xiaojing Li; Ze Ying (Process Safety and Environmental Protection, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

Smarter brains, greener cities? Unveiling the spatial effects of computational power on sustainable development - Qihai Cai; Ze Yu; Fangxin Jiang (Journal of Cleaner Production, 2026)

Integrating Raman spectroscopy and interpretable deep learning: A multimodal approach for plastic material identification - Ze Wang; Dengcai Zhao; Jiaxin Hu; Yuan Liu; Feifei Xu; Li Liu; Shuwen Yu (Journal of Environmental Chemical Engineering, 2026)

Wet milled municipal solid waste incineration fly ash: reagent free immobilization of heavy metals and evaluation as a low carbon supplementary cementitious material - Yu Gao; Ze Liu; Shuaiyun Wen; Xin Zhang (Journal of Cleaner Production, 2026)

Synergistic enhancement of electrochemical performances via PDA/Fe3O4 modified anodes and amino acid-mediated bioelectrocatalysis of biomineralization in marine sediment microbial fuel cells - Lin-Meng Wang; Li-Ze Huangfu; Yi Yang; Yan Chen; Yu-Bin Fu (Journal of Environmental Chemical Engineering, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Numerical analysis of autothermal microchannel reactors for ammonia decomposition: Roles of material and channel architecture - Zu-Guo Shen; Ze-Ping Weng; Yu Wang (Chemical Engineering Journal, 2026)

Plant–microbe interactions underpin contrasting enzymatic responses to flooding intensity variation in the cascade reservoir riparian areas - Nan-ping Wu; Shan-ze Li; Kailang Yin; Yu-chun Wang; Zheng Sun; Xuming Xu; Qingkong Chen; Yufei Bao; Jie Wen (CATENA, 2026)

Vascular plant encroachment drives soil carbon loss and microbial assembly shifts across a successional gradient in a subtropical Sphagnum-dominated peatland - Meng-Jie Yu; Ting Wang; Jia-Peng Wang; Ze-Dong Lang; Zhi-Yi Zhao; Jing-Yan Hu; Yi-Yue Wang; Yu-Huan Wu (Soil Ecology Letters, 2026)

Multiscale heat budget analysis of upper ocean responses to Typhoon Kalmaegi (2014) in the South China Sea - Jinyu Cai; Juncheng Xie; Ze Meng; Guoqing Han; Peng Bai; Yu Liu (Acta Oceanologica Sinica, 2026)

Study on GPR Forward Modeling and Intelligent Identification of Subgrade Defects Characterized by Hidden Voids - Bin Wu; Yan-li Qi; Qi-guang Cheng; Fan-meng Kong; Yu-xuan Han; Yiguo Xue; Yue-hua Wu; Sheng-yong Dong; Ze-zhou Kang; Zhe Zhang; Yong-feng Shi; Min Han (Applied Geophysics, 2026)

Effects of alfalfa as a substitute for dietary kelp on the growth, appetite, digestion, intestine histology, and immunity of abalone Haliotis discus hannai - Yongqing Liu; Zhenhua Wu; Xiaojun Yu; Ze Zhang; Tingting Fang; Yang Liu; Ziqian Han; Kangsen Mai; Wenbing Zhang (Aquaculture International, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Petrogenesis of Triassic crystal-rich and crystal-poor volcanic rocks in the East Kunlun orogenic belt: Evidence from in-situ zircon-apatite-quartz and whole-rock geochemical compositions - Meng-Yu Zhang; Bin Liu; Chang-Qian Ma; Zhen-Hua Xue; Yang Sun; Yan-Qing Li; Yao-Yao Zhang; Luan Wu; Shi-Ze Li (Lithos, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

Mechanistic insights into structural evolution of goji berry (Lycium barbarum L.) during pulsed vacuum drying procedure via moisture migration and cell wall polysaccharide transformations - An-An Zhang; Li-Zhen Deng; Long Xie; Ze-Kang Peng; Ming-Qiang Xu; Wan-Liang Hao; Yu-Hao Jiang; Wen-Bin Ze; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Conservation mulching with plastic film in maize field of arid irrigation region: Agronomic performance, economic, and environmental effects - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Xiao-Yu Lu; Ying Zhu; Meng Hao; Ning Wang; Meng-Ying Li; Xiao-Feng Zhang; Hong-Yan Tao; You-Cai Xiong (Field Crops Research, 2026)

Thermal-mechanical coupled vibration characteristics of a rotating FGP-GNPRC stepped cylindrical shell in nonlinear thermal environment - Ziyi Wang; Hui Li; Yufeng Chang; Qingpeng Han; Ze Jian; Yu Wang; Libo Cai (Engineering Structures, 2026)

GaAs/GaN-based self-powered catalytic systems driven by tribovoltaic effect enable efficient degradation of azo dyes - Meng-Nan Liu; Yan-Xin Wu; Yu-Tong Sun; Xu Li; Ru Li; Jun Zhang; Yun-Ze Long (Chemical Engineering Journal, 2026)

Unlocking enhanced capacity and stability: Interlayer polymerization of PEDOT on NH4V4O10 micron-flowers for zinc-ion batteries - Xiaoqing Liu; Ze Xu; Ruimiao Si; Mengmeng Bai; Shun Zhou; Lixin Zhang; Chuang Yu; Liping Li; Youzhi Liu (Chemical Engineering Journal, 2026)

Correction to: Genetic Mapping of the Wheat Dimeric α-Amylase Inhibitor Multi-Gene Family Using Allele-Specific Primers Based on Intergenomic SNPs - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Plant Molecular Biology Reporter, 2026)

Nr4a2, A Key Factor Controlling the Development and Functional Maintenance of Forebrain Car3 Neurons - Yun-Chao Tao; Li Zhao; Qiong Zhang; Xi-Yue Liu; Wei-Tang Liu; Ze-Xuan Li; Ling Hu; Lei Zhang; Jia-Yin Chen; Yu-Qiang Ding; Ning-Ning Song (Neuroscience Bulletin, 2026)
Nr4a2 ( Nurr1 ) is well known to be vital for midbrain dopaminergic neurons. Recent single-cell RNA analyses reveal that Nr4a2 is expressed in lateral cerebral regions, within neurons named L4/L5/L6 IT Car3 . These neurons have attracted intense attention for the molecular mechanisms underlying their development and functions. We classified Car3 neurons into neocortical (Ncx- Car3 ), claustral (CLA- Car3 ), and dorsal endopiriform nucleus (dEn- Car3 ) subpopulations, focusing on the characterization of Ncx- Car3 neurons. These neurons exhibit distinct birthdates and migratory morphologies compared to CLA- and dEn- Car3 neurons, but share a common transcriptomic profile when Nr4a2 is deleted at the embryonic stage or in adulthood. Notably, Nr4a2 misexpression ectopically induces Car3 -enriched genes in vivo . Mice lacking Nr4a2 in Car3 ensembles during the embryonic stage or in adulthood display hyperactivity and reduced anxiety-like behaviors. Therefore, our results demonstrate that Nr4a2 is a key factor in regulating the development and functional maintenance of the forebrain Car3 neurons.

Host-associated volatile cues drive foraging behavior of Trichopria drosophilae toward Drosophila suzukii-infested fruits - Hai-Kuan Sun; Fan Yang; Ze-Hua Wang; Ren Li; Guang-Hang Qiao; Qiu-Fei Li; Yu-Yu Wang; Shan-Ning Wang (Journal of Pest Science, 2026)

Performance and mechanism of low-temperature domestic sewage treatment by innovative composite ceramsite enhanced biological aerated filter - Xu Wang; Xiao-man Wang; Qing-miao Yu; Ze-tong Shen; Jin-ju Geng (Journal of Water Process Engineering, 2026)

Solvent-mediated construction of phosphate/carboxyl bifunctional hyper-cross-linked polymers for highly efficient uranium removal from aqueous solutions - Ze-Yang Wang; Xin-Long Chen; Xu-Xin Li; Feng Zhang; Wei-Jia Wang; Ze-Yu Ren; Yang Li; Ze-Yi Yan (Journal of Hazardous Materials, 2026)

Investigation on storage space variation characteristics of basalt induced by CO2 mineralization using hydrothermal experiments - Xuguang Dai; Ze Zhou; Meng Wang; Xiaofei Liu; Xiaoran Wang; Sijian Zheng; Chongtao Wei; Yu Song; Guangjun Feng; Shuxun Sang; Weimin Kong; Xuan Shi; et al. (Journal of Environmental Chemical Engineering, 2026)

Structural alignment of PAH in vitrinite-rich anthracite and its impact on methane adsorption - Liu Hanlin; Zou Caineng; Shen Zhen; Veerle Vandeginste; Zhao Qun; Chen Yanpeng; Deng Ze; Feng Guangjun; Zheng Sijian; Shan Deke; Song Yu (Fuel, 2026)

Response mechanisms of abalone Haliotis discus hannai to lead (Pb) exposure in vitro: insights into autophagy, endoplasmic reticulum stress and apoptosis - Yue Liu; Dong Huang; Mingzhu Pan; Xinxin Li; Gaochan Qin; Xiaojun Yu; Ze Zhang; Kangsen Mai; Wenbing Zhang (Fish & Shellfish Immunology, 2026)

Research on the impact of resident behavior on energy consumption during the heating period of ultra-low energy buildings - Ru-Xi Ding; Jia-Ze Dai; Ying-Nan Zhang; Xiao-Ping Wu; Cong-Han Yu; Zhenfa Fan (Energy and Buildings, 2026)

Pivotal effect of oxygen vacancies on S-scheme BiVO4/g-C3N4: Novel dual activation mechanistic studies in photocatalytic selective ethylbenzene oxidation under LED irradiation - Wen-Yu Luo; Ze-Lin Wang; Peng-Jiang Chao; Ying-Ying Xu; Yanfei Xu; Zhuo Li; Lin-Yu Jiao; Mingyue Ding (Chemical Engineering Journal, 2026)

A polypyrrole-based ultrastable monolithic supercapacitor for medical implants - Jiawei Li; Mahmoud Rouabhia; Chongwen Yu; Jifu Mao; Ze Zhang (Chemical Engineering Journal, 2026)

Closed-loop recycling and recovery of vanadium cathodes from waste aqueous zinc-ion batteries - Hsing-Kai Tseng; Jun-An Su; I-Mao Chen; Yu-Ze Chen; Jun-Yi Wu; Pin-Han Chen; Fan-Wei Liu (Chemical Engineering Journal, 2026)

Interpenetrated hierarchical polyzwitterionic hydrogels promote decellularized small-diameter vascular grafts regeneration - Qi-Ying Wu; Chun-Yang Chen; Jin-Chang Li; Ze-Guo Chen; Si-Cheng Chen; Chao Xie; Si-Xi Liu; Zi-Han Liu; Zhong-Shi Wu; Yu-Hong Liu (Chemical Engineering Journal, 2026)

Interactions of Carbon Fixation, Glucose Metabolism, and Stress Tolerance are Associated with Sugarcane Ripening - Ke-Wei Ou; Ting Luo; Ze-Mei Nong; Quan-Guang Zhou; Ping Lv; Yu Zhang; Xin-Hua Pang; Ye-Fei Lu (Sugar Tech, 2026)
High sucrose content is a crucial breeding objective in sugarcane, with significant differences in sucrose accumulation patterns between early and late-maturing varieties during different growth stages. This study aimed to determine how differences in cane maturation affect proteins involved in sucrose metabolism. The isobaric tags for relative and absolute quantitation (iTRAQ) technique was employed to analyze intraspecific and interspecific proteomic differences between the early-maturing sugarcane variety ‘GL05-136’ and the late-maturing variety ‘GR2’ during the maturation period (January and February). A total of 3337 proteins were identified. Gene Ontology, Kyoto Encyclopedia of Genes and Genomes (KEGG), and Clusters of Orthologous Genes analysis found that the differential proteins were mainly associated with metabolic processes, single biological processes, and cellular processes. A total of 47 differential proteins were identified in the four comparison groups (intra-variety temporal comparisons and inter-variety synchronous comparisons), 17 of which were enriched in a KEGG pathway, including glucose metabolism, stress resistance, and photosynthesis pathways. The differential proteins fructose-bisphosphate aldolase and disulfide isomerase were obtained after further screening of the contrast groups between varieties. These two proteins may be associated with differential cane maturation, sucrose synthesis and accumulation in sugarcane. These results provide more insights on sucrose accumulation and stalk maturation in sugarcane varieties.

Impacts of Sargassum hemiphyllum substitution for dietary kelp meal on the growth performance, muscle texture and immunity of abalone (Haliotis discus hannai) - Ziqian Han; Gaochan Qin; Zhenhua Wu; Xiaojun Yu; Ze Zhang; Tingting Fang; Yongqing Liu; Yang Liu; Kangsen Mai; Wenbing Zhang (Journal of Applied Phycology, 2026)

Transcriptome and DNA methylation responses in the liver of Megalobrama amblycephala under hypoxia and heat stress - Kang Chen; Pei-Yu Xie; Hong Liu; Ze-Xia Gao; Huan-Ling Wang (Fish Physiology and Biochemistry, 2026)

Dynamic health risk assessment of chromium exposure in soil and groundwater at tannery sites: a Bayesian network perspective - Shan-shan Guo; Yu Wang; Yong qiang Tian; Hao Wu; Yang Li; Xiao dan Jin; Xin Li; Ze-lin Zhou; Han Zhang; Jin-yan Yang (Environmental Geochemistry and Health, 2026)

Decade of natural regeneration increases carbon accumulation in a drained peatland pasture - Yu Gong; Mei Wang; Feng Sun; Jianghua Wu; Kunshan Bao; Ze Ren; Faming Wang (Agriculture, Ecosystems & Environment, 2026)

Spatiotemporal Characteristics and Long-Term Variability of Large-Wave Frequency in the Northwest Pacific - Zhen-Yu Zhao; Hong-Ze Leng; Yu-Han Wei; Jin-Hui Yang; Xuan Zhou; Ze-Zheng Zhao; Hui-Peng Wang; Bao-Xu Li; Wu-Xin Wang; Jun-Qiang Song (Journal of Marine Science and Engineering, 2026)
This study provides a systematic analysis of the spatiotemporal distribution and trends in the frequency of significant wave height (SWH) exceeding level 5 (SWH > 2.5 m) and level 7 (SWH > 6 m) in the Northwest Pacific (NWP) for 1993–2024, which are defined as f5 and f7, respectively, as well as their correlations with major climate indexes. Our results indicate that (1) the high-value zones for the annual mean f5 and f7 are both located in the south waters of the Aleutian Islands, with maximum values of 58.0% and 6.4%, respectively. Winter’s contribution is greatest (maximum values of 96.9% and 16.8% per year), while summer’s is the smallest. (2) f5 exhibits a significant decline trend across the entire NWP basin (of −0.15 to −0.30%/yr), with the steepest decline occurring in autumn (−0.69%/yr) and the shallowest in summer. f7 exhibits a significant linear decrease in the open ocean east of Japan (−0.08%/yr) while showing a significant linear increase in the waters east of the Kamchatka Peninsula (0.08%/yr). Both variations peak in winter (maximum values of −0.27% and 0.30% per year) and are smallest in summer. (3) Seasonal and regional variations in climate index–f5 and f7 relationships reflect large-scale atmospheric modulation of waves. For example, the Oceanic Niño Index shows a predominantly negative correlation with f5 in winter (maximum correlation coefficient rm = −0.70) around the Luzon Strait, shifting to a significant positive correlation in summer (rm = 0.70) across the extensive region east of Taiwan Island and the Philippines. The Pacific Decadal Oscillation index shows a significant positive correlation with f7 in summer and autumn (rm = 0.69) east of Taiwan Island and a strong negative correlation in winter (rm = −0.77) to the east of Kamchatka Peninsula.

Measuring grazing grassland aboveground biomass and spatial heterogeneity based on UAV LiDAR observation with upscaling samples - Yu-Qing Wu; Li-Biao Guo; Wei-Xian Tan; Ping-Ping Huang; Ming-Ze Ma; Yang Zhao (International Journal of Remote Sensing, 2026)

Adaptability and stress response mechanisms of abalone Haliotis discus hannai to cadmium in vitro and in vivo - Yue Liu; Dong Huang; Mingzhu Pan; Xinxin Li; Gaochan Qin; Xiaojun Yu; Zhenhua Wu; Ze Zhang; Kangsen Mai; Wenbing Zhang (Aquaculture, 2026)

Caspase-3 plays a pivotal role in Acinetobacter johnsonii-induced pyroptosis of black rockfish (Sebastes schlegelii) lymphocytes - Xuangang Wang; Fan Zhang; Qiannan Chen; Zhixiang Duan; Hengshun Li; Ze Tao; Xiangfu Kong; Quanqi Zhang; Haiyang Yu (Aquaculture, 2026)

Evaluations on the regulation of resveratrol on the growth performance, anti-oxidation, immunity, heat tolerance and resistance to Vibrio parahaemolyticus of abalone Haliotis discus hannai - Xiaojun Yu; Zhenhua Wu; Ze Zhang; Tingting Fang; Ziqian Han; Yongqing Liu; Yang Liu; Kangsen Mai; Wenbing Zhang (Aquaculture, 2026)

Lanthanum-quaternized chitosan-modified zeolite for long-lasting operation of constructed wetland: A bifunctional strategy for simultaneous phosphorus removal and microbial clogging mitigation - Ling Wang; Jian-Guo Zhang; Hong-Yin Sha; Yi-Ru Wang; Hao-Yu Wang; Guang-Can Zhu; Yong-Ze Lu (Water Research, 2026)

Experimental study on failure mechanism of tunnel face during shield tunneling beneath existing underground rectangular structure - Xing-Tao Lin; Qi-Jia Wu; Liqiang Cao; Ze-Yu Zhao; Dong Su; Xiangsheng Chen (Tunnelling and Underground Space Technology, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

Microscopic characteristics and gas generation patterns of spontaneous combustion oxidation in deep high-temperature coal seams of the Juye mining area - Li-Feng Ren; Xin Yu; Jing-Bo Li; Qing-Wei Li; Xian-Ze Kong; Xiao-Wei Zhai; Teng Ma; Zong-Qing Tang (Fuel, 2026)

From immunity to table quality: The dual role of oleic acid in Litopenaeus vannamei aquaculture - Ze-Yu Jin; Jin-Meng Cai; Ge Zhao; Wen-Jie Li; Hao Yu; Hong-Wei Zhang; Xiao-Wen Zhang (Food Chemistry, 2026)

Amplifying 2′3′-cGAMP with “open source throttling” strategy: Intelligent nanoreactors enhance immunotherapy in HNSCC via cascade activation of the cGAS-STING pathway - Tong Sha; Ze Wang; Jinwei Li; Yahong Wu; Xiaoyi Yu; Jinbiao Qiang; Annan Liu; Hao Liang; Zunxuan Xie; Yijun Zhou; Hongchen Sun; Andrew K. Whittaker; et al. (Chemical Engineering Journal, 2026)

A self-adaptive interfacial adhesive strategy for enduring flame retardancy and aging resistance of anti-aging agent-free polyurethane foam - Yan Wang; Lei He; Heng-Fei Liang; Chen Ye; Ze-Yong Zhao; Ming-Jun Chen; Yu-Zhong Wang; Hai-Bo Zhao; Cong Deng (Chemical Engineering Journal, 2026)

Hyperbranched polyamine-graft-poly(ε-caprolactone) with integrated flame retardancy, plasticization, and filler-dispersion functions toward high-performance poly(vinyl chloride) plastics - Xing-Hao Wang; Liang Yang; Jing Zhao; Ze-Zhong Lin; Dan-Dan Shi; Yu Chen; Pei-Yao Chen (Chemical Engineering Journal, 2026)

Electrically insulating BNNS/PVDF@AlN/PVP composites with simultaneously enhanced in-plane and through-plane thermal conductivities - Wei-Hua Han; Yaping Fan; Yu Long; Bin Sun; Yun-Ze Long; Chun-Cheng Hao (Chemical Engineering Journal, 2026)

Composite hydrogel microspheres modulate intestinal inflammation via releasing HA modified liposomes@4-OI targeting M1 macrophages - Shuanghong Yang; Ze Li; Guiwen Qu; Liting Deng; Liuqing Dou; Sicheng Li; Yitian Teng; Luqiao Huang; Haohui Li; Kang Chen; Jinpeng Zhang; Rui Ma; et al. (Chemical Engineering Journal, 2026)

Double-network-inspired polymer interphase with fast kinetics for stable zinc-metal anodes - Xue Dong; Ze Yang; Chenchen Wei; Zhixuan Huang; Zhouzhou Wang; Chunchun Wang; Yaran Shi; Libing Zhu; Zhihong Zhu; Ying Yu (Chemical Engineering Journal, 2026)

Soil moisture dynamics and rainfall infiltration across vegetation types in subtropical ecosystems in Southwest China - Qiao-Shun Yan; Yu-Xi Peng; Xiao-Jin Jiang; Pei-Li Fu; Zhi-Yun Lu; Xiao-Wen Hu; Yong-Jiang Zhang; Jiao-Lin Zhang; Ze-Xin Fan (CATENA, 2026)

Chemical constituents from the endangered tertiary relict conifer Pseudotaxus chienii (W. C. Cheng) W. C. Cheng and their chemotaxonomic significance - Jin-Xin Zhu; Ze-Yu Zhao; Chi Song; Juan Xiong; Jin-Feng Hu (Biochemical Systematics and Ecology, 2026)

Hexadecyltrimethylammonium-modified bentonite for enhanced adsorption of per- and polyfluoroalkyl substances: Experiment and thermodynamic mechanism - Ze-Wei Ke; Yu-Xin Liu; Sheng-Jie Wei; Peng Shen; Kun Yang; Yun-Min Chen; Yu-Chao Li (Applied Clay Science, 2026)

Diversity and seasonal dynamics of parasitoid communities sustaining biocontrol of citrus leafminer moth Phyllocnistis citrella - Xin-Yi Chen; Yu-Tong Zhou; Pei-Ping Xu; Ze-Yun Fan; Li-He Zhang; Guillaume Nyagatare; Bao-Li Qiu (Biodiversity and Conservation, 2026)

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

Seasonal dynamics and source attribution of dissolved organic carbon in a representative river-reservoir system in plateau regions - Ze Yu Xiao; Chen Li; Wei Wu; Lei Ren; Hang Chen; Sheng Xu (Chemosphere, 2025)

GAS1 affects proliferation, apoptosis, and steroid hormone levels by regulating mitochondrial functions and the PI3K/AKT pathway in bovine granulosa cells - Wenjie Yu; Na Pei; Haitao Jia; Yijing Yin; Hong Xu; Tian Tian; Chang Liu; Lingxia Xu; Ze Li; Zibin Liu; Xiaoshi Cai; Mingkai Yu; et al. (Theriogenology, 2025)

Recycled oceanic crust restricting trace element enrichment in mid-ocean ridge basalts - Fan Yang; Xiao-Long Huang; Yi-Gang Xu; Yang Yu; Peng-Li He; Le Zhang; Ze-Xian Cui (Lithos, 2025)

A new risk for the recovered Tibetan antelope (Pantholops hodgsonii): Co-exposure of microplastics with organophosphates in their habitats - Rui Guo; Caian He; Jian Sun; Shaohua Li; Chuntao Zhao; Zhiyong Ling; Liang Chen; Wenrui Zhang; Jingmeng Li; Bing Wang; Jufang Hu; Dongmei Yu; et al. (Journal of Hazardous Materials, 2025)

Dual-responsive carboxymethyl cellulose-based hydrogel sensor with antibacterial activity for wound monitoring and infected wound repair - Zhengjie Yu; Fanwei Zeng; Yuejin Cai; Zijie Wang; Ze Chen; Ruizi Wang; Qingfeng Sun; Xiaodong Tang; Xiaoping Shen; Hongxia Xie (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

CDK5-Induced HCN2 Channel Dysfunction in the Prelimbic Cortex Drives Allodynia and Anxiety-Like Behaviors in Neuropathic Pain - Lu Chen; Shuai Cao; Yun-Ze Liu; Qi-Fan Yang; Jin-Yu Yang; Dan-Yang Zhang; Guo-Guang Xie; Xiang-Sha Yin; Ying Zhang; Yun Wang (Neuroscience Bulletin, 2025)

Molecular modeling aided design, synthesis and biological evaluation of quinazoline derivatives for the treatment of human cancer - Cai-Shi Liu; Jin-Peng Tong; Ze-Yu Fang; Xiao-Meng Guo; Ting-Ting Shi; Shou-Rong Liu; Juan Sun (Molecular Diversity, 2025)

Silencing aquaporin 1 inhibits autophagy to exert anti-rheumatoid arthritis effects in TNF-α-induced fibroblast-like synoviocytes and adjuvant-induced arthritis rats - Man-yu Zhang; Meng-qing Wang; Yan Huang; Sheng-long Gu; Meng-yuan Zhou; Ze-shan Xu; Ling-ling Li; Min Lv; Li Cai; Rong Li (Inflammation Research, 2025)

Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Unveiling global energy inequality through the mismatch between embodied energy and value-added transfer - Yannan Zhou; Yuli Shan; Ze He; Yu Yang (Applied Geography, 2025)

Plumbagin disrupts the mature biofilm of Staphylococcus aureus - Hui Yuan; Ming Lu; Chen Shi; Chunshuang Li; Ze Yao; Hui Shang; Xiang Li; Heshui Yu; Songtao Bie (Biofouling, 2025)

Limonoids and protolimonoid from Swietenia macrophylla - Yun-Peng Sun; Wen-Fang Jin; Ze-Rong Xu; Ying-Wei Liu; Li-Juan Sun; Yang Yu; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Upgrade and Application of the Dynamic Positioning System for a Small Waterplane Area Twin Hull Vessel - Jinling Ying; Huabin Mao; Zhiyuan Wei; Yongfeng Qi; Biqing Wu; Chuyin Xuan; Linghui Yu; Ze Qi; Xingyue Wang; Xianpeng Li; Kajia Wu (Journal of Marine Science and Engineering, 2025)
The small waterplane area twin hull (SWATH) is a type of high-performance vessel known for its excellent seakeeping performance, remarkable maneuverability, and high lateral stability. These advantages have led to its growing application in scientific research ships. Since many research operations require a vessel to maintain a fixed position, Dynamic Positioning Systems (DPSs) are essential. To better support diverse scientific tasks, the R/V SHIYAN 1 was upgraded with an enhanced dynamic positioning system. A ship motion model was established after comprehensively accounting for environmental factors such as wind, waves, and currents. By automatically controlling three actuators, the system successfully achieved effective dynamic positioning. In comparative tests conducted under conditions of wind speed at 13.4 m/s, wave height at 3.2 m, and current at 0.2 m/s, the power system was able to maintain a positioning radius within 5 m. Analysis of data from three dynamic positioning experiments revealed that wave loads had the most significant impact on positioning accuracy, followed by wind loads, while ocean current loads had the least influence. This upgrade not only improves the vessel’s operational capability but also enhances its effectiveness in marine scientific exploration.

Sesamol inhibits fungal growth by destroying the redox dynamic equilibrium in Pestalotiopsis neglecta - Jing-Yu Ji; Li-Ying Huang; Bing Bi; Ya-Jun Wang; Jin-Yan Zhao; Sheng-Yu Zhang; Ze Wang; Shu-ming Cui; Qiao-ya Zhang; Guo-Cai Zhang (Physiological and Molecular Plant Pathology, 2025)

Noise-robust underwater propeller fault diagnosis through dictionary learning and graph convolutional networks - Ze Yu; Shuang Gao; Wenfeng Zhao; Bo He (Ocean Engineering, 2025)

Cinnabar-dependent eye pigmentation mediates light input for circadian behavior synchronization in Spodoptera frugiperda - Zi-Jing Zheng; Shen-Lei Li; Shu-Ting Fan; Ze-Yuan Zhang; Shang-Huan Huang; Xi-Yu Ye; Guan-Heng Zhu (Journal of Insect Physiology, 2025)

Acesulfame degradation within a methane-fed biofilm: a novel and efficient biodegradation route - Wenkang Lu; Shengjie Sun; Qingqing Wang; Ziqi Wang; Yong-Ze Lu; Jianhua Guo; He-Ping Zhao; Chun-Yu Lai (Journal of Hazardous Materials, 2025)

Greenhouse gas emissions and nitrogen removal from wastewater - constructed wetland solutions - Ze Guo; Jialin Wang; Yifei Wu; Yihe Wang; Ziyang Dong; Yu Tian; Stevo Lavrnić; Jun Zhang (Journal of Environmental Management, 2025)

Chlorite and associated influence on reservoir properties in tight sandstones of the Upper Shaximiao Formation, SW Sichuan Basin, China - Yunbiao Zhao; Fan Huang; Zhenghui Chen; Zhi Zhao; Hong Yu; Ze Liu; Chenhui Zhao (Journal of Asian Earth Sciences, 2025)

Late Pliocene millennial-scale climate variability response of the South Asian summer monsoon to low-latitude insolation and Antarctic ice sheet forcing - Ze Zhang; Zhixiang Wang; David B. Kemp; Yu Sui; Yanzhen Li; Jiangnan Zhao; Ruiyao Zhang; Anguo Xiao; Mengmeng Cao; Mohan Zhao; Xinya Bai; Chunju Huang (Global and Planetary Change, 2025)

Functional genes and bacterial community assembly dynamics: Key drivers of CO2 emission in the (sub-)deep reservoir biological carbon pump (BCP) - Nan-ping Wu; Yu-fei Bao; Yu-chun Wang; Dan Zhang; Shan-ze Li; Jie Wen; Yuan-yuan Xue; Zhuo Chen; Meng Sun; Hanxiao He; Qian Zhang (Environmental Research, 2025)

Numerical assessment of negative skin friction on pile groups in soft ground - Rui Liang; Zhen-Yu Yin; Pei-Chen Wu; Ze-Jian Chen; Jian-Hua Yin (Computers and Geotechnics, 2025)

Large-area epitaxial hexagonal boron nitride films demonstrating enhanced deep-ultraviolet photodetection enabled by defect suppression under N-rich growth environment - Le Chen; Shuo Wang; Ze Long; Kexiong Zhang; Jinqiang Yu; Hongwei Liang; Hong Yin (Chemical Engineering Journal, 2025)

Stable and high-capacity MnO2-organic aqueous “rocking chair” battery - Runmo Wang; Yu Zhang; Rui Yang; Yaqun Wang; Ze Yang (Chemical Engineering Journal, 2025)

Micro-finned nanostructured superhydrophobic surfaces for high-performance steam condensation heat transfer at high concentrations of non-condensable gases - Wen-Ze Yang; Tian-Yu Zhang; Zhen-Yu Lu; Xuan-Yi Lin; Li-Wu Fan (Chemical Engineering Journal, 2025)

Optimization of conductivity and stability on inverse spinel CoFe2O4 for alkaline oxygen evolution reaction - Fu-Yu Guo; Jian Luan; Xian-Chen Meng; Peng Zheng; Wen-Long Duan; Wen-Ze Li (Chemical Engineering Journal, 2025)

Optimizing multilevel interactions of paper straws using modified cellulose nanocrystal-based coatings to enhance PLA crystallization and microplastic capture efficiency - Yao Xie; Hou-Yong Yu; Haicheng Huang; Chaopei Chen; Ze Ji; Somia Yassin Hussain Abdalkarim; Zhiming Chen (Carbohydrate Polymers, 2025)

Retraction Note to: Overexpression of miR-429 impairs intestinal barrier function in diabetic mice by down-regulating occludin expression - Tao Yu; Xi-Ji Lu; Jie-Yao Li; Ti-Dong Shan; Can-Ze Huang; Hui Ouyang; Hong-Sheng Yang; Ji-Hao Xu; Wa Zhong; Zhong-Sheng Xia; Qi-Kui Chen (Cell and Tissue Research, 2025)

Dietary dimethyl-β-propiothetine supplementation for abalone Haliotis discus hannai: effects on growth, digestion, immunity and appetite - Yang Liu; Zhenhua Wu; Xiaojun Yu; Peng Chen; Yongqing Liu; Ziqian Han; Ze Zhang; Tingting Fang; Kangsen Mai; Wenbing Zhang (Aquaculture International, 2025)

Research on the impact of demographic change on regional sustainable development from the multidimensional coupling perspective - Dong-Feng Ren; Peng Chang; Ze-Yu Hu (Environment, Development and Sustainability, 2025)

Effects of Mono- (2-ethylhexyl) phthalate and Phthalic Acid Monobenzyl Ester on endometriosis using network toxicology, machine learning and molecular docking techniques - Qi Wu; Yu Meng Sun; Qiong Hua Liu; Xing Yue Zhao; Ze Li; Li Xu; Wei Shi (Reproductive Toxicology, 2025)

Uncertainty-based assessment of ice loads for ship navigation in ice floe environments - Ji-Ming Luo; Xing-Hui Li; Ze-Wen Yang; Yu-Chao Yuan; Wen-Yong Tang (Ocean Engineering, 2025)

Molecular and microscale–level insights into the potential mobilization of toxic elements in Pb/Zn smelting contaminated soils under freeze–thaw cycles - Yu–Xiang Shi; Da–Mao Xu; Dong–Sheng Dai; Ze–Lin Xu; Bai–Hong An (Journal of Hazardous Materials, 2025)

Urban soil health improves with green infrastructure and reduced pathogen risks - Can Wang; Ze Zhang; Abolfazl Masoudi; Jingkun Cao; Jichen Qiu; Yin Wang; Min Wang; Jian Feng; Zhijun Yu; Jingze Liu (Journal of Environmental Management, 2025)

Preparation of N263-OA impregnated resin and its study in adsorptive separation of precious metals from wastewater - Shi-lei Lang; Yong-hui Song; Ning Yin; Xin-wei Zhang; Ze-yu Wang; Jia-jun Shi; Yi-xin Wang; Xiao-ming Li (Journal of Environmental Chemical Engineering, 2025)

Enhanced 2,4-DCP degradation with mesoporous nZVI@PRC composite: A high-efficiency PMS activation system and its life cycle assessment - Pengxinyue Huang; Ze Wang; Jiang Yu; Siwei Deng; Zhi Huang; Jie Yu; Yinying Jiang; Weiwei Zhu (Journal of Environmental Chemical Engineering, 2025)

Estuarine long-residence and high-concentration fine sediments induced by reservoir silt discharge during typhoon events - Shang-Shu Shih; Yu-Hsuan Li; Zhong-Ze Huang (Estuarine, Coastal and Shelf Science, 2025)

A two-dimensional discrete metasurface for wireless acoustic communication through water–air interface - Lei Shi; Tong Zhu; Yan-Long Du; Hong-Tao Zhou; Yu-Ze Tian; Yan-Feng Wang; Yue-Sheng Wang (Engineering Structures, 2025)

Aromatic conjugated organic small molecules achieve ultra-stable NH4+ deprotonation storage - Runmo Wang; Yu Zhang; Yaqun Wang; Ze Yang (Chemical Engineering Journal, 2025)

Surface oxygen vacancies-engineered spherical bismuth molybdate: Enhanced visible-light-driven photocatalytic activity for selective oxidation of benzyl alcohol under ambient conditions - Ying-Ying Xu; Wen-Yu Luo; Fei Wen; Yanfei Xu; Zhuo Li; Shanshan Liu; Ze-Long Sun; Xiaoxun Ma; Mingyue Ding; Lin-Yu Jiao (Chemical Engineering Journal, 2025)

Multifunctional TE-Fabric based on interlayer synergy: A flexible thermoelectric fabric for thermal management and self-powered sensing - Tong-Yu Li; Wen-Hao Geng; Ze-Long Bao; Peng-Fei Qian; Yu-Long Guo; Hong-Zhang Geng (Chemical Engineering Journal, 2025)

Enhanced near-infrared mechanoluminescence through energy transfer between Tb3+-Cr3+ pairs in smart oxides - Yu Zhang; Kai Li; Ze Wang; Sur Lig; Hala Muji; Qixu Tian; Yuansong Gao; Nari Mai; Xinyu Gu; Fengqi Zhao; Kefu Chao; Dengfeng Peng (Chemical Engineering Journal, 2025)

Performance and microbial adaptation of a continuous granular sludge-type nitritation process facing the decreasing temperature condition until 5 ℃ - Hongjun Zhao; Yan Guo; Ze Zhang; Qianqian Li; Xiaona Wang; Yuanyuan Ren; Yu-You Li; Qunhui Wang (Bioresource Technology, 2025)

Plant community‐dominating species can sustain population biomass by modifying and strengthening their own growth traits to deal with long‐term grazing - Yu-Wen Zhang; Ze-Chen Peng; Zhao-Feng Wang; Sheng-Hua Chang; Yu-Feng An; Duo-Cai Li; Fu-Jiang Hou; Ji-Zhou Ren (Agriculture, Ecosystems & Environment, 2025)

Diterpene-phenylpropanoid hybrids and structurally diverse diterpenoid monomers from the endangered conifer Podocarpus annamiensis and their bioactivities - Chi Song; Ze-Yu Zhao; Yi Zang; Jia Li; Yeun-Mun Choo; Haibo Wang; Guangyao Mei; Juan Xiong; Jin-Feng Hu (Phytochemistry, 2025)

Green spaces and preventable disease and economic burdens in China from 2000 to 2020: A health impact assessment study - Hui-Ling Qiu; Hui-Yun Chen; Yu-Ting Xie; Gang-Long Zhou; Kai-Ze Yang; Hai-Juan Huang; Jian-Cheng Jiang; Xiao-Qi Zhu; Lu Wang; Kexin Yan; Guang-Hui Dong; Shujun Fan; et al. (Landscape and Urban Planning, 2025)

Competitive effects and environmental factors driving heavy metal leaching in stabilized municipal solid waste incineration fly ash under extreme conditions - Ze Zhang; Yang Yu; Yi Rao; Ying Wang; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Xiaona Wang; Ming Gao; Chuanfu Wu; Shu Liu (Journal of Hazardous Materials, 2025)

Petrological and thermodynamic constraints on carbonate stability in altered oceanic crust subducted to subarc depths: Insights from carbonate-bearing eclogites in the Western Alps - Zeng-Li Guo; Jin-Xue Du; Li-Fei Zhang; Thomas Bader; Ren-Biao Tao; Ze-Ming Zhang; Kurt Bucher; Ting-Nan Gong; Jin-Hong Yu (Geochimica et Cosmochimica Acta, 2025)

Comprehensive assessment of natural estrogens in poultry eggs: Implications for health risks and dietary intervention strategies - Can-yuan Lin; De-ming Kong; Jian Gong; Ze-hua Liu; Zhi Dang; Peng-ran Guo; Yu-mei Song; Jin-yi Sun (Food and Chemical Toxicology, 2025)

Numerical assessment of negative skin friction on piles in soft soils considering pile penetration effects - Rui Liang; Zhen-Yu Yin; Pei-Chen Wu; Ze-Jian Chen; Jian-Hua Yin (Computers and Geotechnics, 2025)

Chitosan/PEO@Eu-MOF nanofiber membrane-based test strip for visual detection of tetracycline with smartphone-assisted analysis - Wei Pan; Zi-Han Zhu; Yan-Shen Zhao; Jie-Liu; Zhi-Guang Zhang; Gui-Xia Li; Tao Yu; Zhong-Zhi Han; Yun-Ze Long; Gui-Feng Yu (Chemical Engineering Journal, 2025)

Conduction of AgNPs with different surface charges in pine trees and their prevention and control of pine wood nematode disease - Shouhe Pan; Pengkun Yan; Rui Zhao; Fengyu Li; Lei Wang; Yinmin Wang; Ze Lv; Yingjian Ma; Meng Yu; Xinyu Guo; Yonggang Xia; Yong Xu; et al. (Chemical Engineering Journal, 2025)

Smart eutectogel with antibacterial activity for efficiently treating multidrug resistant infection, real-time monitoring and diabetic wound repair - Zijie Wang; Baiwen Qi; Ruizi Wang; Ze Chen; Jingming Zhong; Zheng Wang; Qingfeng Sun; Aixi Yu; Xiaoping Shen; Hongxia Xie (Chemical Engineering Journal, 2025)

A Cu-based electronically conducting metal–organic framework with π–d conjugation for cathode and anode modification in aqueous zinc-ion batteries - Chuntao Yang; Kaiyong Feng; Jiangchang Chen; Ze Liu; Yingjian Yu (Chemical Engineering Journal, 2025)

Topology-engineered semi-crosslinked phosphaphenanthrene architectures for epoxy resins: Unlocking synergistic flame retardancy, mechanical, and dielectric properties - Ze-Kun Wang; Yan-Fang Xiao; Shu-Gen Wu; Zhen Qin; Yu-Zhong Wang; Li Chen (Chemical Engineering Journal, 2025)

Pd-Sb bimetallic catalysis for propylene acetoxylation: Identification of active sites and catalytic mechanism - Yong Yan; Ze-Kai Yu; Huai-Qiang Dou; Zhi-Qiang Wang; Cheng-Wei Liu; Xue-Qing Gong; Wen-De Xiao (Chemical Engineering Journal, 2025)

Nitrogen Doped Glycerol-Based Biochar as Effective Catalyst Activating Peroxydisulfate for Organic Dyes Removal - Cai-Wu Luo; Chao Xie; Qing-Qing Chen; Yu Zhang; Liang Jiang; Run-Ze Zhao; Jing-Jing Luo; Tian-Jiao Jiang (Water, Air, & Soil Pollution, 2025)

Limited leaf thermal acclimation but higher tolerance in subtropical trees after 10-year translocation in Dinghushan biosphere reserve - Ting Wu; David T Tissue; Wei Su; Honglang Duan; Mark G. Tjoelker; Sachin G. Chavan; Shuyidan Zhou; Junfeng Yuan; Liang Fang; Mengxiao Yu; Shizhong Liu; Guowei Chu; et al. (Agricultural and Forest Meteorology, 2025)

5-aminoindole restrained larval growth and chitin biosynthesis via depressing TPS activity in Hyphantria cunea - Jinxin Yu; Shengyu Zhang; Diankuan Liu; Ze Wang; Yuyao Nan; Chuanshan Zou (Pesticide Biochemistry and Physiology, 2025)

Improved antifouling and regeneration capability of polyaniline-modified halloysite nanotube/MXene composite membranes - Jing-Yi Feng; Wen-Hao Geng; Ru-Yu Chang; Yu-Han Wang; Yue-Xin Wang; Ze-Long Bao; Wen-Yi Sun; Lu-Yao Tian; Di Zhang; Hong-Zhang Geng (Journal of Water Process Engineering, 2025)

Machine learning based prediction by PlantCdMiner and experimental validation of cadmium-responsive genes in plants - Chaoqun Xu; Ling Sun; Lu-Dan Zhang; Ze-Jun Guo; Ji-Cheng Wang; Li-Han Zhuang; Dong-Na Ma; Ling-Yu Song; Jing Li; Qian-Su Ding; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2025)

Thick polyethylene films lessen pollution footprint while highlighting environmental merit and maize yielding in drylands - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Zi-Yu Han; Yuan Song; Ying Zhu; Yi-Bo Wang; Jin-Lin Zhang; Xu-Sheng Guo; Xiao-Feng Zhang; Xiao-Yu Lu; You-Cai Xiong (Journal of Environmental Management, 2025)

Investigation of methanol steam reforming reactors with different catalyst support structures on hydrogen production efficiency and methanol conversion - Yuan Li; Ze-yu Ma; Zi-yan Qi; Zhi-an Xue; Xiao-long Zhou; Hao Guo (Fuel, 2025)

High-phytosterol rapeseed oil prevents atherosclerosis by reducing intestinal barrier dysfunction and cholesterol uptake in ApoE−/− mice - Yaxi Xu; Mengxue Fang; Ze Chen; Zhili Jin; Tong Zhang; Li Yu; Fei Ma; Zhibing Lu; Hairong Wang; Liangxiao Zhang; Peiwu Li (Food Research International, 2025)

Integrating genome assembly, structural variation map construction and GWAS reveal the impact of SVs on agronomic traits of Brassica napus - Nian Wang; Xianshuai Song; Lieqiong Kuang; Ze Tian; Kaifeng Wang; Keqi Li; Lan Ge; Yu Wu; Xinfa Wang; Xiaoling Dun; Hanzhong Wang (Theoretical and Applied Genetics, 2025)

On the Inconsistency of Cloud Liquid Water between Reanalyses and Satellite Observations over East Asia - Yunheng Xue; Jie Yu; Miao Cai; Ze Chen; Ling Yang; Jia Li (Journal of Meteorological Research, 2025)

Numerical Simulation of Seabed Response Around Monopile Under Wave–Vibration - Hongyi Du; Dunge Wang; Jiankang Hou; Ziqin Yu; Ze Liu; Yongzhou Cheng (Journal of Marine Science and Engineering, 2025)
Monopile foundation is an important foundation form for offshore wind turbines, and the stability of the seabed around it is affected by the combined effects of wave and pile vibration. Based on the Biot consolidation theory and elastoplastic constitutive model, a multi-physical field coupling model of wave–vibration–seabed–monopile is constructed, and the dynamic characteristics of seabed pore pressure around the monopile under the joint action of wave–vibration are systematically investigated, and the influences of waves, vibrations, and seabed parameters on the distribution of pore pressure amplitude are analysed in depth. The results show that the increase in wave incident energy will increase the seabed wave pressure, and the suction and pressure generated by pile vibration will change the soil force state; the coupling of waves and vibrations results in pile displacement difference, causing the seabed pore pressure dissipation depth dissimilarity, and the peak relative amplitude of pore pressure and the peak of vibration displacement are in a linear relationship; the wave parameters and seabed characteristics have a significant effect on the change in pore pressure amplitude distribution.

Phytochemical and biological studies on rare and endangered plants endemic to China. Part XLIV. Integrated NMR/EI-MS/LC-PDA-ESIMS approach for dereplication and targeted isolation of fortunefuroic acids from Keteleeria fortunei across diverse geographical origins - Ze-Yu Zhao; Zhe-Lu Jiang; Ying-Peng Tong; Chun-Jing Chi; Yi Zang; Yeun-Mun Choo; Juan Xiong; Jia Li; Jin-Feng Hu (Phytochemistry, 2025)

Simultaneous high molecular weight PAHs degradation and chromate and arsenite detoxification by Altererythrobacter sp. H2 - Qun Han; Mei-Ling Yang; Ze-Shen Liu; Ying-Hao Zhao; Xue-Hui Liu; Guo-Min Ai; Wei-Hong Qin; Xing-Yu Liu; De-Feng Li (Journal of Hazardous Materials, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Self-healing conductive polymer maltose polyborosiloxane matrix for motion detection and imperceptible pulse sensing - Ching-Te Kuo; Kuan-Yu Tu; Guan-Ze Song; Lung-Hao Hu (Chemical Engineering Journal, 2025)

Stability Evaluation of the Artificial Dam in Underground Reservoirs Under Storage and Drainage Cycles: A Method Based on Concrete Performance and Case Study - Yinghu Li; Qiangling Yao; Ze Xia; Qiang Xu; Liqiang Yu; Zichang Liu; Shengyan Chen (Rock Mechanics and Rock Engineering, 2025)

Chelation treatment for heavy metals in municipal solid waste incineration fly ash: 300-Day study on stability and environmental risk - Ze Zhang; Yang Yu; Yi Rao; Ying Wang; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Xiaona Wang; Ming Gao; Qunhui Wang; Chuanfu Wu (Waste Management, 2025)

Design and synthesis of novel bifunctional polymer with multiplying effect for remediation of uranium-contaminated wastewater - Ze-Yang Wang; Feng Zhang; Jin-Lei Liu; Xu-Xin Li; Wei-Jia Wang; Wen-Jiang Yang; Ze-Yu Ren; Yang Li; Ze-Yi Yan (Journal of Environmental Chemical Engineering, 2025)

Cost-effective production of squalene using Yarrowia lipolytica via metabolic engineering and fermentation engineering - Wen-Bo Lin; Hong Chen; Ze-Qi Song; Yu-Qing Pan; Peng-Cheng Hu; Xiao-Na Yang; Xiang-Yang Lu; Yun Tian; Hu-Hu Liu (Biotechnology Letters, 2025)

Physiological, transcriptomic and metabolomic responses of the marine diatom Phaeodactylum tricornutum to the auxin IAA - Yu-Ting Chen; Dong-Sheng Zhao; Xiao-Li Liu; Huan Yang; Run-Ze Gu; Nan Li; Xiufeng Yan; Hui-Xi Zou (Algal Research, 2025)

A practical approach for grading cotton Verticillium wilt severity for remote sensing monitoring - Yaohui Gui; Changping Huang; Junru Zhou; Mi Yang; Xiaofeng Qiu; Ze Zhang; Yaokai Liu; Yu Gao; Weiling Shen; Wenjiang Huang; Bhaskar Shrestha; Lifu Zhang (Agricultural and Forest Meteorology, 2025)

Aeromagnetic Compensation Method Based on Recursive Least Square and Elastic Weight Consolidation - Xiao-Yu Ma; Jin-Sheng Zhang; Shou-Yi Liao; Ting Li; Ze-Hao Li (Applied Geophysics, 2025)

China’s land-sea environmental regulatory system: reforms and impacts - Ze Jin; Miaohong Yu (Frontiers in Marine Science, 2025)
The updated “Marine Environment Protection Law of the People’s Republic of China,” effective from January 1, 2024, emphasizes enhanced land and marine development in a coordinated way. The revised law has been amended from the original ten chapters comprising 97 articles to nine chapters comprising 124 articles, with an addition of 27 clauses. In particular, the original law had only 3 clauses related to regulatory bodies, which increased to 8 after the revision. Chapter II Supervision and Control over the Marine Environment has added 4 clauses and revised 4 clauses to pursue coordinated land and marine development and regional linkage. As for marine ecological protection, there are 3 new clauses in Chapter III. Through specifying authorities’ responsibilities, fostering a coherent approach to land-sea environmental governance, and bolstering ecological safeguards, these amendments fill a gap in regulations concerning land and marine development in a coordinated way. On this basis, the implementation of the new law will promote a positive interaction between the marine economy and the land-based economy, and facilitate the collaborative governance of ecological environments in both terrestrial and marine areas.

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Unraveling mechanism of denitrification process for treating low carbon-to-nitrogen ratio wastewater with different zero-valent iron exogenous enhancement strategies - Ze-Tong Feng; Yan Yu; Ying-Jun Sun; Jia-Min Zhou; Xin Ma; Fei Ding; Yi-Liu Zheng; Ren-Cun Jin; Chun-Qiang Shen; Qian-Qian Zhang (Journal of Water Process Engineering, 2025)

Pore space optimization of hybrid ultramicroporous material for exceptional one-step C2H4 purification from C2H2/CO2/C2H4 mixture - Hong-Xiang Nie; Hong-Wei Chen; Ting Wang; Hongliang Huang; Qiang Gao; Mei-Hui Yu; Jian Zhu; Li-Bo Li; Zhenjie Zhang; Ze Chang; Xian-He Bu (Chemical Engineering Journal, 2025)

Converting static to Dynamic: Biomimetic Ultra-Sensitive Wide-Range flexible pressure sensor inspired by the Contact-Regulation process of scorpion pectines - Junqiu Zhang; Jiachao Wu; Lili Liu; Xiangbo Gu; Xueping Zhang; Xueyang Li; Zijian Shi; Yu Chen; Jiqi Gao; Junfeng Zhang; Tao Sun; Honglie Song; et al. (Chemical Engineering Journal, 2025)

3D self-supportive structures of micro/nanofiber assemblies constructed in situ in air turbulent flow fields for thermal protection at extreme conditions - Pi-Hang Yu; Yuan Gao; Guo-Dong Zhang; Chao Zhang; Chuan-Hui Guo; Seeram Ramakrishna; Yun-Ze Long; Jun Zhang (Chemical Engineering Journal, 2025)

Inhibition of KDM6B prevents osteoarthritis by blocking growth plate-like H3K27me3 loss in bivalent genes - Hao Du; Yao Zhang; Xi Yu; Xuanhe You; Diwei Wu; Ze Du; Yongrui Cai; Zhenyu Luo; Hanpeng Lu; Zhixin Liao; Bi-Sen Ding; Ya Zhao; et al. (Science China Life Sciences, 2025)

Skeletal muscle-specific Bambi deletion induces hypertrophy and oxidative switching coupling with adipocyte thermogenesis against metabolic disorders - Xiangping Yao; Xudong Mai; Ye Tian; Yifan Liu; Guanghui Jin; Ze Li; Shujie Chen; Xiaoshuang Dai; Liujing Huang; Zijing Fan; Guihua Pan; Xiaohan Pan; et al. (Science China Life Sciences, 2025)

Magma genesis and crustal evolution in continental collision zones - Di-Cheng Zhu; Qing Wang; Shi-Min Li; Qiong-Yao Zhan; Ze Liu; Jin-Cheng Xie; Li Liu; Liang-Liang Zhang; Xin-Yi Zhong; Yu-Xuan Zhao (Science China Earth Sciences, 2025)

Soil viruses regulate soil nutrient cycling through themselves and their effects on host functioning to impede the growth of continuously planted Casuarina equisetifolia - Yu-Hua Wang; Lei Hong; Yi Lin; Miao-En Qiu; Jian-Juan Li; Qing-Xu Zhang; Xiao-Li Jia; Yu-Lin Wang; Li-Yuan Wang; Yang-Xin Luo; Wen-Xiong Lin; Hai-Bin Wang; et al. (Applied Soil Ecology, 2025)

A dual-functional paper-based analytical device for ultrasensitive detection of peanut allergen-specific IgE - Ze-Nan Ma; Jun-Jie Ding; Xin-Qiao Shi; Ying Yuan; Meng-Tian Wang; Li-Na Yu; Xiao-Jun Wang; Peng Shen (Analytica Chimica Acta, 2025)

Unearthing Vertical Stratified Archaeal Community and Associated Methane Metabolism in Thermokarst Sediments - Ze Ren; Mei Wang; Jinlei Yu; Lixiang Zhang; Zhenmei Lin; Xia Li; Yunlin Zhang (Environmental Microbiology, 2025)
Thermokarst lakes are hotspots for greenhouse gas emissions across the Arctic and Qinghai‐Tibet Plateau. Investigating the vertical stratification of archaeal communities in thermokarst lake sediments is essential for understanding their ecological roles and contributions to methane production. Here, we analysed archaeal communities along a depth gradient in thermokarst lake sediments. Alpha diversity (richness and Shannon index) generally decreased with depth. Euryarchaeota was the most abundant phylum, though its relative abundance declined with depth, while Thaumarchaeota increased. At the order level, Methanosarcinales and Nitrosopumilales showed increased relative abundance with depth, indicating adaptation to deeper anoxic layers, whereas Methanomicrobiales and Methanotrichales decreased. Beta diversity increased with depth, shifting from stochastic to deterministic processes. Network topology revealed reduced species connectivity but heightened modularity at depth, signalling niche specialisation. Functionally, genes associated with the initial steps of methane metabolism ( Fwd , Mtd , Mer ) increased with depth, while those involved in later steps ( Mtr , Mcr ) decreased, suggesting reduced energy conservation efficiency and lower overall methanogenesis rates in deeper sediments. These findings highlight the significant impact of vertical stratification on archaeal community structure, interaction networks, and functional capabilities.

Development and evaluation of 50 K liquid SNP array for blunt snout bream (Megalobrama amblycephala) - Li-Fei Luo; Yao Wang; Shi-Long Wang; Yue Yu; Yu-Ye Fu; Chun-Hong Nie; De-Wen Tang; Ze-Xia Gao (Aquaculture, 2025)

Cross-size underwater propeller fault diagnosis via domain adversarial training with spectral attention and multi-task learning - Ze Yu; Wenfeng Zhao; Shuang Gao; Bo He (Ocean Engineering, 2025)

Construction and application of antimicrobial ultrafiltration membranes based on electro-stimulated hollow mesoporous carbon spheres and carbon nanotubes - Ru-Yu Chang; Wen-Hao Geng; Li-Chao Jing; Jing-Yi Feng; Yue-Xin Wang; Peng-Fei Qian; Ze-Long Bao; Wenyi Wang; Di Zhang; Hong-Zhang Geng (Journal of Environmental Chemical Engineering, 2025)

High-temperature creep damage and failure of symmetrical flat-tube solid oxide fuel cell - Yun Luo; De-Ze Feng; Yu-Tong Zheng; Yu-Cai Zhang; Wen-Chun Jiang (Fuel, 2025)

Highly sensitive aggregation-induced electrochemiluminescence sensor for cadmium detection in Ganoderma lucidum - Zhi-Hong Xu; Xin Weng; Sha-Sha Wang; Ze-Hao Huang; Wen Xu; Wei Xu; Yu Lin; Hang Gao (Food Chemistry, 2025)

Based on metabolomics and fourier transforms near infrared spectroscopy characterization of Lanxangia tsaoko chemical profile differences among fruit types and development of rapid identification and nutrient prediction models - Deng-Ke Fu; Wei-Ze Yang; Mei-Quan Yang; Tian-Mei Yang; Yuan-Zhong Wang; Jin-Yu Zhang (Food Bioscience, 2025)

Pre-trained Physics-Informed Neural Networks for Analysis of Contaminant Transport in Soils - Ze-Wei Ke; Sheng-Jie Wei; Shi-Yuan Yao; Si Chen; Yun-Min Chen; Yu-Chao Li (Computers and Geotechnics, 2025)

Petrogenesis of Ke’eryin granitic pegmatites and associated Li mineralization in the Songpan–Ganze orogenic belt, China: evidence from apatite and bulk-rock chemistry - Qing-Gao Yan; Jian-Kang Li; Deng-Hong Wang; Ze-Ying Zhu; Chao Li; Zhen-Yu Chen (Mineralium Deposita, 2025)

Functional potential of compound probiotics fermented soybean meal partially replacing fish meal in spotted seabass (Lateolabrax maculatus): Insights through growth, immunity, antioxidant capacity and intestinal health - Bi-Yun Zhang; Ze-Hui Yuan; Hai-Xia Yu; Hong-Ling Yang; Guo-He Cai; Chun-Xiao Zhang; Jie Su; Yun-Zhang Sun (Aquaculture, 2025)

Research on the hydrothermal process and deformation law of the fill-cut transition section subgrade under dynamic load - Jinbang Zhai; Ze Zhang; Delong Zhang; Kun Zhang; Qihao Yu; Yaqi Zhang (Transportation Geotechnics, 2025)

Peptide neurotoxins affecting insect voltage-gated calcium channels and possessing insecticidal toxicity: Two ω-Atypitoxins from Calommata signata - Yang-yang Yan; Kan Wang; Jing-ting Wang; Qian-qian Han; Zhen Zhang; Na Yu; Ze-Wen Liu (Pesticide Biochemistry and Physiology, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Targeted isolation of lignans and triterpenoids from kadsura coccinea by molecular networking and anti-RA-FLS activity - Shi-qi Liu; Qing-ling Xie; Ya-si Deng; Ling Liang; Han-wen Yuan; Bin Li; Huang-he Yu; Xing Tian; Yi-xing Qiu; Guy Paulin Kemayou Mouthe; Nuzhat Shehla; Ye Zhang; et al. (Phytochemistry, 2025)

Diagnosis method for AUV propeller entanglement based on stylistic diversity and physics-guided priors - Wenfeng Zhao; Ze Yu; Shenghui Rong; Bo He (Ocean Engineering, 2025)

Assessing tea foliar quality by coupling image segmentation and spectral information of multispectral imagery - Xue Kong; Bo Xu; Yang Meng; Qinhong Liao; Yu Wang; Zhenhai Li; Guijun Yang; Ze Xu; Haibin Yang (European Journal of Agronomy, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Exogenous and endogenous optimization for efficient nonconical amino acids incorporation in Saccharomyces cerevisiae - Ji-Ren Wen; Hong-Yu Xie; Ze-Xiong Xie; Ying-Jin Yuan (Chemical Engineering Journal, 2025)

Multi-model and naked-hand wearable sensing system based on direct writing Ag-TPU composite with porous microstructure for human–computer interactions - Yun-Fan Wang; Xiao-Yang Zhang; Jun-Yang Liu; Yuan-Jun Song; Yu-Qing Ni; Ze-Xian Chen; Yuan-Chun Li; Tong Zhang (Chemical Engineering Journal, 2025)

A study of interior design elements promoting the perception of healing considering gender and age: A multi-domain approach - Yi-Kyung Hong; Ji Young Cho; Ze-Yu Wang (Building and Environment, 2025)

MRI Shrimp Sign and Parietooccipital Lesion in Progressive Multifocal Leukoencephalopathy - Wen-Qian Luo; Bin Liu; Chun-Lin Yang; Ze-Yu Zhao; Guan-Qing Wang; Xiao-Li Li; Peng Zhang (The Cerebellum, 2025)

Interaction of micro and nanoplastics (MNPs) with agricultural stored products and their pests - Sakhawat Shah; Muhammad Ilyas; Ze-Yu Liu; De-Jiang Zhang; Gang Wu; Qiu-Ying Huang; Karam Khamis Elgizawy; Feng-Lian Yang (Science of The Total Environment, 2025)

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Compositional diversity of continental arc magmatism caused by variable degrees of mantle melting: A Gangdese case study - Zhi-Guo Zhou; Ze Liu; Qing Wang; Di-Cheng Zhu; Peter A. Cawood; Yu An; Li Liu; Liang-Liang Zhang; Jin-Cheng Xie (Lithos, 2025)

Comparative analysis of certified emission reduction methodologies for methane emission reduction in China - Ze Li; Zhenyang Yu; Peidong Zhang; Siqi Wang; Raymond R. Tan; Xiaoping Jia; Xufei Pang (Journal of Environmental Management, 2025)

The growth and nutrient removal properties of heterotrophic microalgae using volatile fatty acids under different nitrogen forms and its application in actual acid-producing wastewater - Cong Jia; Na Liu; Lei Chen; Wenbao Yan; Qi Zhao; Jie Li; Ze Yu; Mingming Song; Chongqing Xu; Xiaozhe Song (Journal of Environmental Chemical Engineering, 2025)

Application of machine learning to predict the fluoride removal capability of MgO - Lin Fan; Dexi Wang; Honglei Yu; Ze Gong; Yan He; Jinyuan Guo (Journal of Environmental Chemical Engineering, 2025)

Anaerobic co-digestion of winery wastewater with sewage sludge for methane production: Complementary feedstocks and potential direct interspecies electron transfer - Zhixuan Ma; Lifang Yu; Ze Wang; Xin Tian; Lanxiang Zheng; Ran Liu (Fuel, 2025)

Fast simulation strategy for capacitively-coupled plasmas based on fluid model - Jing-Ze Li; Ming-Liang Zhao; Yu-Ru Zhang; Fei Gao; You-Nian Wang (Computer Physics Communications, 2025)

Enhancing antibiotic removal of mixed matrix membranes through electrostatic surface segregation of MIL-101(Fe) catalysts - Xia Zheng; Zhaomei Yang; Guangyong Zeng; Qingquan Lin; Xi Chen; Yuan Xiang; Yu-Hsuan Chiao; Ralph Rolly Gonzales; Ze-Xian Low; Jianquan Luo (Chemical Engineering Journal, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

Whole-genome re-sequencing reveals genetic structure and selection signals of different populations in Megalobrama amblycephala - Shi-Long Wang; Li-Fei Luo; Yue Yu; Yu-Ye Fu; Ze-Xia Gao (Aquaculture, 2025)

Effects of PM2.5 components on hypertension and diabetes: Assessing the mitigating influence of green spaces - Hongyue Sun; Chengjie Pan; Mengfan Yan; Zhongli Wang; Jiayu He; Honglu Zhang; Ze Yang; Zinuo Wang; Yiqing Wang; Hongyan Liu; Xueli Yang; Fang Hou; et al. (Science of The Total Environment, 2025)

Benzofurans and dibenzofurans from galls on twigs of the endangered Chinese endemic tree Parrotia subaequalis and their inhibitory properties against Staphylococcus aureus and ATP-citrate lyase - Peng-Jun Zhou; Xi-Ying Wu; Ze-Yu Zhao; Yi Zang; Zhong-Shuai Sun; Yue-Ling Li; Na Li; Juan Xiong; Yeun-Mun Choo; Ze-Xin Jin; Jia Li; Jin-Feng Hu (Phytochemistry, 2025)

The feasibility of batch-wise polyester degradation and recycling using recombinant Escherichia coli expressing PHB depolymerase (PhaZ ) - Yen-Chun Lin; En Ze Linda Zhong-Johnson; Anthony J. Sinskey; Si-Yu Li (Journal of Environmental Management, 2025)

Experimental study on hydraulic performance and cavitation characteristics of a R134a refrigerant self-lubricating centrifugal pump - Ze Zhang; Song Yang; Beile Zhang; Xufeng Fang; Rong Xue; Shuangtao Chen; Yu Hou (International Journal of Refrigeration, 2025)

Effect of flaxseed oil cyclolinopeptides on lipid oxidation, protein oxidation, and lipid profile during in vitro digestion of high-fat beef - Abdul Mueed; He Ma; Philippe Madjirebaye; Akhtar Ali; Sajjad Ali; Jingwen Yu; Jing Li; Ze-yuan Deng (Food Chemistry, 2025)

Prospective LCA towards achieving carbon neutrality goals: Framework application and challenges - Ya-Xi Fang; Pei-Ze Wu; Sha Chen; Yu Li; Shu-Fen Cui; Jin-Xing Zhu; Hai-Zhou Cao; Ke-Jun Jiang; Ling Zhong (Environmental Impact Assessment Review, 2025)

Volcanic-intrusive connections and crystal-melt segregation in the Dulan tilted crustal section: Insights from accessory mineral evolution - Bin Liu; Luan Wu; Chang-Qian Ma; Meng-Yu Zhang; Zhen-Hua Xue; Yang Sun; Shi-Ze Li (Chemical Geology, 2025)

Rice intercropping with water mimosa (Neptunia oleracea Lour.) could alleviate the negative effects of simulated nitrogen deposition on rice and soil - Yu-Hao Deng; Ji-Dong Liao; Ze-Wen Hei; Kai-Ming Liang; Hui Wei; Jia-En Zhang; Hui-Min Xiang (Plant and Soil, 2025)

Enhanced spectral reconstruction of ultrafast spatiotemporal encoded 2D NMR spectroscopy - Hong Li; Yida Chen; Ze Fang; Yulan Lin; Lucio Frydman; Yu Yang; Zhong Chen (Analytica Chimica Acta, 2025)

Supplementing ageing male laying breeders with lycopene alleviates oxidative stress in testis and improves testosterone secretion - Chun-Yu Ma; Ao-Chuan Yu; Xi-Hui Sheng; Xiang-Guo Wang; Kai Xing; Long-Fei Xiao; Xue-Ze Lv; Yong Guo; Cheng Long; Xiao-Long Qi (Theriogenology, 2024)

Major specialized natural products from the endangered plant Heptacodium miconioides, potential medicinal uses and insights into its longstanding unresolved systematic classification - Ze-Yu Zhao; Jiang Wan; Hao-Wei Chen; Zhong-Shuai Sun; Yu-Tian Tao; Yingpeng Tong; Yi Zang; Yeun-Mun Choo; Pan Wang; Yue-Ling Li; Chun-Xiao Jiang; Junming Li; et al. (Phytochemistry, 2024)

High-value flavonoids with potential anti-inflammatory benefits from Platanus × acerifolia Willd leaves: Turning waste into treasure - Xi-Ying Wu; Ze-Yu Zhao; Ezzat E.A. Osman; Yeun-Mun Choo; Juan Xiong; Mark T. Hamann; Jin-Feng Hu (Phytochemistry Letters, 2024)

Serum trace elements and osteoarthritis: A meta-analysis and Mendelian randomization study - Haoyan Shi; Haochen Wang; Minghao Yu; Jianbang Su; Ze Zhao; Tianqi Gao; Qian Zhang; Yingliang Wei (Journal of Trace Elements in Medicine and Biology, 2024)

Investigating interface adhesion of PLA-coated cellulose paper straws: Degradation, plant growth effects, and life cycle assessment - Yao Xie; Ze Ji; Somia Yassin Hussain Abdalkarim; Haicheng Huang; Khaydar E. Yunusov; Hou-Yong Yu (Journal of Hazardous Materials, 2024)

Fabrication of C and N co-doped CdS semiconductor photocatalysts derived from a novel Cd-MOF for enhancing photocatalytic performance - Wen-Ze Li; Yi Liu; Zhen-Yu Wang; Xian-Chen Meng; Peng Zheng; Jian Luan (Journal of Environmental Chemical Engineering, 2024)

Transcriptome analysis reveals the mechanism of black rockfish (Sebastes schlegelii) macrophages respond to Edwardsiella piscicida infection in vivo - Xuangang Wang; Xiangfu Kong; Zhentao Chen; Hengshun Li; Ze Tao; Quanqi Zhang; Haiyang Yu (Fish & Shellfish Immunology, 2024)

Co-exposure of microplastics with heavy metals increases environmental pressure in the endangered and rare wildlife reserve: A case study of the zhalong wetland red-crowned crane nature reserve, northeast China - Lei Wang; Yuchen Wei; Bing Wang; Jufang Hu; Chuntao Zhao; Dongmei Yu; Jianping Wang; Ze Liu (Environmental Pollution, 2024)

Effect of natural astaxanthin on sperm quality and mitochondrial function of breeder rooster semen cryopreservation - Jia-Yu Wu; Huan-Yu Kang; Yong Guo; Xi-Hui Sheng; Xiang-Guo Wang; Kai Xing; Long-Fei Xiao; Xue-Ze Lv; Cheng Long; Xiao-Long Qi (Cryobiology, 2024)

Ratiometric fluorescence and photothermal dual-mode immunosensor based on MnO2 nanosheets for the detection of isocarbophos - Jie Liu; Hao Deng; Bao-Zhu Jia; Ze-Shan Lin; Yu Wang; Hong Wang; Zhen-Lin Xu; Lin Luo (Chemical Engineering Journal, 2024)

Transcriptomic analysis of hub genes regulating nitrate and glucose response of nitrate response deficiency 1 (NRD1) mutant in foxtail millet - Xin-Li Yao; Zi-Dong Li; Ming-Hua Zhang; Hui-Xin Meng; Yu-Ze Wang; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; Jia-Gang Wang (Plant Cell Reports, 2024)

Molecular characterization, expression and immune functional analysis of cystatin 10 in turbot - Fan Zhang; Zhixiang Duan; Qiannan Chen; Xuangang Wang; Hengshun Li; Ze Tao; Zhentao Chen; Gan Yu; Haiyang Yu (Molecular Biology Reports, 2024)

Processing of N-glycans in the ER and Golgi influences the production of surface sialylated glycoRNA - Yi-Shi Liu; Yu-Long Miao; Yue Dou; Ze-Hui Yang; Wenhao Sun; Xiaoman Zhou; Zijie Li; Nakanishi Hideki; Xiao-Dong Gao; Morihisa Fujita (Glycoconjugate Journal, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

PFOS impairs cardiac function and energy metabolism under high-fat diet: Insights into role of circulating macrophage emphasized by exposure distribution - Ze Zhang; Hao Yin; Chuer Zheng; Zhenhua Yu; Rifat Zubair Ahmed; Yong Niu; Chengying Zhou; Jian Ding; Huan Lin; Yongfeng Lin; Yuxin Zheng; Xiaoting Jin (Science of The Total Environment, 2024)

A molecular mechanism underlies grass carp (Ctenopharyngodon idella) TARBP2 regulating PKR-mediated cell apoptosis - Miao-miao Li; Chang-bai Tao; Mei-feng Li; Chu-xin Wu; Ting-ting Yu; Zhi-qing Feng; Qing-Zhang; Ze-yin Jiang; Hui-ling Mao; Shang-hong Wang; Xiao-wen Xu; Cheng-yu Hu (Fish & Shellfish Immunology, 2024)

Role of ASC, a key component of the inflammasome in the antimicrobial process in black rockfish (Sebastes schlegelii) - Ze Tao; Xuangang Wang; Hengshun Li; Dianyang Zhou; Qiannan Chen; Zhixiang Duan; Fan Zhang; Zhentao Chen; Gan Yu; Haiyang Yu (Fish & Shellfish Immunology, 2024)

Monoclonal antibody based colloidal gold immunochromatographic assay for the visual and rapid screening of profenofos - Ri-Sheng Chen; Jian-Cheng Yuan; Chong-Lan Luo; Yu Wang; Zi-Jian Chen; Ze-Shan Lin; Zhen-Lin Xu (Environmental Pollution, 2024)

Enhanced CO2 Reduction via S-Scheme Heterojunction of Amorphous/Crystalline Metal-free Carbon Nitride Photocatalysts - Liting Wu; Dingyi Yang; Yalin Dong; Ze Wang; Yu Zhang; Tingting Wang; Liang Cheng; Yong Wang; Yizhang Wu (Chemical Engineering Journal, 2024)

Nanofiber aerogel with layered array with structure coupled photothermal/magnetothermal effect for continuous seawater desalination - Zichen Yu; Tingting Fan; Yang Liu; Bowen Yang; Luyao Wang; Fang Yin; Yuan Gao; Yun-Ze Long (Chemical Engineering Journal, 2024)

Modeling of extreme waves in the South China Sea under the influence of tropical cyclones: long-term statistical perspective in Xisha reef islands - Yu Yao; Danni Zhong; Jiangxia Li; Erman Peng; Conghao Xu; Long Chen; Ze Sun (Natural Hazards, 2024)

Identification of novel SNPs and candidate genes significantly affecting growth in grass carp (Ctenopharyngodon idella) through GWAS analysis - Dong-Yang Zhang; Li-Fei Luo; Zheng-Yin Wang; Yue Yu; Chun-Hong Nie; Xiang-Zhao Guo; Ze-Xia Gao (Aquaculture, 2024)

Association of metals and bisphenols exposure with lipid profiles and dyslipidemia in Chinese adults: Independent, combined and interactive effects - Jiemin Wei; Ruifang Liu; Ze Yang; Hongbo Liu; Yiqing Wang; Jingyun Zhang; Meiqing Sun; Changkun Shen; Jian Liu; Pei Yu; Nai-jun Tang (Science of The Total Environment, 2024)

Phytochemical and biological studies on rare and endangered plants endemic to China. Part XXXVI. Tsugaforrestiacids A–O: Structurally diverse C-18 carboxylated diterpenoids from the twigs and needles of the ‘vulnerable’ conifer and their inhibitory effects on ATP-citrate lyase - Peng-Jun Zhou; Ze-Yu Zhao; Jin-Xin Zhu; Yi Zang; Menny M. Benjamin; Juan Xiong; Jia Li; Jin-Feng Hu (Phytochemistry, 2024)

Fabrication of a family of porous azo polymers with multifunctional adsorption and separation performances - Yu Liu; Jun-Hong Jian; Jian Luan; Xiao-Sa Zhang; Ze-Bang Sun; Hong-Xiao Liu; Wen Yang; Wen-Ze Li (Journal of Environmental Chemical Engineering, 2024)

Deciphering the pivotal material properties of perovskite for hydrogen production in tar catalytic cracking - Wang-mi Chen; Bei-dou Xi; Mei-ying Ye; Ming-xiao Li; Jia-qi Hou; Yu-fang Wei; Cheng-ze Yu; Fan-hua Meng (Fuel, 2024)

Research on temperature measurement model of loose coal considering humidity using acoustic wave method - Gao-yang Qu; Jun Deng; Shuai-jing Ren; Cai-ping Wang; Ze-yang Song; Jin-rui Wang; Yu Xu; Xia-qi Zhao (Fuel, 2024)

Simultaneous mitigation of heterocyclic aromatic amines and advanced glycation end products in roasted beef patties by plasma-activated water: Effects and mechanisms - Chen-Xia Zhang; Xiao-Huan Wang; Chao-Yi Xue; Yang Chen; Ze-Ning Zhang; Yu-Xiang Ma; Xue-De Wang; Hua-Min Liu; Mao-Mao Zeng (Food Chemistry, 2024)

Sustainably sourced and DOPO-derived triols as hardeners for epoxy thermosets: A promising solution to synchronously improve flame retardancy, mechanical strength and toughness - Ze-Tao Xiao; Guan-Long Wu; Tian-Mo Yang; Yu Li; Yuan Hu; Manfred Döring; Xin Wang (Chemical Engineering Journal, 2024)

Screen-printed high loading flexible Zn-PANI battery - Runfeng Yu; Yunfei Xu; Xuxian Liu; Guoxin Zhang; Huiping Du; Ze Yang; Yaqun Wang (Chemical Engineering Journal, 2024)

Pure-phase two-dimensional perovskite capping layer enables high-performance and durable carbon-based photovoltaics - Shouye Dai; Huaiman Cao; Walid Sharmoukh; Yue Qiang; Liangyu Zhao; Yulong Chen; Yuxin Li; Hani Nasser Abdelhamid; Nima Taghavinia; Ze Yu (Chemical Engineering Journal, 2024)

Chemical constituents from Elephantopus scaber L. and their chemotaxonomic significant - Ze-Ming Wu; Mei-Ya Lian; Xiao-Yu Han; Ming Bai; Shao-Jiang Song (Biochemical Systematics and Ecology, 2024)

Identification of systemic nitrogen signaling in foxtail millet (Setaria italica) roots based on split-root system and transcriptome analysis - Xin-Li Yao; Yu-Ze Wang; Hui-Xin Meng; Ming-Hua Zhang; Xuan Zhou; Xue-Ting Kang; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; et al. (Plant Cell Reports, 2024)

Influence of Different Stages of Post-Traumatic Elbow Joint Capsule Healing on Pronation Movement - Fang Wang; Xin-Jie Chang; Ming-Xin Li; Ming-Ze Zhou; Bo-Tian Tian; Jian-Guo Zhang; Yu-Bo Fan (Journal of Medical and Biological Engineering, 2024)

Genome-wide Analysis of Developmental Stage-specific Transcriptome in Spodoptera litura for the Identification of Effective Control Method - Fei-Feng Wang; Peng Qin; Meng-Ke Zhang; Ze-En Xiong; Andrew G. S. Cuthbertson; Sulaiman Ali Alharbi; Sajid Fiaz; Saleh Alfarraj; Mohammad Javed Ansari; Farrukh Azeem; Jian-Yu Meng; Wen Sang (Journal of Crop Health, 2024)

Insights into ACO genes across Rosaceae: evolution, expression, and regulatory networks in fruit development - Yuxin Zhang; Yirong Zhang; Ze Yu; Hanyu Wang; Boya Ping; Yunxiao Liu; Jiakai Liang; Fengwang Ma; Yangjun Zou; Tao Zhao (Genes & Genomics, 2024)

Analysis of growth inhibition of continuously planted Casuarina equisetifolia in relation to characteristic soil microbial functions and nutrient cycling - Yu-Hua Wang; Lei Hong; Jian-Juan Li; Qing-Xu Zhang; Ai-Qi Wang; Shao-Xiong Lin; Ming-Yue Hu; Yi-Ling Chen; Wen-Xiong Lin; Hai-Bin Wang; Ze-Yan Wu (Applied Soil Ecology, 2024)

The immunoadjuvant effects of interleukin-8 on Aeromonas veronii inactivated vaccine in largemouth bass (Micropterus salmoides) - Shun Yang; Qian-Rong Liang; Dao-Le Liu; Ze-Sheng Zhang; Yu-Hong Yang; Xiao-Fei Yao; Hui Fei (Aquaculture International, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

The effectiveness of gliding arc discharge plasma in sterilizing artificial seawater contaminated with Vibrio parahaemolyticus - Meng-Ru Du; Yu-yi Guo; Han-ze Wei; Yu-pan Zhu; Rong-rong Liu; Ruo-nan Ma; Fu-kun Shi; Jin-song Guo; Jie Zhuang (Journal of Hazardous Materials, 2024)

Solidago canadensis enhances its invasion by modulating prokaryotic communities in the bulk soil - Wen-Tao Qiao; Yong-Feng Wang; Xue-Yan Hou; Dao-Lin Du; Ze-Yu Li; Xin-Yu Wang (International Biodeterioration & Biodegradation, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Exogenous sulfur application can effectively alleviate iron deficiency yellowing in peanuts and increase pod yield - Xiao-yan Zhang; Wen-feng Hou; Ze-chang Gou; Shu-ran Jia; Han Li; Qiang Gao; Xiao-yu Li (European Journal of Agronomy, 2024)

Construction of an anti-anionic-depletion layer to mitigate the tip deposition effect for dendrite-free zinc anode - Xiaohui Li; Dan Qiu; Qiancheng Zhou; Ze Yang; Xing Zhou; Wenping Wang; Chenchen Wei; Ting Zou; Ying Yu (Chemical Engineering Journal, 2024)

Design and synthesis of ligustrazine derivatives as potential anti-Alzheimer’s agents - Xu-fei Chen; Shan-shan Li; Yu-jun Bai; Ze-feng Zhao; Ya-jun Bai; Gu Gong; Xi-rui He; Xiao-hui Zheng (Natural Product Research, 2024)

Age-related alterations in vortex veins on indocyanine green angiography - Chen-Xi Cai; Shan-Shan Yu; Xiao-Mei Xiong; Bing-Qian Liu; Zhen-Qiang Lin; Qiang Wang; Jin-Li Cui; Ze-Hao Liu; Tao Li; Lin Lu; Ying Lin (GeroScience, 2024)
To determine age-related alterations in vortex veins in healthy subjects. A total of 228 healthy subjects (aged 4 to 86 years) were recruited and divided into four groups (G1, <21 years; G2, 21–40 years; G3, 41–60 years; and G4, 61–86 years). The clinical characteristics of the participants were recorded, and parameters including the number of vortex vein roots (NVVR), the central vortex vein diameter (CVVD), the mean root area of the vortex vein (MRAVV), and the weighted mean of the thickest branch diameter (WMTBD) were obtained by marking the vortex veins on indocyanine green angiography (ICGA). The NVVR in the age group over 60 years old was significantly lower than that in other age groups ( P < 0.05). The CVVD, MRAVV, and WMTBD of all age groups increased with increasing age ( P < 0.05). The NVVR was unevenly distributed among the quadrants ( P < 0.001). The proportions of type four vortex veins (complete systems including ampulla) and anastomotic branches of the vortex veins were significantly increased in elderly participants over 50 years of age ( P < 0.05). Subfoveal choroidal thickness was significantly correlated with age, NVVR, CVVD and MRAVV ( P < 0.05). This is the first study to reveal age-related alterations in vortex veins on ICGA in a healthy population. Aging may lead to partial vortex occlusion and residual vortex dilation. As age increases, anastomotic branches increasingly appear between the originally independent vortex veins. Translational relevance: Aging may lead to partial vortex occlusion and residual vortex dilation.

Treating waste with waste: adsorption behavior and mechanism of phosphate in water by modified phosphogypsum biochar - Li-li Shan; Ruo-shan Wang; Hai-tao Lai; Ze-bing Zhu; Yu Chen; Zhu-ye Ni; Chang-long Pang; Qiu-zhuo Zhang (Environmental Science and Pollution Research, 2024)

Association between residential greenness and incident delirium: A prospective cohort study in the UK Biobank - Qida He; Mengtong Sun; Yu Wang; Guoxian Li; Hanqing Zhao; Ze Ma; Zhaolong Feng; Tongxing Li; Qiang Han; Na Sun; Linyan Li; Yueping Shen (Science of The Total Environment, 2024)

Behavioral events and functional analysis of bursicon signal during adult eclosion in the 28-spotted larger potato ladybird - Wen-Ze Li; Yi-Kuan Wu; Yu-Xing Zhang; Lin Jin; Guo-Qing Li (Pesticide Biochemistry and Physiology, 2024)

Tectochrysin ameliorates dextran sulfate sodium-induced chronic colitis by regulating the intestinal flora and inflammatory responses - Qifeng Yu; Shiguang Yang; Yujiao Han; Xiang Wang; Ningbo Xiao; Ze Yu; Jinliang Dong (Food Bioscience, 2024)

Genome-wide identification, characterization, molecular evolution and expression profiling analysis of scavenger receptors in black rockfish (Sebastes schlegelii) - Zhentao Chen; Xuangang Wang; Gan Yu; Jingrun Pu; Xuechen Li; Ze Tao; Zhixiang Duan; Fan Zhang; Ping Han; Hengshun Li; Haiyang Yu (Fish & Shellfish Immunology, 2024)

Different mechanisms for enhanced ocean response and feedback during sequential super typhoons - Wang Huipeng; Li Jiagen; Song Junqiang; Leng Hongze; Ren Kaijun; Wang Huizan; Zhang Ze; Wang Hanshi; Wang Chunming; Yu Jie; Yang Xiangrong (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Synergetic catalysis of bimetallic sites in CoNi alloys in-situ encapsulated N-doped CNTs to accelerate sulfur redox kinetics for lithium-sulfur batteries - Jia Li; Guixiang Zhong; Jingyi Zhou; Shouyu Hong; Ji Yu; Zhenyu Yang; Ze Zhang (Chemical Engineering Journal, 2024)

Electrocatalytic nitrogen reduction to ammonia at low overpotentials based on tungsten carbide doped by non-precious metal single cobalt atoms - Ya Gao; Meng-Jiao Zhu; Xian-He Liu; Guo-Liang Dai; Yi-Wen Zhou; Ze-Da Meng; Li Luo; Tian Gan; Feng Chen; Yu-Yang Zhou; Wen-Wen Deng; Shou-Qing Liu (Chemical Engineering Journal, 2024)

Mitigation Effect of Exogenous Dopamine Treatment on Downy Mildew-Infected Cucumber - Ze-Yu Ji; Ze-Yu Liu; Li-Ming Shi; Xin-Yu Lu; Yu-Ying Han; Yan Sun (Journal of Plant Growth Regulation, 2024)

Calycosin inhibited MIF-mediated inflammatory chemotaxis of macrophages to ameliorate ischemia reperfusion-induced acute kidney injury - Hong-Lian Wang; Ze Peng; Yu-Qing Li; Yi-Xuan Wang; Jian-Chun Li; Rui-Zhi Tan; Hong-Wei Su; Hong-Ping Shen; Chang-Ying Zhao; Jian Liu; Li Wang (Inflammation Research, 2024)

Development and implementation of an advanced shipborne integrated platform for water quality inspection - Chao Li; Yu-Ze Song; Hui-Min Si (Frontiers in Marine Science, 2024)
Monitoring the quality of marine water is crucial for ensuring the health and sustainability of marine ecosystems. The conventional monitoring approach involves manual sampling using a water sampler, followed by packaging the water samples in plastic bottles and transporting them to a terrestrial laboratory for analysis. However, this method is time consuming, labor intensive, and cannot provide real-time data for addressing unforeseen circumstances. In response to these challenges, an advanced shipborne integrated platform for water quality inspection (ASIPWQI) has been proposed and implemented. This system automates the collection of multi-layer seawater samples in the vertical profile, conducts online measurements of monitoring elements, and provides real-time measurement data. In multiple sea trials, ASIPWQI successfully conducted on-site collection and measurement of a significant number of samples, meeting the water quality monitoring requirements in China’s nearshore waters. Comparative analysis of the laboratory measurement results for nutrients, heavy metals, and total phosphorus and nitrogen in water samples collected using automatic and manual methods revealed no significant differences between the two sampling approaches and demonstrated strong correlation. Further analysis using practical relative error (PRE) statistical methods showed that the data rate of most monitoring elements with relative errors less than 10% was higher than 70%, with nitrite, silicate, and phosphate even exceeding 90%. This indicate that ASIPWQI has excellent stability and applicability, offering a viable alternative to traditional manual sampling and laboratory testing. This innovation makes water quality monitoring significantly more efficient.

Low energy-consumption oriented membrane fouling control strategy in anaerobic fluidized membrane bioreactor - Lu Liu; Ze Guo; Yihe Wang; Linlin Yin; Wei Zuo; Yu Tian; Jun Zhang (Chemosphere, 2024)

Transformation of metoprolol in UV/PDS process: Role and mechanisms of degradation and polymerization - Sui-Qin Yang; Rui-Qiu Ye; Yu-Hong Cui; Zheng-Qian Liu; Kai Sun; Yu-Ze Yu (Journal of Hazardous Materials, 2024)

A systematic review of biochar aging and the potential eco-environmental risk in heavy metal contaminated soil - Xin-Xian Long; Ze-Ning Yu; Shao-wen Liu; Ting Gao; Rong-Liang Qiu (Journal of Hazardous Materials, 2024)

C-type lectin 12B/4E of black rockfish (Sebastes schlegelii) macrophages as pattern recognition receptors in the antibacterial mechanism of exploration - Zhixiang Duan; Fan Zhang; Xuangang Wang; Hengshun Li; Dianyang Zhou; Qiannan Chen; Ze Tao; Zhentao Chen; Gan Yu; Haiyang Yu (Fish & Shellfish Immunology, 2024)

Exploring efficient strategies for air quality improvement in China based on its regional characteristics and interannual evolution of PM2.5 pollution - Xin-ze Geng; Jia-tian Hu; Zi-meng Zhang; Zhi-ling Li; Chong-jun Chen; Yu-long Wang; Zhi-qing Zhang; Ying-jie Zhong (Environmental Research, 2024)

Orthorhombic K3V3(PO4)4: A low-temperature cathode material for potassium-ion batteries - Rui-Jie Luo; Chong-Yu Du; Cui Ma; Jie Zeng; Xuan Xu; Zhe Qian; Zhe Mei; Zi-Ting Zhou; Ze-Yu Zhu; Yong-Ning Zhou (Chemical Engineering Journal, 2024)

Cu-based bubble and ion sieve for ampere-level hydrogen evolution - Si-Wei Yan; Chuan-Qi Cheng; Fei-Fei Zhang; Ze-Yu Zhang; Kui Lin; Peng-Fei Yin; Rui Zhang; Jing Yang; Cun-Ku Dong; Jing Mao; Hui Liu; Xi-Wen Du (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Combined collection systems of sewage and rainfall runoff seriously affect the spatial distributions of natural estrogens and their conjugates in river water: Insights from the Pearl River of China - Jia-Le Wu; Ze-hua Liu; Qing-guang Ma; Yi-ping Wan; Zhi Dang; Yun Liu; Yu Liu (Water Research, 2024)

Distribution, migration patterns, and food chain human health risks of endocrine-disrupting chemicals in water, sediments, and fish in the Xiangjiang River - Ze Liao; Yu Jian; Jing Lu; Yilin Liu; Qinyao Li; Xunzhi Deng; Yin Xu; Qiuping Wang; Yuan Yang; Zhoufei Luo (Science of The Total Environment, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Annamiacids A and B: Two dissymmetric bis-diterpenes containing a rare ketal-γ-lactone motif from Podocarpus annamiensis and their inhibitory effects on ATP-citrate lyase - Chi Song; Ze-Yu Zhao; Jin-Xin Zhu; Yi Zang; Juan Xiong; Jia Li; Jin-Feng Hu (Phytochemistry Letters, 2024)

First record of the late Famennian conodonts in Qamdo, Tibet and their biostratigraphic implications - Yu-Ze Huang; Wen Guo; Wei Lin; Ping-Cuo Zhaxi; Le Yao; Ke-Yi Hu; Qiu-Lai Wang; Yu-Ping Qi (Palaeoworld, 2024)

Reactive oxygen species (ROS) modulate nitrogen signaling using temporal transcriptome analysis in foxtail millet - Hui-Xin Meng; Yu-Ze Wang; Xin-Li Yao; Xin-Ran Xie; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; Jia-Gang Wang (Plant Molecular Biology, 2024)

Fer-1 Protects against Isoflurane-Induced Ferroptosis in Astrocytes and Cognitive Impairment in Neonatal Mice - Peng Zhang; Xiaotong Shi; Danyi He; Yu Hu; Yongchao Zhang; Youyi Zhao; Sanxing Ma; Shuhui Cao; Meiting Zhai; Ze Fan (Neurotoxicity Research, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

Protective effect of resveratrol on nickel-refining fumes-induced inflammatory damage - Yu-Lin Pan; Rui-Ze Wu; Yao Fu; Rui Xin; Yong-Hui Wu (Cell Biochemistry and Biophysics, 2024)

Identification of SNPs and candidate genes associated with growth using GWAS and transcriptome analysis in Coilia nasus - Yue Yu; Shi-Ming Wan; Shuang-Meng Zhang; Jun-Qi Liu; Ai-Li Sun; Yao Wang; Yong-Fu Zhu; Shu-Xin Gu; Ze-Xia Gao (Aquaculture, 2024)

Deconjugation potentials of natural estrogen conjugates in sewage and wastewater treatment plant: New insights from model prediction and on-site investigations - Jun Zhang; Ze-hua Liu; Jia-le Wu; Yu-ting Ding; Qing-guang Ma; Waseem Hayat; Yun Liu; Peng-jie Wang; Zhi Dang; Bruce Rittmann (Science of The Total Environment, 2024)

Quantum spin driven Yu-Shiba-Rusinov multiplets and fermion-parity-preserving phase transition in K3C60 - Shu-Ze Wang; Xue-Qing Yu; Li-Xuan Wei; Li Wang; Qiang-Jun Cheng; Kun Peng; Fang-Jun Cheng; Yu Liu; Fang-Sen Li; Xu-Cun Ma; Qi-Kun Xue; Can-Li Song (Science Bulletin, 2024)

Highly modified cephalotane-type diterpenoids from Cephalotaxus fortunei var. alpina and C. sinensis - Zhan-Peng Ge; Jin-Biao Xu; Peng Zhao; Mai Xiang; Yu Zhou; Ze-Min Lin; Jian-Ping Zuo; Jin-Xin Zhao; Jian-Min Yue (Phytochemistry, 2024)

NUFIP1-engineered exosomes derived from hUMSCs regulate apoptosis and neurological injury induced by propofol in newborn rats - Wen Sun; Pengyue Zhao; Shidong Hu; Zhenting Zhao; Boyan Liu; Xingpeng Yang; Jiaqi Yang; Ze Fu; Songyan Li; Wenli Yu (NeuroToxicology, 2024)

Oxidation of chromium(Ⅲ): A potential risk of using chemical oxidation processes for the remediation of 2-chlorophenol contaminated soils - Jie Yu; Jiang Yu; Siwei Deng; Zhi Huang; Ze Wang; Weiwei Zhu; Xueling Zhou; Longyu Liu; Donghai Wu; Hanyi Zhang (Journal of Environmental Management, 2024)

Petrogenesis and tectonic implications of late Permian andesites from Rongzharinian, northern Qiangtang, Tibet - Jiang-Yu Qi; Sheng-Sheng Chen; Yuan-Yuan Cao; Ze Zhang (Journal of Asian Earth Sciences, 2024)

Regimes of global and national oil palm cultivations from 2001 to 2018 - Hao Yu; Dongjie Fu; Ze Yuan; Jiasheng Tang; Ye Xiao; Lu Kang; Vincent Lyne; Fenzhen Su (Global Environmental Change, 2024)

A numerical simulation-based ANN method to determine the shear strength parameters of rock minerals in nanoscale - Qing Lü; Shi-hao Liu; Wei-ze Mao; Yang Yu; Xu Long (Computers and Geotechnics, 2024)

Regulating photoluminescence through single-crystal-to-single-crystal transformation of solvent-containing zero-dimensional hybrid metal halide isomers - Ying-Chen Peng; Jian-Ce Jin; Sheng-Hua Zhou; Hao-Wei Lin; Dan-Dan Huang; Zhong-Hua Deng; Yu Dong; Hao-Jie Xu; Ke-Zhao Du; Ze-Ping Wang; Xiao-Ying Huang (Chemical Engineering Journal, 2024)

Nutrients recycled by a small omnivorous fish facilitate the growth and change the stoichiometric contents of submerged macrophytes - Jinlei Yu; Lusheng Ma; Sipeng Yao; Zhigang Mao; Hu He; Xiaolong Huang; Ze Ren; Zhengwen Liu; Erik Jeppesen (Hydrobiologia, 2024)

SCREENES: Enhancing non-uniform sampling reconstruction for symmetrical NMR spectroscopy - Ze Fang; Bo Chen; Chengda Huang; Yifei Yuan; Yao Luo; Liubin Wu; Yida Chen; Yuqing Huang; Yu Yang; Enping Lin; Zhong Chen (Analytica Chimica Acta, 2024)

Preparation of geopolymer based on municipal solid waste incineration fly ash-phosphorus slag and its function for solidification of heavy metals - An Sai; Wang Baomin; Chen Wenxiu; Yu Ze; Fan Chengcheng (Waste Management, 2024)

PI3K/AKT mediated De novo fatty acid synthesis regulates RIG-1/MDA-5-dependent type I IFN responses in BVDV-infected CD8+T cells - Shan-shan Liu; Tong-tong Bai; Tao-lin Que; An Luo; Yu-xin Liang; Yu-xin Song; Tian-yi Liu; Jin-wei Chen; Jing Li; Nan Li; Ze-chen Zhang; Nan-nan Chen; et al. (Veterinary Microbiology, 2024)

Physical model embedding-based generative adversarial networks for unsupervised fault detection of underwater thrusters - Shuang Gao; Ze Yu; Zhiyao Zhang; Chen Feng; Tianhong Yan; Bo He; Enrico Zio (Ocean Engineering, 2024)

Latest Devonian–Early Mississippian conodont biostratigraphy in the Naqing section, Guizhou, South China - Yu-Ze Huang; Yu-Ping Qi; Qiu-Lai Wang; Le Yao; Ji-Tao Chen (Palaeoworld, 2024)

Effect of anions on sonochemical degradation of PPCPs and their DBPs formation potential - Yu-qiong Gao; Ke-xuan Li; Qian Zeng; Fu-xiang Tian; Ze-ning Fan; Gang-yi Xing; Nai-yun Gao (Journal of Water Process Engineering, 2024)

A new α-amylase inhibitory peptide from Gynura medica extract - Ke Ma; Ze-Yu Su; Yuan-Hang Cheng; Xue-Peng Yang (Food Chemistry, 2024)

Phosphorus-supplemented seawater–wastewater cyclic system for microalgal cultivation: Production of high-lipid and high-protein algae - Meng Ma; Liqun Jiang; Zhen Xie; Mingyan Liu; Huiying Chen; Ze Yu; Haiyan Pei (Bioresource Technology, 2024)

Molecular identification of DNA barcoding of Leguminous toxic species and quantitative analysis by ELISA kits - Jie Wang; Shuangyu Wang; Fenglin Sun; Chang Liu; Jinquan Zhao; Hongwei Yu; Xiaojing Lv; Ze Liu; Shuhua Bu; Weisen Yu (Plant Biotechnology Reports, 2024)

Growth of Scenedesmus obliquus in anaerobically digested swine wastewater from different cleaning processes for pollutants removal and biomass production - Xiao-Bo Tan; Ze-Yuan Zhao; Hui Gong; Tao Jiang; Xin-Ping Liu; Jian-Yu Liao; Ya-Lei Zhang (Chemosphere, 2024)

Stabilization of heavy metals in municipal solid waste incineration fly ash using organic chelating agents: Insight into risk assessment and function mechanism - Ze Zhang; Yang Yu; Yi Rao; Ying Wang; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Amirhomayoun Saffarzadeh; Xiaona Wang; Chuanfu Wu; Qunhui Wang (Science of The Total Environment, 2024)

Modulator of TMB-associated immune infiltration (MOTIF) predicts immunotherapy response and guides combination therapy - Zheng-Yu Qian; Yi-Qian Pan; Xue-Xin Li; Yan-Xing Chen; Hao-Xiang Wu; Ze-Xian Liu; Martin Kosar; Jiri Bartek; Zi-Xian Wang; Rui-Hua Xu (Science Bulletin, 2024)

Terricoxanthones A–E, unprecedented dihydropyran-containing dimeric xanthones from the endophytic fungus Neurospora terricola HDF-Br-2 associated with the vulnerable conifer Pseudotsuga gaussenii - Hao-Wei Chen; Xi-Ying Wu; Ze-Yu Zhao; Zi-Qi Huang; Xin-Sheng Lei; Guo-Xun Yang; Jiyang Li; Juan Xiong; Jin-Feng Hu (Phytochemistry, 2024)

Impact of deoxynivalenol on rumen function, production, and health of dairy cows: Insights from metabolomics and microbiota analysis - Jia-nan Dong; Zhi-kun Zhao; Zhan-qing Wang; Song-ze Li; Yong-peng Zhang; Zhe Sun; Gui-xin Qin; Xue-feng Zhang; Wei Zhao; Natnael Demelash Aschalew; Tao Wang; Yu-guo Zhen (Journal of Hazardous Materials, 2024)

Growth of Ag/g-C3N4 nanocomposites on nickel foam to enhance photocatalytic degradation of formaldehyde under visible light - Ze Wang; Zhi Huang; Jiang Yu; Xiao Shao; Weidong Peng; Jie Yu; Yinying Jiang (Journal of Environmental Sciences, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Retraction Note: MEK/ERK pathway activation by insulin receptor isoform alteration is associated with the abnormal proliferation and differentiation of intestinal epithelial cells in diabetic mice - Hui Ouyang; Hong-Sheng Yang; Tao Yu; Ti-Dong Shan; Jie-Yao Li; Can-Ze Huang; Wa Zhong; Zhong-Sheng Xia; Qi-Kui Chen (Molecular and Cellular Biochemistry, 2024)

Correction to: Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2024)

Liriogerphines E–U, further unique sesquiterpene-alkaloid hybrids from the rare Chinese tulip tree - Yu-Hang He; Hong Xiang; Qi-Xiu Li; Yu-Fei Wu; Ze-Xin Jin; Jin-Feng Hu; Yi-Cheng Mao; Juan Xiong (Phytochemistry, 2024)

Experimental and simulation study on the combustion characteristics of ammonia/n-dodecane mixtures - Yu Sun; Yejian Qian; Ze Sun; Zhen Gong; Xiang Gu (Fuel, 2024)

The role of a small molecular dipole moment for efficient non-doped deep blue thermally activated delayed fluorescence emitters - Hong-Ji Tan; Jie-Rong Yu; Zhi-Zhong Lin; Guo-Xi Yang; Zhi-Qiang Long; Ying-Lan Deng; Ze-Lin Zhu; Xian-Kai Chen; Jing-Xin Jian; Qing-Xiao Tong; Chun-Sing Lee (Chemical Engineering Journal, 2024)

Increasing carbon to nitrogen ratio promoted anaerobic ammonia-oxidizing bacterial enrichment and advanced nitrogen removal in mainstream anammox system - Wenke Zhang; Jianhua Zhang; Deshuang Yu; Ze Zhu; Yuanyuan Miao (Bioresource Technology, 2024)

C-methylated homoisoflavanones from the rhizomes of polygonatum cyrtonema and their chemotaxonomic significance - Jiang Wan; Guangyao Mei; Jun-Xia Ma; Ze-Yu Zhao; Can Wang; Ziping Zhu; Junmin Li; Jin-Feng Hu (Biochemical Systematics and Ecology, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Simultaneous realization of heavy metal Cd solidification and chloride separation in municipal solid waste incineration fly ash: Mechanism and DFT analysis - Fuli Liu; Ze Liu; Yu Gao; Rui Liu; Dongmin Wang; Baomin Wang; Yan You (Chemosphere, 2024)

Binding interaction of environmental DNA with typical emerging perfluoroalkyl acids and its impact on bioavailability - Chao Qin; Lei Xiang; Yi-Ze Wang; Peng-Fei Yu; Can Meng; Yan-Wen Li; Hai-Ming Zhao; Xiaojie Hu; Yanzheng Gao; Ce-Hui Mo (Science of The Total Environment, 2024)

Multiomics analyses of two Leonurus species illuminate leonurine biosynthesis and its evolution - Peng Li; Meng-Xiao Yan; Pan Liu; Dan-Jie Yang; Ze-Kun He; Yun Gao; Yan Jiang; Yu Kong; Xin Zhong; Sheng Wu; Jun Yang; Hong-Xia Wang; et al. (Molecular Plant, 2024)

Phylogenomics and divergence pattern of Polygonatum (Asparagaceae: Polygonateae) in the north temperate region - Yu-Qian Qin; Meng-Hua Zhang; Chu-Yun Yang; Ze-Long Nie; Jun Wen; Ying Meng (Molecular Phylogenetics and Evolution, 2024)

How human capital prevents intergenerational poverty transmission in rural China: Evidence based on the Chinese general social survey - Hong Chen; Jia Yu; Ze Zhang; Yuheng Li; Lijian Qin; Mingshuai Qin (Journal of Rural Studies, 2024)

Astronomically forced late Paleocene-early Eocene climate variability in the Subei Basin, East China - Juan Liu; Xiaodong Ma; Yongchao Lu; James G. Ogg; Wenrui Yu; Zhiqi Qian; Ze Zhang; Hao Tai; Zhanhong Liu; David B. Kemp; Chunju Huang (Global and Planetary Change, 2024)

Migration pathway and solidification mechanism of heavy metal Pb during the conversion of municipal solid waste incineration fly ash into ettringite and simultaneously purification of chloride salts solution process - Fuli Liu; Ze Liu; Yu Gao; Rui Liu; Dongmin Wang; Baomin Wang; Yan You (Environmental Pollution, 2024)

Modulating the microenvironment of catalytic interface with functional groups for efficient photocatalytic degradation of persistent organic pollutants - Yujun Ju; Ze Wang; Hailong Lin; Ruien Hou; Hua Li; Zhe Wang; Ruitong Zhi; Xiaoquan Lu; Yu Tang; Fengjuan Chen (Chemical Engineering Journal, 2024)

Deciphering the bioavailability of dissolved organic matter in thermophilic compost and vermicompost at the molecular level - Dingmei Wang; Liwen Mai; Zhen Yu; Kongtan Wang; Ze Meng; Xiongfei Wang; Qinfen Li; Jiacong Lin; Dongming Wu (Bioresource Technology, 2024)

Hydrometeorological-modeling-based analysis and risk assessment of a torrential rainfall flash flood in a data deficient area in Wenchuan County, Sichuan Province, China - En-Ze Jin; Yu-Ge Wang; Ze-Xing Xu; Xu-Feng Yan; Xie-Kang Wang (Stochastic Environmental Research and Risk Assessment, 2024)

The stable operation of nitritation process with the continuous granular sludge-type reactor and microbial community analysis - Hongjun Zhao; Yan Guo; Ze Zhang; Haishu Sun; Xiaona Wang; Shuang Li; Jianbo Liao; Yu-You Li; Qunhui Wang (Chemosphere, 2023)

Analysis of Edwardsiella piscicida induced transcriptome profiles in macrophages of black rockfish (Sebastes schlegelii) provides insights into the trigger of pyroptosis - Xuangang Wang; Xiangfu Kong; Hengshun Li; Ying Chen; Ze Tao; Fan Zhang; Zhixiang Duan; Zhentao Chen; Jinxiang Liu; Quanqi Zhang; Haiyang Yu (Aquaculture, 2023)

Efficiently regenerating spent lithium battery graphite anode materials through heat treatment processes for impurity dissipation and crystal structure repair - Guo-Qing Yu; Ming-Zhuang Xie; Zhi-Hao Zheng; Ze-Gang Wu; Hong-Liang Zhao; Feng-Qin Liu (Resources, Conservation and Recycling, 2023)

Analysis of spatial structure and filling mechanism of a paleokarst channel against a background of denudation: A case study in the Tahe Oilfield, Tarim basin - Chenhe Zhang; Zhiqian Gao; Tailiang Fan; Debin Yang; Duan Wei; Jun Wu; Jinxian Liu; Huitao Zhang; Xinlei Zhang; Bo Li; Zhe Chang; Yu Gu; et al. (Marine and Petroleum Geology, 2023)

Long-term grazing improved soil chemical properties and benefited community traits under climatic influence in an alpine typical steppe - Yu-Wen Zhang; Ze-Chen Peng; Sheng-Hua Chang; Zhao-Feng Wang; Duo-Cai Li; Yu-Feng An; Fu-Jiang Hou; Ji-Zhou Ren (Journal of Environmental Management, 2023)

Dual-mode Janus Structural-Color films toward an integrated sensing device with synergistic optical and electrical outputs - Zi-Li Wang; Ze-Peng Deng; Fang Wang; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Mechanism of the toxic effects of tetracycline on blood meal digestion in Haemaphysalis longicornis - Yan-Kai Zhang; Si-Si Li; Chen Yang; Yu-Fan Zhang; Jing-Ze Liu (Experimental and Applied Acarology, 2023)

Synergistic leaching process for ion-exchange ammonium from weathered crust elution deposited rare earth tailings with potassium magnesium compound eluent - Xiaoju Li; Junxia Yu; Xiaodi Li; Guoping Song; Ze Ouyang; Rong Wang; Zhenyue Zhang; Chunqiao Xiao; Ruan Chi (Environmental Science and Pollution Research, 2023)

Mid-Holocene pine forest expansion caused by the weakening of the East Asian winter monsoon and linked to climate change in the North Atlantic region - Jing Wu; Wei-he Ren; Qiao-yu Cui; Yu-zhen Ma; Laurent Marquer; Hong-wei Meng; Ze-yang Zhu; Guo-qiang Chu; Jia-qi Liu (Quaternary Science Reviews, 2023)

Zircon U–Pb geochronology, Hf–O isotopes and whole-rock geochemistry of A-type granitoids in Halajun, South Tienshan, NW China: Implications for subdivision, petrogenesis and tectonic settings - Tian-Chu Chen; Ming-Xing Ling; Yu-Long Liu; Ying Wei; Xi-Hui Cheng; Xiao-Yan Jiang; Shuo Xue; Ze-Bin Luo; Jiang-Hao Bai (Lithos, 2023)

Electrochemical oxidation treatment of reverse osmosis concentrated landfill leachate: Effect of operation parameters and evolution of dissolved organic matter - Ye-Chao Tian; Wen-Xiang Ji; Yu-Ze Han; Ze-Tao Wu; Hai-Ou Song; Ai-Min Li; Wen-Tao Li (Chemical Engineering Journal, 2023)

Thermal and electrical conductive 2D CuO evaporator for all-day steam generation - Ze-Yu Yang; Lu-Qi Liu; Shan-Qiu Liu; Gang Wang; Zhi-Xiang Zeng; Li-Jing Zhu (Chemical Engineering Journal, 2023)

Three-hourly PM2.5 and O3 concentrations prediction based on time series decomposition and LSTM model with attention mechanism - Yuan-yue Chu; Jian Yao; De-wen Qiao; Ze-yu Zhang; Chao-yong Zhong; Li-juan Tang (Atmospheric Pollution Research, 2023)

Nitrogen allocation for CO2 fixation promotes nitrogen use in the photosynthetic compensation of soybean under heterogeneous light after a pre-shading - Xin Sun; En-Ze Zhang; Liang Yu; Jun-Bo Du; Wen-Yu Yang (Physiology and Molecular Biology of Plants, 2023)

Ångstrom-scale silver particles ameliorate collagen-induced and K/BxN-transfer arthritis in mice via the suppression of inflammation and osteoclastogenesis - Ze-Hui He; Jing-Tao Zou; Xia Chen; Jiang-Shan Gong; Ya Chen; Ling Jin; Yi-Wei Liu; Shan-Shan Rao; Hao Yin; Yi-Juan Tan; Zun Wang; Wei Du; et al. (Inflammation Research, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

Simultaneous determination of twelve natural estrogens in dairy milk using liquid–liquid extraction and solid-phase extraction coupled with gas chromatography-mass spectrometry - De-ming Kong; Zhao Tang; Ze-hua Liu; Zhi Dang; Peng-ran Guo; Yu-mei Song; Yu Liu (Environmental Science and Pollution Research, 2023)

The evolution of insecticide resistance in the white backed planthopper Sogatella furcifera (Horvath) of China in the period 2014–2022 - Ya-Ting Liu; Xin-Yu Song; Bin Zeng; Wen-Jing Zhang; Xing-Yu Chen; Ze-Rui Feng; Hua-Yang Yu; Cong-Fen Gao; Shun-Fan Wu (Crop Protection, 2023)

ID3 regulates progesterone synthesis in bovine cumulus cells through modulation of mitochondrial function - Zi-Bin Liu; Jia-Bao Zhang; Sheng-Peng Li; Wen-Jie Yu; Na Pei; Hai-Tao Jia; Ze Li; Wen-Fa Lv; Jun Wang; Nam-Hyung Kim; Bao Yuan; Hao Jiang (Theriogenology, 2023)

Inventory of cadmium-transporter genes in the root of mangrove plant Avicennia marina under cadmium stress - Lu-Dan Zhang; Ling-Yu Song; Ming-Jin Dai; Jin-Yu Liu; Jing Li; Chao-Qun Xu; Ze-Jun Guo; Shi-Wei Song; Jing-Wen Liu; Xue-Yi Zhu; Hai-Lei Zheng (Journal of Hazardous Materials, 2023)

Synthesis and CO2 adsorption performance of high Si/Al ratio DDR zeolites prepared from silica fume - Zhonghao Peng; Ze Liu; Yu Gao; Jiayu Liu; Dongmin Wang; Hongying Liu; Yanbo Zhang; Li Li (Journal of Environmental Chemical Engineering, 2023)

Fabrication of granular MOF@γ-Al2O3 composites as promising dual-function adsorbents for the efficient capture of iodine and dyes - Yu Liu; Jian-Peng Cui; Xiao-Sa Zhang; Ze-Bang Sun; Wen-Ze Li; Ai-Ai Yang; Jian Luan (Journal of Environmental Chemical Engineering, 2023)

Neoproterozoic tectonic transition from subduction to back-arc extension along the western Yangtze Block, South China: Petrological evidence of Nb-enriched basalts and arc-type intrusive rocks - Yu Zhu; Shao-cong Lai; Wan-li Xie; Jiang-feng Qin; Ren-zhi Zhu; Shao-wei Zhao; Min Liu; Fang-yi Zhang; Ze-zhong Zhang; Hang Yang (Gondwana Research, 2023)

Effect of dispersed species heterogeneity in carbon-based catalysts for near-infrared light-responsive synergistic antibacterial therapy - Yang Yang; Shudi Mo; Ze Zhang; Jingyu Sun; Jinghong Wen; Qilin Yu; Mingyang Liu (Chemical Engineering Journal, 2023)

p-Nrf2/HO-1 Pathway Involved in Methamphetamine-induced Executive Dysfunction through Endoplasmic Reticulum Stress and Apoptosis in the Dorsal Striatum - Tao Wei; Jun-Da Li; Yu-Jing Wang; Wei Zhao; Fan Duan; Yan Wang; Ling-Ling Xia; Zhao-Bin Jiang; Xun Song; Yu-Qiong Zhu; Wen-Yi Shao; Ze Wang; et al. (Neurotoxicity Research, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

Biodegradability enhancement of waste lubricating oil regeneration wastewater using electrocoagulation pretreatment - Li-li Shan; Zhao Tan; Yu Chen; Ruo-shan Wang; Meng Zhang; Chang-long Pang; Yu-Hong Cui; Zhi-min Liao; Hong-qiang Ma; Ze-bing Zhu (Environmental Science and Pollution Research, 2023)

Twelve natural estrogens and ten bisphenol analogues in eight drinking water treatment plants: Analytical method, their occurrence and risk evaluation - Zhao Tang; Ze-hua Liu; Hao Wang; Yi-ping Wan; Zhi Dang; Peng-ran Guo; Yu-mei Song; Sa Chen (Water Research, 2023)

Solidification/stabilization and risk assessment of heavy metals in municipal solid waste incineration fly ash: A review - Ze Zhang; Chutong Zhao; Yi Rao; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Xiaona Wang; Chuanfu Wu; Qunhui Wang (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

FDP-Na-induced enhancement of glycolysis impacts larval growth and development and chitin biosynthesis in fall webworm, Hyphantria cunea (Lepidoptera: Arctiidae) - Shengyu Zhang; Yu Zhang; Haifeng Zou; Xingpeng Li; Hang Zou; Ze Wang; Chuanshan Zou (Pesticide Biochemistry and Physiology, 2023)

The TRAF gene family in turbot (Scophthalmus maximus): Identification, characterization, molecular evolution and expression patterns analysis - Dianyang Zhou; Xuangang Wang; Hengshun Li; Ze Tao; Zhixiang Duan; Haiyang Yu (Fish & Shellfish Immunology, 2023)

Revolutionizing wound healing: Ultrashort pulse electric fields in seconds for highly aligned extracellular matrix and efficient cell migration - Xiao-Wei Xiang; Hao-Tian Liu; Wei Liu; Ze-Yao Yan; Yu-Lian Zeng; Ya-Jun Wang; Jing Liu; Yu-Chen Chen; Sai-Xi Yu; Cai-Hui Zhu; Xiao-Nan Tao; Chen Wang; et al. (Chemical Engineering Journal, 2023)

Integration of eQTL and GWAS analysis uncovers a genetic regulation of natural ionomic variation in Arabidopsis - Chaoqun Xu; Ling-Yu Song; Ying Zhou; Dong-Na Ma; Qian-Su Ding; Ze-Jun Guo; Jing Li; Shi-Wei Song; Lu-Dan Zhang; Hai-Lei Zheng (Plant Cell Reports, 2023)

Melatonin alleviates cisplatin-induced mice spermatogenesis defects - Zhu Peng; Wang Zhi Xin; Zhang Yu Sheng; Teng Zi; Liu Ya Nan; Wang Ze Lin; Liu Fu Jun; Liu Xue Xia (Reproductive Toxicology, 2023)

Facile engineering of metal–organic framework derived SnO2-ZnO composite based gas sensor toward superior acetone sensing performance - Hui Zhang; Shisong Guo; Wenjun Zheng; Haichao Wang; Hua-Yao Li; Mei-Hui Yu; Ze Chang; Xian-He Bu; Huan Liu (Chemical Engineering Journal, 2023)

Mesomechanical characteristics of rock failure under variable amplitude cyclic loading by DEM - Ze-han Liu; Jin Yu; Chong-hong Ren; De-fu Zhu; Xiao-qin Chen (Bulletin of Engineering Geology and the Environment, 2023)

Evaluation the role of soluble microbial products for denitrification sludge characteristic under starvation stress - Qian-Qian Zhang; Yan Yu; Jin-Ze Liu; Wen-Jing Fu; Jin-Yang Quan; Ying Chen; Jian-Qiang Zhao; Sha Wang; Ren-Cun Jin (Science of The Total Environment, 2023)

Seven undescribed compounds from the flower heads of Helianthus annuus L. - Jiaxuan Bai; Xianmei Piao; Yanli Wang; Xiaoling Cheng; Mingfeng Feng; Yongming Wang; Rong Fu; Jinna Zhao; Shufei Yu; Ze Li; Libo Wang; Jian Huang; et al. (Phytochemistry, 2023)

Elution of the residual water-soluble ammonium from the weathered crust elution-deposited rare earth tailings: Kinetics and mechanism - Xiaoju Li; Ze Ouyang; Zhanhui Li; Junxia Yu; Zhenyue Zhang; Xiaodi Li; Chunqiao Xiao; Ruan Chi (Minerals Engineering, 2023)

A dynamic SNS-PFEM with generalized-α method for hydro-mechanical coupled geotechnical problems - Ze-Yu Wang; Yin-Fu Jin; Zhen-Yu Yin; Yu-Ze Wang (Computers and Geotechnics, 2023)

Research on the blocking effect of baffle-net structure on rock avalanches: consider the influence of particle splashing - Yu-Zhang Bi; Dong-Po Wang; Shuai-Xing Yan; Qin-Ze Li; Si-Ming He (Bulletin of Engineering Geology and the Environment, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Squamabietenols A–F, undescribed abietane-O-abietane dimeric diterpenoids from the ornamental conifer Juniperus squamata and their ATP-citrate lyase inhibitory activities - Kai-Yuan Liang; Hao Li; Peng-Jun Zhou; Ze-Yu Zhao; Yi Zang; Juan Xiong; Jia Li; Jin-Feng Hu (Phytochemistry, 2023)

Meta-analysis reveals cyanotoxins risk across African inland waters - Xu Zhao; Ying Liu; Yu-Ming Guo; Chi Xu; Liang Chen; Geoffrey A. Codd; Jun Chen; Ying Wang; Pu-Ze Wang; Li-Wei Yang; Long Zhou; Yan Li; et al. (Journal of Hazardous Materials, 2023)

Microplastics exacerbate co-occurrence and horizontal transfer of antibiotic resistance genes - Xi Yu; Zhen-Chao Zhou; Xin-yi Shuai; Ze-jun Lin; Zhe Liu; Jin-yu Zhou; Yan-han Lin; Guang-shu Zeng; Zi-ye Ge; Hong Chen (Journal of Hazardous Materials, 2023)

Double-edged sword effect of nano-biochar for Cd2+ adsorption on zeolite - Xuewen Cao; Zhaofu Meng; Li Sheng; Xiaolong Hu; Teng Wang; Xiuxian Sun; Yong Yu; Ze Liu (Journal of Environmental Chemical Engineering, 2023)

Experimental research and model optimization of a novel mechanical vapor compression evaporation system driven by Roots steam compressor - Huafu Zhang; Zhentao Zhang; Lige Tong; Junling Yang; Li Wang; Xiaoqiong Li; Yu Zhang; Peng Xu; Ze Yu; Junhao Zhang (International Journal of Refrigeration, 2023)

Sex-specific effect of perfluoroalkyl substances exposure on liver and thyroid function biomarkers: A mixture approach - Ze Yang; Ruifang Liu; Hongbo Liu; Jiemin Wei; Xiaohui Lin; Mingyue Zhang; Yu Chen; Jingyun Zhang; Meiqing Sun; Zhe Feng; Jian Liu; Xiangyang Liu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Ultra-thin CoNi0.2P nanosheets for plastics and biomass participated hybrid water electrolysis - Xiao-Hui Wang; Ze-Nong Zhang; Zhe Wang; Yu Ding; Quan-Guo Zhai; Yu-Cheng Jiang; Shu-Ni Li; Yu Chen (Chemical Engineering Journal, 2023)

Association between urinary cadmium level and subclinical myocardial injury in the general population without cardiovascular disease aged ≥ 50 years - Yu-Jie Wu; Si-Bo Wang; Jia-Teng Sun; Ling-Feng Gu; Ze-Mu Wang; Bo Deng; Hao Wang; Lian-Sheng Wang (Environmental Science and Pollution Research, 2023)

Experimental Study on the Mechanical Damage and Deformation Failure of Water-bearing Coal Samples - Qiangling Yao; Liqiang Yu; Changhao Shan; Ze Xia; Ning Chen; Hongxin Xie; Liu Zhu (Mine Water and the Environment, 2023)

Imaging and detection of sulfite in acute liver injury with a novel quinoxaline-based fluorescent probe - Ze-Yang Hu; Xu-Yang Chen; Xue Yang; Ting Li; Yu-Shun Yang; Sheng-Jun Wang; Kai Wang; Zhi-Gang Hu (Analytica Chimica Acta, 2023)

Anthraquinones with potential antiproliferative activities from the fruits of Morinda citrifolia - Zhang-Yang Shen; Ying-Ying Zhao; Ze-Hua Qiao; Zhen Xie; Ruo-Qing Guan; Ze-Yu Liu; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu (Natural Product Research, 2023)

Distribution of polycyclic aromatic hydrocarbons in indoor/outdoor window films and the indoor film/air partition of northeastern Chinese college dormitories - Yu Sun; Li-Yan Liu; Lin-Lin Lv; Xi-Xi Zhou; Yu-Yan Luo; Jin-Ze Qu; Wan-Li Ma; Zi-Feng Zhang; Li Song; Li Wang; Yi-Fan Li (Chemosphere, 2023)

Unraveling the evolution of dissolved organic matter in full-scale A/A/O wastewater treatment process using size exclusion chromatography with PARAFAC and nonnegative matrix factorization analysis - Min-Hui Cai; Ye-Chao Tian; Ai-Min Li; Yan Li; Yu-Ze Han; Wen-Xiang Ji; Qing Zhou; Jun Li; Wen-Tao Li (Water Research, 2023)

Phosphatized microfossils from the Miaohe Member of South China and their implications for the terminal Ediacaran biodiversity decline - Qin Ye; Zhihui An; Yang Yu; Ze Zhou; Jun Hu; Jinnan Tong; Shuhai Xiao (Precambrian Research, 2023)

Effects of tetrasodium pyrophosphate coupled with soy protein isolate on the emulsion gel properties of oxidative myofibrillar protein - Jun Liu; Ze Yu; Wenru Xie; Lu Yang; Mingyun Zhang; Chunqiang Li; Jun-hua Shao (Food Chemistry, 2023)

Collocalia birds inspired Janus-structured bandage with strong wet tissue adhesion for rapid hemostasis and wound healing - Chao Hui; Yuan Gao; Bing-Yu Yan; Li-Qiang Ding; Tian-Cai Sun; Zhong Liu; Seeram Ramakrishna; Yun-Ze Long; Jun Zhang (Chemical Engineering Journal, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Expression pattern analysis of anti‐Mullerian hormone in testis development of pearlscale angelfish ( Centropyge vrolikii ) - Yan Xu; Zhao‐wei Zhong; Yan Feng; Ze‐yu Zhang; Lu‐lu Ao; Hongwei Liu; Yi‐lei Wang; Yong‐hua Jiang (Journal of Fish Biology, 2023)
In vertebrates, anti‐Mullerian hormone (Amh) secreted by Sertoli cells (SC) performs a pivotal function in male sex differentiation. Compared with that of higher vertebrates, the expression pattern of Amh is more diversified in fish. In this study, the full‐length complementary DNA (cDNA) of Amh in Centropyge vrolikii ( Cv‐Amh ) was cloned and analysed, which was 2,470 bp, including a 238 bp 5'UTR, a 1,602 bp ORF and a 633 bp 3'UTR; the similarity of Amh between Cv ‐Amh and other fish is relatively high. The quantitative real‐time PCR (qRT‐PCR) results of healthy tissues and gonads at sex reversal stages in C. vrolikii showed that the expression level of Amh in the testis was significantly higher than that in other tissues ( P Amh was weakly expressed in the vitellogenic stage ovary and perinucleolus stage ovary, but its expression significantly increased in the gonads at the hermaphroditic stage, and finally reached the highest in the pure testis after sexual reversal. The results of in situ hybridization indicated that the positive signal of Amh was strongly concentrated in SCs of testis. After Amh knockdown in the gonads, the effect on sex‐related genes was tested using qRT‐PCR. Among these, the expression of Dmrt1 , Cyp11a , Hsd11b2 , Sox8 and Sox9 significantly decreased, whereas that of Cyp19a , Sox4 , Foxl2 and Sox3 increased. These results suggested that Amh could be the pivotal gene in reproductive regulation in C. vrolikii , and the data will contribute to sex‐related research of C. vrolikii in the future.

Identification of potential necroinflammation-associated necroptosis-related biomarkers for delayed graft function and renal allograft failure: a machine learning-based exploration in the framework of predictive, preventive, and personalized medicine - Qing Bi; Ji-Yue Wu; Xue-Meng Qiu; Yu-Qing Li; Yu-Yao Yan; Ze-Jia Sun; Wei Wang (EPMA Journal, 2023)

Changes of dissolved organic matter fractions and formation of oxidation byproducts during electrochemical treatment of landfill leachates: Development of spectroscopic indicators for process optimization - Bi-Cun Jiang; Ye-Chao Tian; Ai-Min Li; Yu-Ze Han; Ze-Tao Wu; Chang Lu; Hai-Ou Song; Rong Ji; Wen-Tao Li; Gregory V. Korshin (Water Research, 2023)

Eliminating temporal correlation in quantum-dot entangled photon source by quantum interference - Run-Ze Liu; Yu-Kun Qiao; Han-Sen Zhong; Zhen-Xuan Ge; Hui Wang; Tung-Hsun Chung; Chao-Yang Lu; Yong-Heng Huo; Jian-Wei Pan (Science Bulletin, 2023)

Study on wave attenuation on a coral reef flat in SCS by in-situ measurement and simulation - Wenwei Chen; Xiaolong Liu; Zhiwen Cai; Ze Sun; Jun Yu; Haihua Zhang (Ocean Modelling, 2023)

Proteomic analysis reveals differential responsive mechanisms in Solanum nigrum exposed to low and high dose of cadmium - Ling-Yu Song; Xiang Liu; Lu-Dan Zhang; Wen-Jun Hu; Chao-Qun Xu; Jing Li; Shi-Wei Song; Ze-Jun Guo; Chen-Yang Sun; Han-Chen Tang; Ji-Cheng Wang; Xue-Yi Zhu; et al. (Journal of Hazardous Materials, 2023)

Association of occupational exposure to polycyclic aromatic hydrocarbons in workers with hypertension from a northeastern Chinese petrochemical industrial area - Yu Sun; Ze Kan; Zi-Feng Zhang; Li Song; Chao Jiang; Ji Wang; Wan-Li Ma; Yi-Fan Li; Li Wang; Li-Yan Liu (Environmental Pollution, 2023)

Recent advances in palladium-catalyzed reactions in water - Dao-Qing Dong; Hao Yang; Meng-Yu Zhou; Ze-Hui Wei; Pei Wu; Zu-Li Wang (Current Opinion in Green and Sustainable Chemistry, 2023)

Evaluation of BDE-47-induced neurodevelopmental toxicity in zebrafish embryos - Juan Zhuang; Zheng-jun Pan; Ying Qin; Hui Liang; Wen-feng Zhang; Ze-yu Sun; Han-bo Shi (Environmental Science and Pollution Research, 2023)

Generation of blunt snout bream without intermuscular bones by runx2b gene mutation - Qiang Dong; Chun-Hong Nie; Ya-Ming Wu; Dong-Yang Zhang; Xu-Dong Wang; Tan Tu; Jian Jin; Zu-Yu Tian; Jun-Qi Liu; Zheng-Yu Xiao; Shi-Ming Wan; Ze-Xia Gao (Aquaculture, 2023)

Deciphering basic and key traits of antibiotic resistome in influent and effluent of hospital wastewater treatment systems - Lin Zhu; Ling Yuan; Xin-Yi Shuai; Ze-Jun Lin; Yu-Jie Sun; Zhen-Chao Zhou; Ling-Xuan Meng; Feng Ju; Hong Chen (Water Research, 2023)

Effects of short-term exposure to volatile pesticide dichlorvos on the olfactory systems in Spodoptera litura: Calcium homeostasis, synaptic plasticity and apoptosis - Shu-Shang Li; Shou-Min Fang; Jie Chen; Ze Zhang; Quan-You Yu (Science of The Total Environment, 2023)

Influence of natural resources, ICT, and financial globalization on economic growth: Evidence from G10 countries - Fu Ze; Wence Yu; Anis Ali; Sanil S. Hishan; Iskandar Muda; Khurshid Khudoykulov (Resources Policy, 2023)

Aflatoxin B1 exposure triggers hepatic lipotoxicity via p53 and perilipin 2 interaction-mediated mitochondria-lipid droplet contacts: An in vitro and in vivo assessment - Lin Che; Jing Huang; Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Ze-Bang Du; Jia-Shen Wu; Zhong-Ning Lin; Yu-Chun Lin (Journal of Hazardous Materials, 2023)

Alga-based dairy wastewater treatment scheme: Candidates screening, process advancement, and economic analysis - Meng Ma; Ze Yu; Liqun Jiang; Qingjie Hou; Zhen Xie; Mingyan Liu; Siteng Yu; Haiyan Pei (Journal of Cleaner Production, 2023)

Metabolomics integrated with transcriptomics unveil the regulatory pathways of modified atmosphere packaging–maintained leaf quality of Chinese flowering cabbage - Zhen-liang Mou; Ling Wang; Ze-xiang Zeng; Xin-guo Su; Shu-juan Ji; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Yu-long Chen; Ya-ting Zhao; Jian-ye Chen (Food Chemistry, 2023)

Shrub encroachment increases soil erosion risk in hillside alpine meadows of the Qinghai-Tibetan Plateau, NW China - Yi-Fan Liu; Hui Fang; Ze Huang; Pedro A.M. Leite; Yu Liu; Manuel López-Vicente; Jingxue Zhao; Zhi-Hua Shi; Gao-Lin Wu (CATENA, 2023)

Rising temperatures affect the interspecific interference competition between Harmonia axyridis and Propylea japonica, and their predation rate on Myzus persicae - Xing-Lin Yu; Yu-Jie Zhang; Jun-Feng Zuo; Xun Luo; Long Zhang; Zhuo-Ma Danzeng; Bo Wang; Peng-Liang Xia; Shi-Ze Zhang; Tong-Xian Liu; Yi Feng (Journal of Pest Science, 2023)

From lab to application: Cultivating limnetic microalgae in seawater coupled with wastewater for biodiesel production on a pilot scale - Ze Yu; Qingjie Hou; Mingyan Liu; Zhen Xie; Meng Ma; Huiying Chen; Haiyan Pei (Water Research, 2023)

Extracellular polymeric substances trigger microbial immigration from partial denitrification (PD) to anammox biofilms in a long-term operated PD/anammox process in low-strength wastewater - Lifang Yu; Qiong Zhang; Ren Li; Bingchuang Qiao; Ze Wang; Lanxiang Zheng; Dangcong Peng (Water Research, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Recovery and recycling core of phosphogypsum: Characteristic hazardous elements risk assessment and analysis - Chao-Qiang Wang; Ze-Yuan Wang; De-Ming Huang; Qi-Cong Huang; Yu Chen; Huan Zhang; Zhong-He Shui (Process Safety and Environmental Protection, 2023)

Co-substrate promoting the biodegradation of refractory DOM in semi-coking wastewater: DOM evolution and microbial community - Min-Hui Cai; Ye-Chao Tian; Ai-Min Li; Yan Li; Yu-Ze Han; Jun Li; Hong-Fang Sun; Xin Wang; Qing Zhou; Wen-Tao Li (Journal of Environmental Chemical Engineering, 2023)

Study on the Damage Mechanism and Energy Evolution Characteristics of Water-Bearing Coal Samples Under Cyclic Loading - Hongxin Xie; Xuehua Li; Changhao Shan; Ze Xia; Liqiang Yu (Rock Mechanics and Rock Engineering, 2023)

Somatostatin-Positive Neurons in the Rostral Zona Incerta Modulate Innate Fear-Induced Defensive Response in Mice - Shan Lin; Meng-Yue Zhu; Meng-Yu Tang; Mi Wang; Xiao-Dan Yu; Yi Zhu; Shi-Ze Xie; Dan Yang; Jiadong Chen; Xiao-Ming Li (Neuroscience Bulletin, 2023)
Defensive behaviors induced by innate fear or Pavlovian fear conditioning are crucial for animals to avoid threats and ensure survival. The zona incerta (ZI) has been demonstrated to play important roles in fear learning and fear memory, as well as modulating auditory-induced innate defensive behavior. However, whether the neuronal subtypes in the ZI and specific circuits can mediate the innate fear response is largely unknown. Here, we found that somatostatin (SST)-positive neurons in the rostral ZI of mice were activated by a visual innate fear stimulus. Optogenetic inhibition of SST-positive neurons in the rostral ZI resulted in reduced flight responses to an overhead looming stimulus. Optogenetic activation of SST-positive neurons in the rostral ZI induced fear-like defensive behavior including increased immobility and bradycardia. In addition, we demonstrated that manipulation of the GABAergic projections from SST-positive neurons in the rostral ZI to the downstream nucleus reuniens (Re) mediated fear-like defensive behavior. Retrograde trans-synaptic tracing also revealed looming stimulus-activated neurons in the superior colliculus (SC) that projected to the Re-projecting SST-positive neurons in the rostral ZI (SC-ZIr SST -Re pathway). Together, our study elucidates the function of SST-positive neurons in the rostral ZI and the SC-ZIr SST -Re tri-synaptic circuit in mediating the innate fear response.

The interaction of MC3R and MC4R with MRAP2a in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; De-Bin Zhong; Xin Ren; Hao-Lin Mo; Ze-Bin Jiang; Jia-Jia Yu; Dong-Mei Xiong; Hai-Xia Liu; Li-Xin Wang (Fish Physiology and Biochemistry, 2023)

Mechanism for the adsorption of Per- and polyfluoroalkyl substances on kaolinite: Molecular dynamics modeling - Ze-Wei Ke; Sheng-Jie Wei; Peng Shen; Yun-Min Chen; Yu-Chao Li (Applied Clay Science, 2023)

Trajectory Data Compression Algorithm Based on Ship Navigation State and Acceleration Variation - Junbo Gao; Ze Cai; Wangjing Yu; Wei Sun (Journal of Marine Science and Engineering, 2023)
An active area of study under the dual carbon target, which is based on automatic identification systems (AIS), is the emission inventory of pollutants from ships. Data compression is required because there is currently so much data that it has become difficult to transmit, process, and store it. A trajectory simplification method considering the ship sailing state and acceleration rate of change is developed in this paper to assure the validity of the compressed data used in the emission inventory analysis. By carefully examining the integral relationship between acceleration and pollution emissions, the algorithm constructs an acceleration rate of change function for data compression and categorizes AIS data by ship navigation status. By dynamically altering the amount of acceleration change, the developed function can stabilize the pollutant emission calculation error and adaptively calculate the threshold value. The experimental results show that the emission calculation error of the proposed algorithm is only 0.185% when the compression rate is 90.28%.

An integrated monitoring system for disaster-causing organisms in the water intake areas of coastal nuclear power plants - Chao Li; Jian-ling Huo; Yu-ze Song; Lei Yang; Song-tang Liu (Frontiers in Marine Science, 2023)
Nowadays, nuclear power plays an important role in the energy structure of many countries. However, A bloom of a disaster-causing organism (DCO) in the cold-water intake area of a coastal nuclear power plant can block the water cooling system and seriously affect the operational safety of the nuclear power unit. Currently, the traditional method of protection is to estimate the DCO abundance by regular manual investigation and sampling, but that method cannot give continuous real-time data. Instead, proposed and implemented here is a seafloor in situ integrated monitoring system for DCOs (known as IMSDCO), which is equipped with an optical microscopic imager (OMI) and hydrometric sensors to monitor automatically the DCO abundance and hydrology. All the data are transmitted to a terminal in the shore station through a photoelectric composite cable for real-time display. When the DCO abundance reaches a preset threshold, software automatically raises an alarm. Since placing IMSDCO at the cold-water intake of the Changjiang nuclear power plant, a six-month field trial has been completed, during which large amounts of hydrology data and DCO images were obtained. IMSDCO successfully identified and estimated the abundances of various DCOs (e.g., Phaeocystis globosa , Acetes chinensis , and small fish) and predicted their movements based on hydrology data. Based on the analysis of the experimental data, we discussed the reasons for the error in the abundance estimation of DCO and the methods to reduce the error. The experimental results show that the OMI-based IMSDCO can monitor and give early warning of DCOs in the water intake areas of costal nuclear power plants and is worthy of long-term deployment.

The construction of high efficient visible-light-driven 3D porous g-C3N4/Fe3O4 photocatalyst: A new photo-induced bacterial inactivation material enhanced by cascade photo-Fenton reaction - Ze-Yu Liu; Wen-Qian Huang; Chuan-Qing Huang; Zhao-Zhen Liu; Xiao-Yue Tang; Wei-Chang Chen; Zheng-Zheng Tang; Yu-Xing Huang; Shuo-Chun Zheng; Lin Lin; Changzhu Li; Yong Ye (Chemosphere, 2023)

Association between exposure to perfluoroalkyl substances and uric acid in Chinese adults - Ze Yang; Kun Men; Jiaxin Guo; Ruifang Liu; Hongbo Liu; Jiemin Wei; Jingyun Zhang; Liangpo Liu; Xiaohui Lin; Mingyue Zhang; Yong Liu; Yu Chen; et al. (Chemosphere, 2023)

Sound absorption characteristics of loose bituminous coal porous media with different metamorphic degrees - Shuai-Jing Ren; Teng Ma; Yan-Ni Zhang; Jun Deng; Yang Xiao; Xiao-Wei Zhai; Yu-Tao Zhang; Ze-Yang Song; Cai-Ping Wang (Fuel, 2023)

Cation-doped V2O5 microsphere as a bidirectional catalyst to activate sulfur redox reactions for lithium-sulfur batteries - Fan-Jun Liu; Wen-Lin Luo; Ze Zhang; Ji Yu; Jian-Xin Cai; Zhen-Yu Yang (Chemical Engineering Journal, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Noble-metal-free 3D hierarchical Ni-WC heterostructure with enhanced interfacial charge transfer for efficient electrocatalytic hydrodechlorination - Qi Wang; Jing Du; Yuan-Yuan Ma; Xiao-Yu Yin; Ze-Yu Tian; Zhan-Gang Han (Chemical Engineering Journal, 2023)

Study on salt expansion mechanism of subgrade-culvert transition section in saline soils and cold regions - Yu Zhang; Run-ze Tian; Tian-liang Wang (Cold Regions Science and Technology, 2023)

Retraction notice to “Potential of β-elemene induced ferroptosis through Pole2-mediated p53 and PI3K/AKT signaling in lung cancer cells” [Chem. Biol. Interact. 365 (25 September 2022) 110088] - Zheng Gong; Ze-Gang Liu; Kun-Yu Du; Jiang-Hai Wu; Na Yang; Anshoo Malhotra; Jing-Kui Shu (Chemico-Biological Interactions, 2023)

Clinical Decision on Disorders of Consciousness After Acquired Brain Injury: Stepping Forward - Rui-Zhe Zheng; Zeng-Xin Qi; Zhe Wang; Ze-Yu Xu; Xue-Hai Wu; Ying Mao (Neuroscience Bulletin, 2023)

The growth and lipid accumulation of Scenedesmus quadricauda under nitrogen starvation stress during xylose mixotrophic/heterotrophic cultivation - Yiwen Mou; Na Liu; Kunyang Su; Xue Li; Tianxiang Lu; Ze Yu; Mingming Song (Environmental Science and Pollution Research, 2022)

Evaluation of the Anti-Inflammatory Activity of Enzymatic Hydrolysis Peptide SEP-3 from Skipjack ( Katsuwonus pelamis ) Based on NF-κB and MAPK Pathways - Chong Yi; Yue Wu; Zhi-gao Wang; Kun-mei Wang; Ze-kun Zhang; Bin Wang; Hong-yu Luo (Journal of Aquatic Food Product Technology, 2022)

Immobilization of Cd2+ and Pb2+ by biomineralization of the carbonate mineralized bacterial consortium JZ1 - Peng Zhang; Xiao-Qiang Liu; Li-yuan Yang; Hua-ze-yu Sheng; An-qi Qian; Ting Fan (Environmental Science and Pollution Research, 2022)

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

New polymerized sesquiterpene lactones from Ainsliaea yunnanensis and their activity evaluation - Na Zhou; Jin-Jie Li; Yong Wu; Ze-Yu Wang; Xin Wang; Zhi-Peng Yin; Xin-Peng Wang; Yi-Ran Liu; Xiao-Ya Shang (Natural Product Research, 2022)

Characterization of the transcription factor Sox3 regulating the gonadal development of pearlscale angelfish (Centropyge vrolikii) - Yan Feng; Zhao-wei Zhong; Yan Xu; Ze-yu Zhang; Lu-lu Ao; Zhen Yang; Yi-lei Wang; Yong-hua Jiang (Fish Physiology and Biochemistry, 2022)

Oceanobacillus saliphilus sp. nov., Isolated from Saline−Alkali Soil in Heilongjiang Province, China - Yu-Ting OuYang; Meng-Meng Li; Ai-Ping Lv; Pin-Jiao Jin; Lan Liu; Ze-Tao Liu; Jian-Yu Jiao; Wen-Jun Li; Li-Xiang Cao; Shuang Wang (Current Microbiology, 2022)

Paracandidimonas lactea sp. nov., a urea-utilizing bacterium isolated from landfill - Chu Zhang; Qian Pu; Jun-jie Ying; Ying Chen; Cheng-ze Li; Hang-tao Wu; Bin-jie Wang; Yu-han Zhang; Guo-hong Zeng; Ou Li; Xiu-fang Hu; Cong Sun (Archives of Microbiology, 2022)

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

Prevention of water and mud inrush in longwall top coal cave mining under shallow buried thin bedrock - Liu Zhu; Qiangling Yao; Ze Xia; Qiang Xu; Liqiang Yu; Xuehua Li (Bulletin of Engineering Geology and the Environment, 2022)

Trophinin-associated protein expression correlates with shorter survival of patients with glioma: a study based on multiple data fusion analysis - Yong Sun; Zhen Dong Liu; Run Ze Liu; Xiao Yu Lian; Xing Bo Cheng; Yu Long Jia; Bin Feng Liu; Yan Zheng Gao; Xinjun Wang (Molecular Biology Reports, 2022)

Fracability Evaluation Based on the Three-Dimensional Geological Numerical Simulation of In Situ Stress: Case Study of the Longmaxi Formation in the Weirong Shale Gas Field, Southwestern China - Ze Li; Gao Li; Hao Yu; Long He; Zujun Jiang; Hongzhi Li; Hanbo Gong (Mathematical Geosciences, 2022)

Shoot organogenesis and somatic embryogenesis in leaf tissue of Pulsatilla tongkangensis Y.N. Lee & T.C. Lee - Xiao-mei Zhao; Yu-ji Lian; Ze-lin Jin; Xue-jie Zhang; Yan Y; Shou-jin Fan (Plant Biotechnology Reports, 2022)

Twelve natural estrogens in urines of six threatened or endangered mammalian species in Zoo Park: implications and their potential risk - Zhao Tang; Ze-hua Liu; Wu Chen; Chen Wang; Ya-jiang Wu; Hao Wang; Zhi Dang; Yu Liu (Environmental Science and Pollution Research, 2022)

Grain size-dependent geochemical evidence reveals provenance and implications of aeolian sands, Dinggye region, southern Tibet - You-gui Chen; Mei-hui Pan; Ze-wen Hao; Yu-han Qi; Chen-lu Li (Journal of Mountain Science, 2022)

Rhodoflexus caldus gen. nov., sp. nov., a new member of the phylum Bacteroidota isolated from a hot spring sediment - Ze-Tao Liu; Lan Liu; Wen-Dong Xian; Zheng-Han Lian; Jun-Yi Dai; Bao-Zhu Fang; Meng-Meng Li; Ai-Ping Lv; Zhen-Hao Luo; Jian-Yu Jiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Cadinane-type sesquiterpenes with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Mappianthus iodoides - Yan-Ping Liu; Xiao-Mei Yu; Ze-Hua Qiao; Bo Jiang; Lan Xie; Hao-Xuan Tang; Xiao Liang; Yan-Hui Fu (Natural Product Research, 2022)

Tracking Neural Stem Cells in vivo: Achievements and Limitations - Chun-Ran Xue; Kan Wang; Meng-Ze Zhang; Ze Wang; Ya-Ying Song; Hao-Jun Yu; Yong Hao; Yang-Tai Guan (Stem Cell Reviews and Reports, 2022)

Signaling Mechanism for Modulation by GLP-1 and Exendin-4 of GABA Receptors on Rat Retinal Ganglion Cells - Tao Zhang; Hang-Ze Ruan; Yong-Chen Wang; Yu-Qi Shao; Wei Zhou; Shi-Jun Weng; Yong-Mei Zhong (Neuroscience Bulletin, 2022)
Glucagon-like peptide-1 (GLP-1) is expressed in retinal neurons, but its role in the retina is largely unknown. Here, we demonstrated that GLP-1 or the GLP-1 receptor (GLP-1R; a G protein-coupled receptor) agonist exendin-4 suppressed γ-aminobutyric acid receptor (GABAR)-mediated currents through GLP-1Rs in isolated rat retinal ganglion cells (GCs). Pre-incubation with the stimulatory G protein (G s ) inhibitor NF 449 abolished the exendin-4 effect. The exendin-4-induced suppression was mimicked by perfusion with 8-Br-cAMP (a cAMP analog), but was eliminated by the protein kinase A (PKA) inhibitor Rp-cAMP/KT-5720. The exendin-4 effect was accompanied by an increase in [Ca 2+ ] i of GCs through the IP 3 -sensitive pathway and was blocked in Ca 2+ -free solution. Furthermore, when the activity of calmodulin (CaM) and CaM-dependent protein kinase II (CaMKII) was inhibited, the exendin-4 effect was eliminated. Consistent with this, exendin-4 suppressed GABAR-mediated light-evoked inhibitory postsynaptic currents in GCs in rat retinal slices. These results suggest that exendin-4-induced suppression may be mediated by a distinct G s /cAMP-PKA/IP 3 /Ca 2+ /CaM/CaMKII signaling pathway, following the activation of GLP-1Rs.

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Colletotrichum litangense sp. nov., Isolated as an Endophyte of Hippuris vulgaris, an Aquatic Plant in Sichuan, China - Jie Li; Hua Zheng; Ze-fen Yu; Min Qiao (Current Microbiology, 2022)

Prenylated coumarins from the fruits of Artocarpus heterophyllus with their potential anti-inflammatory and anti-HIV activities - Lei Tao; Ya-Ting Zhuo; Ze-Hua Qiao; Juan Li; Hao-Xuan Tang; Qiao-Mei Yu; Yun-Yao Liu; Yan-Ping Liu (Natural Product Research, 2022)

Metabolic tuning of a stable microbial community in the surface oligotrophic Indian Ocean revealed by integrated meta-omics - Zhang-Xian Xie; Ke-Qiang Yan; Ling-Fen Kong; Ying-Bao Gai; Tao Jin; Yan-Bin He; Ya-Yu Wang; Feng Chen; Lin Lin; Zhi-Long Lin; Hong-Kai Xu; Zong-Ze Shao; et al. (Marine Life Science & Technology, 2022)
Understanding the mechanisms, structuring microbial communities in oligotrophic ocean surface waters remains a major ecological endeavor. Functional redundancy and metabolic tuning are two mechanisms that have been proposed to shape microbial response to environmental forcing. However, little is known about their roles in the oligotrophic surface ocean due to less integrative characterization of community taxonomy and function. Here, we applied an integrated meta-omics-based approach, from genes to proteins, to investigate the microbial community of the oligotrophic northern Indian Ocean. Insignificant spatial variabilities of both genomic and proteomic compositions indicated a stable microbial community that was dominated by Prochlorococcus , Synechococcus , and SAR11. However, fine tuning of some metabolic functions that are mainly driven by salinity and temperature was observed. Intriguingly, a tuning divergence occurred between metabolic potential and activity in response to different environmental perturbations. Our results indicate that metabolic tuning is an important mechanism for sustaining the stability of microbial communities in oligotrophic oceans. In addition, integrated meta-omics provides a powerful tool to comprehensively understand microbial behavior and function in the ocean.

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Bacterial microbiota analysis demonstrates that ticks can acquire bacteria from habitat and host blood meal - Si-Si Li; Xiao-Yu Zhang; Xue-Jiao Zhou; Kai-Li Chen; Abolfazl Masoudi; Jing-Ze Liu; Yan-Kai Zhang (Experimental and Applied Acarology, 2022)

Genome-based reclassification of the genus Meiothermus along with the proposal of a new genus Allomeiothermus gen. nov - Jian-Yu Jiao; Zheng-Han Lian; Ze-Tao Liu; Lan Liu; Meng-Meng Li; Ai-Ping Lv; Wen-Dong Xian; Ting Zhou; Zhitang Lyu; Nimaichand Salam; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Stability properties of natural estrogen conjugates in different aqueous samples at room temperature and tips for sample storage - Jun Zhang; Yi-ping Wan; Ze-hua Liu; Hao Wang; Zhi Dang; Yu Liu (Environmental Science and Pollution Research, 2022)

Effects of Antrodia camphorata-Supplemented Diets on the Non-Specific Immune Responses and Disease Resistance of Orange-Spotted Grouper (Epinephelus coioides) against Vibrio alginolyticus and Streptococcus iniae - Hsiang-Chieh Chuang; Yin-Ze Shi; Chiu-Min Cheng; Chieh-Yu Pan; Ann-Chang Cheng (Journal of Marine Science and Engineering, 2022)
In Taiwan, the mushroom Antrodia camphorata (AC) is used for medicinal purposes, including cancer prevention and treatment. This study aimed to investigate the effect of AC-supplemented diets on the innate immunity and disease resistance of the orange-spotted grouper Epinephelus coioides against two bacterial infections—Vibrio alginolyticus and Streptococcus iniae. Orange-spotted groupers were fed AC-supplemented diets at 0 (control), 1.5, 3.0, 4.5, and 6.0 g kg−1 for 28 days and examined for innate immune responses and survival rates against V. alginolyticus and S. iniae. The results showed that the innate cellular and humoral immune parameters, including respiratory burst, phagocytic activity, and lysozyme activity of leukocytes, along with serum alternative complement activity (ACH50) and superoxide dismutase activity, as well as interleukin (IL)-4 and IL-6, were all significantly increased in groupers fed AC-supplemented diets. Groupers fed diets containing AC at doses higher than 3.0 g kg−1 had better survival rates than the control group 3–18 days after V. alginolyticus or S. iniae challenge. The enhanced disease resistance may be attributable to AC-induced innate immunity, suggesting that utilizing AC as a dietary supplement at 3.0 g kg−1 may enhance the disease resistance of orange-spotted groupers against Vibrio or Streptococcus infection.

Sulfite may disrupt estrogen homeostasis in human via inhibition of steroid arylsulfatase - Jun Zhang; Shu-shu Zhong; Ke-meng Zhao; Ze-hua Liu; Zhi Dang; Yu Liu (Environmental Science and Pollution Research, 2022)

Probiotic Therapy (BIO-THREE) Mitigates Intestinal Microbial Imbalance and Intestinal Damage Caused by Oxaliplatin - Wenzhen Yuan; Xingpeng Xiao; Xuan Yu; Fuquan Xie; Pengya Feng; Kamran Malik; Jingyuan Wu; Ze Ye; Peng Zhang; Xiangkai Li (Probiotics and Antimicrobial Proteins, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Functional characterization of melanocortin-3 receptor in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; Wei-Jia Song; Hui Wang; Hao-Lin Mo; Qiao Liu; Xin-Miao Zhang; Ze-Bin Jiang; Li-Xin Wang (Fish Physiology and Biochemistry, 2022)

Two new iridoid glycosides from the fruit of Gardenia jasminoides - Hai-Bo Li; Jin-Feng Ma; Yu-Dan Mei; Ling-Xian Liu; Ze-yu Cao; Dan-Feng Shi; Xin-Sheng Yao; Yang Yu (Natural Product Research, 2022)

Two new nor -lignans from Selaginella pulvinata (Hook. & Grev.) Maxim and their antihyperglycemic activities - Hua-Wei Lv; Yu-Xia Li; Meng Luo; Jia-Meng Qi; Ze-Fei Fu; Hong-Jian Zhang; Yuan-Qiang Guo; Chu Chu; Han-Bing Li; Ji-Zhong Yan (Natural Product Research, 2022)

Maribellus maritimus sp. nov., isolated from marine sediment - Yu-Qi Ye; Ze-Tian Han; Xin-Jiang Liu; Meng-Qi Ye; Zong-Jun Du (Archives of Microbiology, 2022)

Laboratory and field investigations of different bolting configurations for coal mine roadways in weak coal strata - Weijian Yu; Genshui Wu; Bao Pan; Chunlai Wang; Ke Li; Ze Liao (Bulletin of Engineering Geology and the Environment, 2021)

A novel investigation on casing deformation during hydraulic fracturing in the Weirong shale gas field, Sichuan basin, China - Ze Li; Gao Li; Hongtao Li; Hao Yu; Long He; Zujun Jiang (Arabian Journal of Geosciences, 2021)

Investigation on the statistical characteristics of geoelectric field seismic anomalies in the North–South seismic belt of Chinese mainland - Hou Ze-Yu; An Zhang-Hui; Fan Ying-Ying; Tan Da-Cheng; Fu A-Long; Wei Lei (Acta Geophysica, 2021)

Early Palaeozoic alkaline trachytes in the North Daba Mountains, South Qinling Belt: petrogenesis and geological implications - Hang Yang; Shao-Cong Lai; Jiang-Feng Qin; Ren-Zhi Zhu; Shao-Wei Zhao; Yu Zhu; Fang-Yi Zhang; Ze-Zhong Zhang; Xing-Ying Wang (International Geology Review, 2021)

Loganin ameliorates depression-like behaviors of mice via modulation of serotoninergic system - Chen-Hao Pan; Cong-Yuan Xia; Yu Yan; Yan Han; Rui Shi; Jun He; Ze-Xing Wang; Yu-Ming Wang; Wei-Ku Zhang; Jie-Kun Xu (Psychopharmacology, 2021)

Research progress in bioremediation of petroleum pollution - Yong Yang; Zhan-Wei Zhang; Rui-Xia Liu; Hai-Yan Ju; Xue-Ke Bian; Wan-Ze Zhang; Chuan-Bo Zhang; Ting Yang; Bing Guo; Chen-Lei Xiao; He Bai; Wen-Yu Lu (Environmental Science and Pollution Research, 2021)

Maternal exposure to sulfur dioxide and the risk of oral clefts in Liaoning Province, China: a population-based case-control study - Fang-Hua Liu; Ze Xing; Ting-Ting Gong; Jia-Yu Zhang; Yan-Hong Huang; Jing Li; Shu Liu; Yan-Ling Chen; Li-Li Li; Cheng-Zhi Jiang; Zong-Jiao Chen; Yu-Hong Zhao; et al. (Environmental Science and Pollution Research, 2021)

Gas-phase isopropanol degradation by nonthermal plasma combined with Mn-Cu/-Al2O3 - Ken-Lin Chang; Yu-Chieh Lin; Ming-Ze Qiu; Chun-Wei Tu; Chih-Ping Chang; Jhong-Lin Wu; Yung-Chang Lin; Chien-Kuei Chang (Environmental Science and Pollution Research, 2021)

Variations in aeolian landform patterns in the Gonghe Basin over the last 30 years - Yu-han Qi; Mei-hui Pan; Ze-wen Hao; An-na Yang; Wen-xuan Xue (Journal of Mountain Science, 2021)

5-HTTLPR polymorphism and depression risk in Parkinson's disease: an updated meta-analysis - Pengfei Cheng; Junxiang Zhang; Yu Wu; Wenting Liu; Jiaying Zhu; Ze Chen; Jiarui Zhang; Songwen Guan; Yiming Sun; Jingxia Wang (Acta Neurologica Belgica, 2021)

Altered structural and functional connectivity in CSF1R-related leukoencephalopathy - Fei-Xia Zhan; Ze-Yu Zhu; Qing Liu; Hai-Yan Zhou; Xing-Hua Luan; Xiao-Jun Huang; Xiao-Li Liu; Wo-Tu Tian; Shi-Ge Wang; Xiao-Xuan Song; Guang Chen; Ming-Liang Zhao; et al. (Brain Imaging and Behavior, 2021)

LAI scale effect research based on compact airborne spectrographic imager data in the Heihe Oasis - Xiao-ai Dai; Chao Liu; Nai-wen Li; Mei-lian Wang; Yu-wei Yang; Xing-ping Yang; Shi-qi Zhang; Xu-wei He; Zheng-li Yang; Heng Lu; Jing-zhong Li; Ze-kun Wang (Journal of Mountain Science, 2021)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

Legislation against endocrine-disrupting compounds in drinking water: essential but not enough to ensure water safety - Ze-hua Liu; Zhi Dang; Yu Liu (Environmental Science and Pollution Research, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

Thermaurantiacus tibetensis gen. nov., sp. nov., a novel moderately thermophilic bacterium isolated from hot spring microbial mat in Tibet - Yu-Zhen Ming; Lan Liu; Ai-Ping Lv; Wen-Dong Xian; Ze-Tao Liu; Meng-Meng Li; Jian-Yu Jiao; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Combining targeted sequencing and ultra-low-pass whole-genome sequencing for accurate somatic copy number alteration detection - Junfeng Fu; Weihua Guo; Cheng Yan; Zhenyang Lv; Yu Wang; Ze Wang; Zhe Fan; Ting Lei (Functional & Integrative Genomics, 2021)

Fitness of F1 hybrids between 10 maternal wild soybean populations and transgenic soybean - Jin Yue Liu; Ze Wen Sheng; Yu Qi Hu; Qi Liu; Sheng Qiang; Xiao Ling Song; Biao Liu (Transgenic Research, 2021)
The releasing of transgenic soybeans ( Glycine max (L.) Merr.) into farming systems raises concerns that transgenes might escape from the soybeans via pollen into their endemic wild relatives, the wild soybean ( Glycine soja Sieb. et Zucc.). The fitness of F1 hybrids obtained from 10 wild soybean populations collected from China and transgenic glyphosate-resistant soybean was measured without weed competition, as well as one JLBC-1 F1 hybrid under weed competition. All crossed seeds emerged at a lower rate from 13.33–63.33%. Compared with those of their wild progenitors, most F1 hybrids were shorter, smaller, and with decreased aboveground dry biomass, pod number, and 100-seed weight. All F1 hybrids had lower pollen viability and filled seeds per plant. Finally, the composite fitness of nine F1 hybrids was significantly lower. One exceptional F1 hybrid was IMBT F1, in which the composite fitness was 1.28, which was similar to that of its wild progenitor due to the similarities in pod number, increased aboveground dry biomass, and 100-seed weight. Under weed competition, plant height, aboveground dry biomass, pod number per plant, filled seed number per plant, and 100-seed weight of JLBC-1 F1 were lower than those of the wild progenitor JLBC-1. JLBC-1 F1 hybrids produced 60 filled seeds per plant. Therefore, F1 hybrids could emerge and produce offspring. Thus, effective measures should be taken to prevent gene flow from transgenic soybean to wild soybean to avoid the production F1 hybrids when releasing transgenic soybean in fields in the future.

Julichrome derivatives and gliotoxin from a soil derived Streptomyces sp. - Tong Shen; Le-Mei Li; Ze-Yu Xu; Yong-Dong Wang; Wei-Dong Xie (Natural Product Research, 2021)

Estimating normal effective stress degradation in sand under undrained simple shear condition - Ze-Xiang Wu; Christophe Dano; Pierre-Yves Hicher; Zhen-Yu Yin (European Journal of Environmental and Civil Engineering, 2021)

Development Range Determination of Gas Conducting Fissure Zones for Lower Protective Seam Mining in JINJIA Coal Mine - Xun Zhao; Tao Feng; Shuqing Li; Weijian Yu; Ping Wang; Ze Liao (Geotechnical and Geological Engineering, 2021)

Energy consumption, CO2 emissions, and agricultural disaster efficiency evaluation of China based on the two-stage dynamic DEA method - Fang-rong Ren; Ze Tian; Hang-sheng Chen; Yu-ting Shen (Environmental Science and Pollution Research, 2021)

Non-coding RNAS and colorectal cancer liver metastasis - Xiao-Yu Zhou; Bing Luo; Ze-Kun Jiang; Ying-Kang Xie; Feng-Cong Wu; Jiong-Qiang Huang; Jing-Song Chen (Molecular and Cellular Biochemistry, 2020)

High-precision downward continuation of potential fields algorithm utilizing adaptive damping coefficient of generalized minimal residuals - Zhi-Hou Zhang; Xiao-Long Liao; Ze-Yu Shi; Anthony R. Lowry; Yu Yao; Run-Qi Lu; Xiang-Tai Fan; Peng-Fei Liu; Si-Wei Zhao (Applied Geophysics, 2020)

A C‐type lectin with antibacterial activity in weather loach, Misgurnus anguillicaudatus - Xiao‐Wen Zhang; Cong‐Hui Yang; Hong‐Quan Zhang; Xin‐Tong Pan; Ze‐Yu Jin; Hong‐Wei Zhang; Xiao‐Hua Xia (Journal of Fish Diseases, 2020)
C‐type lectins are carbohydrate‐binding proteins that play important roles in immunity by serving as pattern recognition receptors. In the present study, a novel nattectin‐like C‐type lectin was obtained from the weather loach, Misgurnus anguillicaudatus , designated as MaCTL. MaCTL encodes a peptide with 165 amino acids, with a signal peptide and a single C‐type lectin domain (CTLD), containing a galactose‐specific QPD motif and a conserved Ca 2+ ‐binding site. Transcripts of MaCTL were significantly upregulated after immune challenge with its pathogen A. hydrophila . In vitro assays with recombinant MaCTL protein revealed that it exhibited hemagglutinating and bacterial agglutinating activities, in a Ca 2+ ‐dependent manner. MaCTL was found to bind to a wide range of bacteria, as well as bind to bacterial polysaccharides LPS and PGN. Moreover, MaCTL displayed antimicrobial activity by inhibiting the growth of bacteria. These results collectively suggest that MaCTL is involved in the antibacterial defence of weather loach.

Key rules of life and the fading cryosphere: Impacts in alpine lakes and streams - James J. Elser; Chenxi Wu; Angélica L. González; Daniel H. Shain; Heidi J. Smith; Ruben Sommaruga; Craig E. Williamson; Janice Brahney; Scott Hotaling; Joseph Vanderwall; Jinlei Yu; Vladimir Aizen; et al. (Global Change Biology, 2020)
Alpine regions are changing rapidly due to loss of snow and ice in response to ongoing climate change. While studies have documented ecological responses in alpine lakes and streams to these changes, our ability to predict such outcomes is limited. We propose that the application of fundamental rules of life can help develop necessary predictive frameworks. We focus on four key rules of life and their interactions: the temperature dependence of biotic processes from enzymes to evolution; the wavelength dependence of the effects of solar radiation on biological and ecological processes; the ramifications of the non‐arbitrary elemental stoichiometry of life; and maximization of limiting resource use efficiency across scales. As the cryosphere melts and thaws, alpine lakes and streams will experience major changes in temperature regimes, absolute and relative inputs of solar radiation in ultraviolet and photosynthetically active radiation, and relative supplies of resources (e.g., carbon, nitrogen, and phosphorus), leading to nonlinear and interactive effects on particular biota, as well as on community and ecosystem properties. We propose that applying these key rules of life to cryosphere‐influenced ecosystems will reduce uncertainties about the impacts of global change and help develop an integrated global view of rapidly changing alpine environments. However, doing so will require intensive interdisciplinary collaboration and international cooperation. More broadly, the alpine cryosphere is an example of a system where improving our understanding of mechanistic underpinnings of living systems might transform our ability to predict and mitigate the impacts of ongoing global change across the daunting scope of diversity in Earth's biota and environments.

Physiological and transcriptional response to heat stress in heat-resistant and heat-sensitive maize (Zea mays L.) inbred lines at seedling stage - De-Chuan Wu; Jia-Fei Zhu; Zhong-Ze Shu; Wei Wang; Cheng Yan; Shan-Bin Xu; De-Xiang Wu; Cheng-Yu Wang; Zhao-rong Dong; Genlou Sun (Protoplasma, 2020)

Whole-Brain Map of Long-Range Monosynaptic Inputs to Different Cell Types in the Amygdala of the Mouse - Jia-Yu Fu; Xiao-Dan Yu; Yi Zhu; Shi-Ze Xie; Meng-Yu Tang; Bin Yu; Xiao-Ming Li (Neuroscience Bulletin, 2020)
The amygdala, which is involved in various behaviors and emotions, is reported to connect with the whole brain. However, the long-range inputs of distinct cell types have not yet been defined. Here, we used a retrograde trans-synaptic rabies virus to generate a whole-brain map of inputs to the main cell types in the mouse amygdala. We identified 37 individual regions that projected to neurons expressing vesicular glutamate transporter 2, 78 regions to parvalbumin-expressing neurons, 104 regions to neurons expressing protein kinase C-δ, and 89 regions to somatostatin-expressing neurons. The amygdala received massive projections from the isocortex and striatum. Several nuclei, such as the caudate-putamen and the CA1 field of the hippocampus, exhibited input preferences to different cell types in the amygdala. Notably, we identified several novel input areas, including the substantia innominata and zona incerta. These findings provide anatomical evidence to help understand the precise connections and diverse functions of the amygdala.

The effect of blastomere loss during frozen embryo transfer on the transcriptome of offspring’s umbilical cord blood - Yan-Ting Wu; Ze-Han Dong; Cheng Li; Dai-Zhan Zhou; Jun-Yu Zhang; Yan Wu; Jing-Jing Xu; Yu Wang; Xiao-Qun Ye; Jian-Zhong Sheng; Li Wang; He-Feng Huang (Molecular Biology Reports, 2020)

Synthesis and molecular docking studies of novel pyrimidine derivatives as potential antibacterial agents - Xue-Qian Bai; Chun-Shi Li; Ming-Yue Cui; Ze-Wen Song; Xing-Yu Zhou; Chao Zhang; Yang Zhao; Tian-Yi Zhang; Tie-Yan Jiang (Molecular Diversity, 2020)

Energy geopolitics in Central Asia: China’s involvement and responses - Qiang Zhou; Ze He; Yu Yang (Journal of Geographical Sciences, 2020)

Evolutionary investment network and the emerging energy power in Central Asia: From the perspective of cross-border mergers and acquisitions - Ze He; Zhaohui Chong; Yu Yang; Yannan Zhou; Yi Liu (Journal of Geographical Sciences, 2020)

Dynamic transition mechanism analysis of the impact of energy development on urbanization in Central Asia - Yannan Zhou; Yu Yang; Zhouying Song; Ze He; Siyou Xia; Yawen Ren (Journal of Geographical Sciences, 2020)

A pair of new diastereoisomeric phenylpropanoid-substituted flavan from the leaves of Ilex centrochinensis - Hui Long; Yu Chen; Ze-Hua Hu; Shao-Jun Zhang; Lu-Jun Li (Natural Product Research, 2020)

Application of dairy manure as fertilizer in dry land in East China: field monitoring and model estimation of heavy metal accumulation in surface soil - Xiao-Yong Qian; Gen-Xiang Shen; Zhen-Qi Wang; Xiao-Hua Chen; Qing-Jie Zhao; Yu-Jie Bai; Zheng-Ze Tang (Environmental Science and Pollution Research, 2020)

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

Seasonal abundance and activity of the tick Dermacentor everestianus (Acari: Ixodidae) in the Tibetan Plateau, China - Ming Liu; Tuo Li; Jia Yang; Si-Si Li; Zhi-Jun Yu; Jing-Ze Liu (Experimental and Applied Acarology, 2020)

Microvirga arsenatis sp. nov., an arsenate reduction bacterium isolated from Tibet hot spring sediments - Ze-Tao Liu; Wen-Dong Xian; Meng-Meng Li; Lan Liu; Yu-Zhen Ming; Jian-Yu Jiao; Bao-Zhu Fang; Min Xiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2020)

Astrocytic GABAB Receptors in Mouse Hippocampus Control Responses to Behavioral Challenges through Astrocytic BDNF - Ji-Hong Liu; Ze-Lin Li; Yi-Si Liu; Huai-De Chu; Neng-Yuan Hu; Ding-Yu Wu; Lang Huang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

Mapping quantitative trait loci (QTLs) and estimating the epistasis controlling stem rot resistance in cultivated peanut (Arachis hypogaea) - Ziliang Luo; Renjie Cui; Carolina Chavarro; Yu-Chien Tseng; Hai Zhou; Ze Peng; Ye Chu; Xiping Yang; Yolanda Lopez; Barry Tillman; Nicholas Dufault; Timothy Brenneman; et al. (Theoretical and Applied Genetics, 2020)

Synchrotron Radiation-Based Three-Dimensional Visualization of Angioarchitectural Remodeling in Hippocampus of Epileptic Rats - Pan Gu; Zi-Hao Xu; Yu-Ze Cao; Sheng-Hui Liao; Qian-Fang Deng; Xian-Zhen Yin; Zhuo-Lu Wang; Zhuo-Hui Chen; Xin-Hang Hu; Hui Wang; Li-Zhi Li; Shi-Xin Liu; et al. (Neuroscience Bulletin, 2020)

L-type Calcium Channels are Involved in Iron-induced Neurotoxicity in Primary Cultured Ventral Mesencephalon Neurons of Rats - Yu-Yu Xu; Wen-Ping Wan; Sha Zhao; Ze-Gang Ma (Neuroscience Bulletin, 2020)

Preliminary study on the role of novel LysR family gene kp05372 in Klebsiella pneumoniae of forest musk deer - Wei Yang; Wu-you Wang; Wei Zhao; Jian-guo Cheng; Yin Wang; Xue-ping Yao; Ze-xiao Yang; Dong Yu; Yan Luo (Journal of Zhejiang University-SCIENCE B, 2020)

A straightforward procedure of parameters determination for sand: a bridge from critical state based constitutive modelling to finite element analysis - Ze-Xiang Wu; Zhen-Yu Yin; Yin-Fu Jin; Xue-Yu Geng (European Journal of Environmental and Civil Engineering, 2019)

The mitochondrial genome of the ornate sheep tick, Dermacentor marginatus - Yan-Kai Zhang; Zhi-Jun Yu; Xiao-Yu Zhang; Víchová Bronislava; Peťko Branislav; Jing-Ze Liu (Experimental and Applied Acarology, 2019)

Insights into transcriptional characteristics and homoeolog expression bias of embryo and de-embryonated kernels in developing grain through RNA-Seq and Iso-Seq - Jun Wei; Hong Cao; Jing-dong Liu; Jing-hong Zuo; Yu Fang; Chih-Ta Lin; Run-ze Sun; Wen-long Li; Yong-xiu Liu (Functional & Integrative Genomics, 2019)

A loop-mediated isothermal amplification assay can rapidly diagnose soybean root-rot and damping-off diseases caused by Pythium spinosum - Hui Feng; Jiajia Chen; Ze Yu; Zhe Li; Wenwu Ye; Yuanchao Wang; Xiaobo Zheng (Australasian Plant Pathology, 2019)

Orientin Improves Cognition by Enhancing Autophagosome Clearance in an Alzheimer’s Mouse Model - Yi Zhong; Qing-yu Zheng; Cheng-yan Sun; Ze Zhang; Kun Han; Ning Jia (Journal of Molecular Neuroscience, 2019)

Conservation and differentiation of polyphenol oxidase (PPO) gene introns in Triticum and Aegilops tauschii Coss. - Yun Fang Li; Yu Wu; Chun Yan Zhang; Lei Zhang; Ze Hou Liu; Chi Hong Zhang (Genetic Resources and Crop Evolution, 2019)

Associations of brain entropy (BEN) to cerebral blood flow and fractional amplitude of low-frequency fluctuations in the resting brain - Donghui Song; Da Chang; Jian Zhang; Qiu Ge; Yu-Feng Zang; Ze Wang (Brain Imaging and Behavior, 2019)

Numerical Calculation and Stability of the Yield and Enhanced Support Technology for Shaft - Weijian Yu; Ze Liu; Baifu An; Fangfang Liu; Yunbo Wang (Geotechnical and Geological Engineering, 2019)

Assessing China’s human-environment relationship - Yu Yang; Xiaoyun Li; Wen Dong; Jessie P. H. Poon; Hui Hong; Ze He; Yi Liu (Journal of Geographical Sciences, 2019)

Taxonomic structure and potential nitrogen metabolism of microbial assemblage in a large hypereutrophic steppe lake - Xiaodong Qu; Min Zhang; Yu Yang; Ying Xie; Ze Ren; Wenqi Peng; Xia Du (Environmental Science and Pollution Research, 2019)

Comparative expression analysis of let-7 microRNAs during ovary development in Megalobrama amblycephala - Tian Lan; Yu-Long Chen; Yasmeen Gul; Bo-Wen Zhao; Ze-Xia Gao (Fish Physiology and Biochemistry, 2019)

Diffusion of helium in FCT zircon - Shun Yu; Wen Chen; Jingbo Sun; Ze Shen (Science China Earth Sciences, 2019)

Diltiazem used as a tacrolimus-sparing agent for treatment of pediatric patients with refractory nephrotic syndrome: a case report and retrospective analysis - Jie-Yu Sun; Ya-Hui Hu; Hong-Li Guo; Xia Jing; Ze-Jun Xu; Fang Sun; Hui-Lei Guo; Xuan-Sheng Ding; Feng Chen; Jing Xu (European Journal of Clinical Pharmacology, 2019)

Complete Genome Sequence of Streptomyces olivoreticuli ATCC 31159 Which can Produce Anticancer Bestatin and Show Diverse Secondary Metabolic Potentials - Hong Yu Zhang; Ze Ping Xie; Ting Ting Lou; Su Ying Wang (Current Microbiology, 2019)

Comparative transcriptomic analysis reveals adriamycin-induced apoptosis via p53 signaling pathway in retinal pigment epithelial cells - Yu-chen Lin; Ze-ren Shen; Xiao-hui Song; Xin Liu; Ke Yao (Journal of Zhejiang University-SCIENCE B, 2018)

The life cycle and development characteristics of Dermacentor everestianus (Acari: Ixodidae) under field conditions in Qinghai–Tibet Plateau - Tuo Li; Ming Liu; Tian-Tian Zhang; Yuan Li; Wen-Ying Wang; Meng-Meng Li; Zhi-Jun Yu; Jing-Ze Liu (Experimental and Applied Acarology, 2018)

Complete plastid genome of Bupleurum boissieuanum, an endemic herb plant in western China - Ying Wu; Tian-Ze Zhang; Dai-Yu Qiu; Qiang Chai; Wei-Bing Fan; Zhong-Hu Li; Min-Feng Fang (Conservation Genetics Resources, 2018)

Effects of artificial aeration and iron inputs on the transformation of carbon and phosphorus in a typical wetland soil - Linlin Zhang; Ze Tang; Sijian Zhang; Xueying Jia; Xiaofei Yu; Guangzhi Sun; Yuanchun Zou (Journal of Soils and Sediments, 2018)

A Bayesian modeling approach for phosphorus load apportionment in a reservoir with high water transfer disturbance - Xia Liu; Yuan Wang; Jianfeng Feng; Chunli Chu; Yu Qiu; Ze Xu; Zeli Li; Yuqiu Wang (Environmental Science and Pollution Research, 2018)

Flow variability along a vegetated natural stream under various sediment transport rates - Hai-zhou Wang; Ze-xing Xu; Hai-ti Yu; Xie-kang Wang (Journal of Mountain Science, 2018)

Origin of Early Cretaceous Guandian adakitic pluton in central eastern China: partial melting of delaminated lower continental crust triggered by ridge subduction - Ze-Bin Luo; Shuo Xue; Li-Peng Zhang; He Li; Cong-Ying Li; Hong Zhang; Yu-Long Liu; Ming-Xing Ling; Weidong Sun (International Geology Review, 2018)

CYP46A1 and the APOEε4 Allele Polymorphisms Correlate with the Risk of Alzheimer’s Disease - Ling Li; Fan Zeng; Yu-Hui Liu; Hui-Yun Li; Shu-Yang Dong; Ze-Yan Peng; Yan-Jiang Wang; Hua-Dong Zhou (Molecular Neurobiology, 2018)

Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2018)

Modeling and multi-objective optimization for ANAMMOX process under COD disturbance using hybrid intelligent algorithm - Bin Xie; Yong-wen Ma; Jin-quan Wan; Yan Wang; Zhi-cheng Yan; Lin Liu; Ze-yu Guan (Environmental Science and Pollution Research, 2018)

New bioactive compounds from aquatic endophyte Chaetomium globosum - Bao-Hui Ruan; Ze-Fen Yu; Xue-Qiong Yang; Ya-Bin Yang; Ming Hu; Zhuo-Xi Zhang; Qing-Yan Zhou; Hao Zhou; Zhong-Tao Ding (Natural Product Research, 2018)

An Optimized and Feasible Preparation Technique for the Industrial Production of Hydrogel Patches - Wei-Ze Li; Wen-Xia Han; Xu-Liang Hao; Ning Zhao; Xi-Feng Zhai; Li-Bin Yang; Shu-Miao He; Yu-Chuan Cheng; Han Zhang; Li-Na Fu; Yan Zhang; Ze Liang (AAPS PharmSciTech, 2018)

Evolution of drug-resistant mutations in HBV genomes in patients with treatment failure during the past seven years (2010–2016) - Hong-yu Zhang; Long-gen Liu; Chun-yan Ye; Chun-hua Chen; Shuang-xiong Hang; Zhen Zhu; Hong-yu Shen; Ze-yu Huang; Wen-yi Chen; Yuan Xue (Virus Genes, 2018)

Safe sites of pollen placement: a conflict of interest between plants and bees? - Ze-Yu Tong; Shuang-Quan Huang (Oecologia, 2018)

Epigenetic modification of TLE1 induce abnormal differentiation in diabetic mice intestinal epithelium - Ji-hao Xu; Guang-cheng Chen; Can-ze Huang; Di Cheng; Ting-feng Wu; Si-yi Wang; Jie-yao Li; Tao Yu; Qi-kui Chen (Molecular and Cellular Biochemistry, 2018)

Kinetics and pathways of Bezafibrate degradation in UV/chlorine process - Xue-Ting Shi; Yong-Ze Liu; Yu-Qing Tang; Li Feng; Li-Qiu Zhang (Environmental Science and Pollution Research, 2018)

Establishing a Forecast Mathematical Model of Sugarcane Yield and Brix Reduction Based on the Extent of Pokkah Boeng Disease - Ze-ping Wang; Lu Liu; Yu-chi Deng; Yi-jie Li; Ge-min Zhang; Shan-hai Lin; Tie-guang He (Sugar Tech, 2017)

Anti-complementary constituents of Anchusa italica - Yu-zhen Hou; Kui-kui Chen; Xi-ling Deng; Ze-long Fu; Dao-feng Chen; Qi Wang (Natural Product Research, 2017)

Molecular evidence of tick-borne pathogens in Hyalomma anatolicum ticks infesting cattle in Xinjiang Uygur Autonomous Region, Northwestern China - Peifa Yu; Zhijie Liu; Qingli Niu; Jifei Yang; Mirza Omar Abdallah; Ze Chen; Guangyuan Liu; Jianxun Luo; Hong Yin (Experimental and Applied Acarology, 2017)

Copper-modified palygorskite is effective in preventing and treating diarrhea caused by Salmonella typhimurium - Da-wei Yao; Ze-zhong Yu; Na Li; Yu-nong Hou; Jia-rong Xu; De-ji Yang (Journal of Zhejiang University-SCIENCE B, 2017)

Identification of differentially expressed genes from Trichoderma atroviride strain SS003 in the presence of cell wall of Cronartium ribicola - Nai-Yong Liu; Ze-Ran Bao; Jing Li; Xin-Yu Ao; Jia-Ying Zhu; Yu-Hui Chen (Genes & Genomics, 2017)

Assessing the mean strength and variations of the time-to-time fluctuations of resting-state brain activity - Zhengjun Li; Yu-Feng Zang; Jianping Ding; Ze Wang (Medical & Biological Engineering & Computing, 2017)

Geochemistry, geochronology, and petrogenesis of mid-Cretaceous Talabuco volcanic rocks, central Tibet: implications for the evolution of the Bangong Meso-Tethys - Xi-Chong Hu; Bin Xia; Qiang-Tai Huang; Wei-Liang Liu; Yun Zhong; Ya-Juan Yuan; Lian-Ze Xia; Yu Wu; Xiao Zhang (International Geology Review, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

A chickpea NAC-type transcription factor, CarNAC6, confers enhanced dehydration tolerance in Arabidopsis - Yanmin Liu; Xingwang Yu; Sushuang Liu; Hui Peng; Abudoukeyumu Mijiti; Ze Wang; Hua Zhang; Hao Ma (Plant Molecular Biology Reporter, 2017)

Molecular characterization of HOXC8 gene and methylation status analysis of its exon 1 associated with the length of cashmere fiber in Liaoning cashmere goat - Wen L. Bai; Jiao J. Wang; Rong H. Yin; Yun L. Dang; Ze Y. Wang; Yu B. Zhu; Yu Y. Cong; Liang Deng; Dan Guo; Shi Q. Wang; Shu H. Yang; Hui L. Xue (Genetica, 2017)

Erratum to: Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

RETRACTED ARTICLE: Overexpression of miR-429 impairs intestinal barrier function in diabetic mice by down-regulating occludin expression - Tao Yu; Xi-Ji Lu; Jie-Yao Li; Ti-Dong Shan; Can-Ze Huang; Hui Ouyang; Hong-Sheng Yang; Ji-Hao Xu; Wa Zhong; Zhong-Sheng Xia; Qi-Kui Chen (Cell and Tissue Research, 2016)

The transcriptome response of Heliconius melpomene larvae to a novel host plant - Quan‐You Yu; Shou‐Min Fang; Ze Zhang; Chris D. Jiggins (Molecular Ecology, 2016)
In the warfare between herbivore and host plant, insects have evolved a variety of defensive mechanisms, including allelochemical transformation and excretion. Several studies have explored the transcriptome responses of insects after host plant shifts to understand these mechanisms. We investigated the plastic responses of Heliconius melpomene larvae feeding on a native host Passiflora menispermifolia and a less strongly defended nonhost species, Passiflora biflora . In total, 326 differentially expressed genes were identified, with a greater number upregulated on the more strongly defended native host. Functional annotation showed that detoxifying enzymes, transporters and components of peritrophic membrane were strongly represented. In total, 30 candidate detoxification genes were differentially expressed, with glutathione S‐transferases ( GST s) and UDP ‐glucuronosyltransferases (UGTs) showing the highest proportion of differential expression, 27.3% and 17.3%, respectively. These differentially expressed detoxification genes were shown to evolve mainly under the influence of purifying selection, suggesting that protein‐coding evolution has not played a major role in host adaptation. We found only one gene, GSTe3 , with evidence of adaptive evolution at H40, which is around the G‐site and might alter enzyme activity. Based on our transcriptome and molecular evolution analysis, we suggest that transcriptional plasticity of genes in a herbivore may play an important role in adaptation to a new host plant.

TDO as a therapeutic target in brain diseases - Cheng-Peng Yu; Ze-Zheng Pan; Da-Ya Luo (Metabolic Brain Disease, 2016)

Molecular characterization, expression and methylation status analysis of BMP4 gene in skin tissue of Liaoning cashmere goat during hair follicle cycle - Wen L. Bai; Yun L. Dang; Jiao J. Wang; Rong H. Yin; Ze Y. Wang; Yu B. Zhu; Yu Y. Cong; Hui L. Xue; Liang Deng; Dan Guo; Shi Q. Wang; Shu H. Yang (Genetica, 2016)

Engrailed-2 might play an anti-oncogenic role in clear-cell renal cell carcinoma - Cai-yong Lai; Yin Xu; Gan-shen Yu; Xun Wu; Yun-fei Li; Bin Pan; Bao-li Heng; Yi-jun Xue; Ze-xuan Su (Journal of Molecular Histology, 2016)

Demyelination and polycythemia in a case of paraganglioma - Xin-Bao Wang; Xiu-Yu Shi; Wen-Ze Wang; Guang Yang; Li-Ping Zou (Acta Neurologica Belgica, 2016)

Characterization of the life cycle of the tick Haemaphysalis tibetensis under field conditions in Qinghai-Tibet plateau - Ming Liu; Tuo Li; Zhi-Jun Yu; Xiao-He Gao; Chun-Wei Zuo; Rong-Rong Wang; Ning-Xin Li; Hui Wang; Jing-Ze Liu (Experimental and Applied Acarology, 2016)

Hurdles of CAR-T cell-based cancer immunotherapy directed against solid tumors - Bing-Lan Zhang; Di-Yuan Qin; Ze-Ming Mo; Yi Li; Wei Wei; Yong-Sheng Wang; Wei Wang; Yu-Quan Wei (Science China Life Sciences, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Allelic variations of α-gliadin genes from species of Aegilops section Sitopsis and insights into evolution of α-gliadin multigene family among Triticum and Aegilops - Zhuo Huang; Hai Long; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Genetica, 2016)

The spatial relationship between human activities and C, N, P, S in soil based on landscape geochemical interpretation - Huan Yu; Zheng-Wei He; Bo Kong; Zhong-Yin Weng; Ze-Ming Shi (Environmental Geochemistry and Health, 2016)

Inhibiting cyprinid herpesvirus-3 replication with CRISPR/Cas9 - Yicheng Zhao; Tiedong Wang; Ze Yu; Heming Wang; Bo Liu; Chunyan Wu; Chun-Bo Teng (Biotechnology Letters, 2016)

CarNAC4, a NAC-type chickpea transcription factor conferring enhanced drought and salt stress tolerances in Arabidopsis - Xingwang Yu; Yanmin Liu; Shuang Wang; Yuan Tao; Zhankui Wang; Yingjie Shu; Hui Peng; Abudoukeyumu Mijiti; Ze Wang; Hua Zhang; Hao Ma (Plant Cell Reports, 2016)

RETRACTED ARTICLE: MEK/ERK pathway activation by insulin receptor isoform alteration is associated with the abnormal proliferation and differentiation of intestinal epithelial cells in diabetic mice - Hui Ouyang; Hong-Sheng Yang; Tao Yu; Ti-Dong Shan; Jie-Yao Li; Can-Ze Huang; Wa Zhong; Zhong-Sheng Xia; Qi-Kui Chen (Molecular and Cellular Biochemistry, 2016)

Erratum to: Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2016)

Single Chemosensor for Double Analytes: Spectrophotometric Sensing of Cu2+ and Fluorogenic Sensing of Al3+ Under Aqueous Conditions - Jie Yang; Ze-li Yuan; Guang-qing Yu; Shun-li He; Qing-hong Hu; Qing Wu; Bo Jiang; Gang Wei (Journal of Fluorescence, 2016)

Repair of articular cartilage defects in rabbits through tissue-engineered cartilage constructed with chitosan hydrogel and chondrocytes - Ming Zhao; Zhu Chen; Kang Liu; Yu-qing Wan; Xu-dong Li; Xu-wei Luo; Yi-guang Bai; Ze-long Yang; Gang Feng (Journal of Zhejiang University-SCIENCE B, 2015)

Identification of the Avulsion-Injured Spinal Motoneurons - Min Tan; Ming-zhou Yuan; Tian-yu Sun; Ying-yu Xie; Lin-Lin Liu; Ying Tang; Ze-min Ling; Ying-qin Li; Guang-yin Yu; Li Hua Zhou (Journal of Molecular Neuroscience, 2015)

Characterization of low-molecular-weight glutenin subunit genes of Aegilops section Sitopsis and comparative analysis with those of wheat (Triticum aestivum L.) and some Aegilops species - ZHUO HUANG; HAI LONG; XIAO-FANG YU; YU-MING WEI; ZE-HONG YAN; YOU-LIANG ZHENG (Journal of Genetics, 2015)

A Novel Coumarin-Based Fluorescent Probe for the Detection of Hydrazine Both in Aqueous Solution and Vapor State - Yu-Hao Xiao; Gang Xi; Xuan-Xuan Zhao; Shuai Zhou; Ze-Quan Zhou; Bao-Xiang Zhao (Journal of Fluorescence, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

Physical regulation of stem cells differentiation into teno-lineage: current strategies and future direction - Jia Lin Chen; Wei Zhang; Ze Yu Liu; Boon Chin Heng; Hong Wei Ouyang; Xue Song Dai (Cell and Tissue Research, 2015)

Protective Effects of Poly (butyl) Cyanoacrylate Nanoparticles Containing Vasoactive Intestinal Peptide Against 6-Hydroxydopamine-Induced Neurotoxicity In Vitro - Zhi-Ran Xu; Wu-Fang Wang; Xin-Fang Liang; Ze-Hua Liu; Yu Liu; Liang Lin; Xuan Zhu (Journal of Molecular Neuroscience, 2015)

Isolation and Preliminary Functional Analysis of MxCS2: a Gene Encoding a Citrate Synthase in Malus xiaojinensis - De-Guo Han; Yan Shi; Bing Wang; Wei Liu; Ze-Yuan Yu; Bing-Yu Lv; Guo-Hui Yang (Plant Molecular Biology Reporter, 2015)

Orbilia yuanensis sp. nov. and its anamorph - Min Qiao; Jian-Ying Li; Hans-Otto Baral; Ying Zhang; Wen-Yun Qian; Hong-yan Su; Ze-Fen Yu (Mycological Progress, 2015)

Hyperacetylation of Histone H3K9 Involved in the Promotion of Abnormally High Transcription of the gdnf Gene in Glioma Cells - Zheng-Quan Yu; Bao-Le Zhang; Hai-Bo Ni; Ze-Hao Liu; Jian-Cun Wang; Qing-Xian Ren; Jian-Bing Mo; Ye Xiong; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2014)

2.5D induced polarization forward modeling using the adaptive finite-element method - Yi-Xin Ye; Yu-Guo Li; Ju-Zhi Deng; Ze-Lin Li (Applied Geophysics, 2014)

Efficacy of a high-growth reassortant H1N1 influenza virus vaccine against the classical swine H1N1 subtype influenza virus in mice and pigs - Feng Wen; Hai Yu; Fu-ru Yang; Meng Huang; Sheng Yang; Yan-Jun Zhou; Ze-Jun Li; Guang-Zhi Tong (Archives of Virology, 2014)

Photodegradation of Tri(Chloropropyl) Phosphate Solution by UV/O3 - Xin-Chao Ruan; Xiao Jin; Ze-Yu Yang; Qing-Fu Zeng (Water, Air, & Soil Pollution, 2014)

Role and Mechanism of Microglial Activation in Iron-Induced Selective and Progressive Dopaminergic Neurodegeneration - Wei Zhang; Zhao-fen Yan; Jun-hua Gao; Li Sun; Xi-yan Huang; Zhuo Liu; Shu-yang Yu; Chen-Jie Cao; Li-jun Zuo; Ze-Jie Chen; Yang Hu; Fang Wang; et al. (Molecular Neurobiology, 2014)

The Impact of Microbial Immune Enteral Nutrition on the Patients with Acute Radiation Enteritis in Bowel Function and Immune Status - Feng shao; Fu-ze Xin; Cheng-gang Yang; Dao-gui Yang; Yue-tang Mi; Jun-xiu Yu; Guo-yong Li (Cell Biochemistry and Biophysics, 2014)

Elevational patterns of endogenous hormones and their relation to resprouting ability of Quercus aquifolioides plants on the eastern edge of the Tibetan Plateau - Wan-Ze Zhu; San-Gen Wang; De-Zhen Yu; Yong Jiang; Mai-He Li (Trees, 2014)

RNA-seq methods for identifying differentially expressed gene in human pancreatic islet cells treated with pro-inflammatory cytokines - Bo Li; Chang Long Bi; Ning Lang; Yu Ze Li; Chao Xu; Ying Qi Zhang; Ai Xia Zhai; Zhi Feng Cheng (Molecular Biology Reports, 2014)

The role of Gracilaria lemaneiformis in eliminating the dissolved inorganic carbon released from calcification and respiration process of Chlamys farreri - Zeng Jie Jiang; Jian Guang Fang; Ting Ting Han; Yu Ze Mao; Jia Qi Li; Mei Rong Du (Journal of Applied Phycology, 2014)

Perception of potential sex pheromones and host-associated volatiles in the cotton plant bug, Adelphocoris fasciaticollis (Hemiptera: Miridae): morphology and electrophysiology - Liang Sun; Hai-Jun Xiao; Shao-Hua Gu; Yu-Yuan Guo; Ze-Wen Liu; Yong-Jun Zhang (Applied Entomology and Zoology, 2014)

Changes in Transcriptional Factor Binding Capacity Resulting from Promoter Region Methylation Induce Aberrantly High GDNF Expression in Human Glioma - Zheng-Quan Yu; Bao-Le Zhang; Qing-Xian Ren; Jian-Cun Wang; Ru-Tong Yu; De-Wei Qu; Ze-Hao Liu; Ye Xiong; Dian-Shuai Gao (Molecular Neurobiology, 2013)

The Preferential Binding of a Sensory Organ Specific Odorant Binding Protein of the Alfalfa Plant Bug Adelphocoris lineolatus AlinOBP10 to Biologically Active Host Plant Volatiles - Liang Sun; Shao-Hua Gu; Hai-Jun Xiao; Jing-Jiang Zhou; Yu-Yuan Guo; Ze-Wen Liu; Yong-Jun Zhang (Journal of Chemical Ecology, 2013)

Overexpression of a Malus xiaojinensis Nas1 Gene Influences Flower Development and Tolerance to Iron Stress in Transgenic Tobacco - De-Guo Han; Guo-Hui Yang; Ke-Dong Xu; Qin Shao; Ze-Yuan Yu; Bing Wang; Qiu-Lai Ge; Yang Yu (Plant Molecular Biology Reporter, 2013)

A correlation between acute kidney injury and myonecrosis after scheduled percutaneous coronary intervention - Min Zhang; Hao-yu Meng; Ying-ming Zhao; Zhi-wen Tao; Xiao-xuan Gong; Ze-mu Wang; Bo Chen; Zheng-xian Tao; Chun-jian Li; Tie-bing Zhu; Lian-sheng Wang; Zhi-jian Yang (Journal of Zhejiang University-SCIENCE B, 2013)

The Acute and Chronic Effects of Monosodium l-Glutamate on Serum Iron and Total Iron-Binding Capacity in the Jugular Artery and Vein of Pigs - Wu Xin; Shu Xugang; Chunyan Xie; Jun Li; Jiangning Hu; Yu-long Yin; Ze-yuan Deng (Biological Trace Element Research, 2013)

The Very Large G Protein Coupled Receptor (Vlgr1) in Hair Cells - Jin-Peng Sun; Rong Li; Hong-Ze Ren; An-Ting Xu; Xiao Yu; Zhi-Gang Xu (Journal of Molecular Neuroscience, 2013)

Photodegradation of Tri (2-chloroethyl) Phosphate in Aqueous Solution by UV/H2O2 - Xin-Chao Ruan; Rui Ai; Xiao Jin; Qing-Fu Zeng; Ze-Yu Yang (Water, Air, & Soil Pollution, 2013)

Brain-targeting research of 10-O-nicotinate ginkgolide B: a new prodrug of ginkgolide B - Ze-Yu Wu; Jian Pan; Yuan Yuan; Ai-Ling Hui; Yi Yang; An Zhou; Min Tao; Xiao-Jian Zhou (Medicinal Chemistry Research, 2012)

Source apportionment of sediment-associated aliphatic hydrocarbon in a eutrophicated shallow lake, China - Ji-Zhong Wang; Ze-Yu Yang; Tian-Hu Chen (Environmental Science and Pollution Research, 2012)

Ectopic expression of the apple mhgai2 gene brings about GA-insensitive phenotypes in tomatoes - Shuang-Shuang Wang; Chao Sun; Ze-Zhou Liu; Qing-Hua Shi; Yu-Xin Yao; Chun-Xiang You; Yu-Jin Hao (Acta Physiologiae Plantarum, 2012)

RT-PCR test for detecting porcine sapovirus in weanling piglets in Hunan Province, China - Guo-Hua Liu; Run-Cheng Li; Ze-Bin Huang; Jun Yang; Chao-Ting Xiao; Jing Li; Man-Xiang Li; Yun-Qiu Yan; Xing-Long Yu (Tropical Animal Health and Production, 2012)

Molecular characterization of four HMW glutenin genes from Heteranthelium piliferum C. E. Hubbard and Henrardia persica (Banks et Solander) Hochstetter - Xiang-Quan Wang; Ze-Hong Yan; Shou-Fen Dai; Deng-Cai Liu; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2012)

Pseudolaric acid B-driven phosphorylation of c-Jun impairs its role in stabilizing HIF-1alpha: a novel function-converter model - Bing Yu; Mei-Hong Li; Wei Wang; Ying-Qing Wang; Yi Jiang; Sheng-Ping Yang; Jian-Min Yue; Jian Ding; Ze-Hong Miao (Journal of Molecular Medicine, 2012)

Phylogeny and evolutionary history of the silkworm - Wei Sun; HongSong Yu; YiHong Shen; Yutaka Banno; ZhongHuai Xiang; Ze Zhang (Science China Life Sciences, 2012)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

Phosphorylation of GIT1 tyrosine 321 is required for association with FAK at focal adhesions and for PDGF-activated migration of osteoblasts - Yongxin Ren; Lipeng Yu; Jin Fan; Ze Rui; Zhengzhe Hua; Zitao Zhang; Ning Zhang; Guoyong Yin (Molecular and Cellular Biochemistry, 2012)

Seasonal variations of concentrations, profiles and possible sources of polycyclic aromatic hydrocarbons in sediments from Taihu Lake, China - Yuan Zhang; Guo-Liang Shi; Chang-Sheng Guo; Jian Xu; Ying-Ze Tian; Yin-Chang Feng; Yu-Qiu Wang (Journal of Soils and Sediments, 2012)

Allelic variation and distribution of HMW glutenin subunit 1Ay in Triticum species - Xi-Gui Hu; Bi-Hua Wu; Zhe-Guang Bi; Deng-Cai Liu; Lian-Quan Zhang; Ze-Hong Yan; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2012)

Seroprevalence of porcine cytomegalovirus and sapovirus infection in pigs in Hunan province, China - Guo-Hua Liu; Run-Cheng Li; Jing Li; Ze-Bin Huang; Chao-Ting Xiao; Wei Luo; Meng Ge; Da-Liang Jiang; Xing-Long Yu (Archives of Virology, 2012)

Orbilia blumenaviensis and its Arthrobotrys anamorph - Min Qiao; Ying Zhang; Shi-Fu Li; H.-O. Baral; E. Weber; Hong-Yan Su; Jian-Ping Xu; Ke-Qin Zhang; Ze-Fen Yu (Mycological Progress, 2012)

Molecular characterization of LMW glutenin genes from Taeniatherum Nevski - Chang Han; Ze-Hong Yan; Shou-Fen Dai; Deng-Cai Liu; Yu-Ming Wei; You-Liang Zheng; Xiu-Jin Lan; Yuan-Ying Peng (Genetic Resources and Crop Evolution, 2011)

TH-030418: a potent long-acting opioid analgesic with low dependence liability - Gang Yu; Ling-Di Yan; Yu-Lei Li; Quan Wen; Hua-Jin Dong; Ze-Hui Gong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Development and biological characteristics of Haemaphysalis longicornis (Acari: Ixodidae) under field conditions - Hongyuan Zheng; Zhijun Yu; Ze Chen; Lifeng Zhou; Bin Zheng; Hui Ma; Jingze Liu (Experimental and Applied Acarology, 2011)

Heme oxygenase is involved in cobalt chloride-induced lateral root development in tomato - Sheng Xu; Bo Zhang; Ze-Yu Cao; Teng-Fang Ling; Wen-Biao Shen (BioMetals, 2011)

Genetic analysis of avian paramyxovirus-1 (Newcastle disease virus) isolates obtained from swine populations in China related to commonly utilized commercial vaccine strains - Zhuang Ding; Yan-long Cong; Shuang Chang; Guang-mei Wang; Ze Wang; Quan-peng Zhang; Hao Wu; Yu-zhang Sun (Virus Genes, 2010)

A minimum traveltime ray tracing global algorithm on a triangular net for propagating plane waves - Shi-Jian Yu; Run-Ze Liu; Jiu-Long Cheng (Applied Geophysics, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Phylogenetic inferences in Avena based on analysis of FL intron2 sequences - Yuan-Ying Peng; Yu-Ming Wei; Bernard R. Baum; Ze-Hong Yan; Xiu-Jin Lan; Shou-Fen Dai; You-Liang Zheng (Theoretical and Applied Genetics, 2010)

Eutrophication assessment and bioremediation strategy in a marine fish cage culture area in Nansha Bay, China - Zeng Jie Jiang; Jian Guang Fang; Yu Ze Mao; Wei Wang (Journal of Applied Phycology, 2010)

Molecular diversity and phylogenetic analyses of y-type high-molecular-weight glutenin promoters from different genomes in Triticeae - Qian-Tao Jiang; Yu-Ming Wei; Ji-Rui Wang; Ze-Hong Yan; You-Liang Zheng (Plant Systematics and Evolution, 2010)

Disintegration of microsporocytes in a male sterile mutant of Brassica napus L. is possibly associated with endoplasmic reticulum-dependent autophagic programmed cell death - Hai Jun Wu; Xu Hao Liu; Kan Chen; Ze Ping Cai; Xin Juan Luo; Tao Zhang; Xin Yu Wang (Euphytica, 2009)

The construction of siRNA plasmid targeting mouse HIF-1α and in vitro study of its inhibition effect - Zhen-Yu Ding; Ze-Gui Li; Yi-Zhan Xing; Hua Ji; Hong-Li Li; Zhi-Jie Chang (Neuroscience Bulletin, 2009)

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules - Hai-Lian Shen; Zhi-Gang Xu; Li-Yu Huang; Dong Liu; Dao-Hong Lin; Jia-Bin Cao; Xin Zhang; Zhi-Qin Wang; Wen-Hui Wang; Peng-Yuan Yang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2009)

SNP and haplotype identification of the wheat monomeric α-amylase inhibitor genes - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Genetica, 2008)

hBolA, novel non-classical secreted proteins, belonging to different BolA family with functional divergence - Yu-Bo Zhou; Jia-Bing Cao; Bing-Bing Wan; Xin-Rong Wang; Guo-Hui Ding; Hong Zhu; Hong-Meng Yang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2008)

Influence of dietary conjugated linoleic acid on growth, fatty acid composition and hepatic lipogenesis in large yellow croaker (Pseudosciaena crocea R.) - Zhan-yu Zhao; Tian-xing Wu; Hong-gang Tang; Ji-ze Zhang (Journal of Zhejiang University-SCIENCE B, 2008)

Sequence Variations and Haplotype Identification of Wheat Dimeric α-Amylase Inhibitor Genes in Einkorn Wheats - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Biochemical Genetics, 2007)

Two new species of Trichoderma from Yunnan, China - Ze-Fen Yu; Min Qiao; Ying Zhang; Ke-Qin Zhang (Antonie van Leeuwenhoek, 2007)

EST-SSR DNA polymorphism in durum wheat (Triticum durum L.) collections - Han -Yan Wang; Yu -Ming Wei; Ze -Hong Yan; You -Liang Zheng (Journal of Applied Genetics, 2007)

ZBTB34, a novel human BTB/POZ zinc finger protein, is a potential transcriptional repressor - Jia Qi; Xin Zhang; Hai-Kuo Zhang; Hong-Meng Yang; Yu-Bo Zhou; Ze-Guang Han (Molecular and Cellular Biochemistry, 2006)

Genetic mapping of the wheat dimeric α-amylase inhibitor multi-gene family using allele-specific primers based on intergenomic SNPs - Ji-Rui Wang; Yu-Ming Wei; Ze-Hong Yan; You-Liang Zheng (Plant Molecular Biology Reporter, 2006)

Characterization of two HMW glutenin subunit genes from Taenitherum Nevski - Ze-Hong Yan; Yu-Ming Wei; Ji-Rui Wang; Deng-Cai Liu; Shou-Fen Dai; You-Liang Zheng (Genetica, 2006)

A high-molecular-weight glutenin subunit gene 1Dx2.1 from Xinjiang rice wheat - Qian-Tao Jiang; Yu-Ming Wei; Ji-Rui Wang; Ze-Hong Yan; You-Liang Zheng (Cereal Research Communications, 2005)

Classification of wheat low-molecular-weight glutenin subunit genes and its chromosome assignment by developing LMW-GS group-specific primers - Hai Long; Yu-Ming Wei; Ze-Hong Yan; Bernard Baum; Eviatar Nevo; You-Liang Zheng (Theoretical and Applied Genetics, 2005)

Macroscopic phototactic behavior of the purple photosynthetic bacterium Rhodospirillum centenum - Lisa Ragatz; Ze-Yu Jiang; Carl E. Bauer; Howard Gest (Archives of Microbiology, 1995)

Allelic constitution of the hemoglobin beta chain in wild populations of the house mouse, Mus musculus - Nobumoto Miyashita; Kazuo Moriwaki; Mitsuru Minezawa; Hiromichi Yonekawa; Francois Bonhomme; Shunsuke Migita; Ze-chang Yu; De-yuan Lu; Wang Su Cho; Machmud Thohari (Biochemical Genetics, 1985)